Dehydrogenation catalyst for organic hydrogen storage material and support therefor, hydrogen storage alloy, and method for supplying high-purity hydrogen gas

Through the combination of dehydrogenation reaction of liquid organic hydrogen storage materials and hydrogen storage alloys, the difficulties in hydrogen storage and transportation are solved, and high-purity and high-pressure hydrogen supply is achieved, reducing costs and improving safety.

JP7625538B2Active Publication Date: 2025-02-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021566297
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-06
Filing Date
2020-05-06
Publication Date
2025-02-03
Estimated Expiration
2040-05-06

AI Technical Summary

Technical Problem

In the prior art, there are difficulties in storing and transporting hydrogen. The transportation cost of high-pressure gaseous hydrogen is high and has high safety risks, and the storage tank costs are high and the danger is high, making it difficult to achieve safe and efficient hydrogen energy utilization.

Method used

The liquid organic hydrogen storage material is dehydrogenated by using a catalyst, combining the separation and purification methods of hydrogen storage alloy and high-purity hydrogen, including cooling, adsorption and heating processes, to achieve efficient hydrogen production and storage.

Benefits of technology

It realizes the safe and efficient supply of high-purity and high-pressure hydrogen, reduces transportation and storage costs, and improves the safety and efficiency of hydrogen energy utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625538000009
    Figure 0007625538000009
  • Figure 0007625538000010
    Figure 0007625538000010
  • Figure 0007625538000011
    Figure 0007625538000011
Patent Text Reader

Abstract

The present invention relates to a catalyst for producing hydrogen by dehydrogenating an organic hydrogen storage material, a support for the catalyst, and a method for preparing the catalyst.The present invention also relates to a hydrogen storage alloy and a method for preparing the same.The present invention also relates to a method for supplying high-purity hydrogen, a highly efficient distributed method for producing high-purity, high-pressure hydrogen, a supply system for high-purity, high-pressure hydrogen, a mobile hydrogen supply system, and a distributed hydrogen supply device.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] TECHNICAL FIELD The present invention relates to a catalyst for producing hydrogen gas by dehydrogenating an organic hydrogen storage material, a carrier for the catalyst, and a method for preparing the same. The present invention also relates to a hydrogen storage alloy and a method for preparing the same. The present invention also relates to a method for supplying high-purity hydrogen gas, a highly efficient distributed method for producing high-purity high-pressure hydrogen gas, a supply system for high-purity high-pressure hydrogen gas, a mobile hydrogen supply system, and a distributed hydrogen supply device.

[0002] [Background technology] As a renewable energy source, hydrogen gas is not only energy efficient but also produces little waste. The development of hydrogen gas energy sources is expected to be an important means of improving energy efficiency, reducing petroleum consumption, improving environmental pollution, and achieving energy security. The development of sustainable and efficient large-scale hydrogen production technology is an urgent need in the hydrogen energy era.

[0003] Hydrogen gas exists in a gaseous state under normal conditions, and due to its flammability, explosiveness, and diffusibility, in practical applications, the safety, efficiency, and leakage prevention of hydrogen storage and transportation must be given priority, which poses great difficulties in storage and transportation. Therefore, in order to utilize hydrogen energy, it is necessary to solve the problems of storing and transporting hydrogen gas.

[0004] Hydrogen gas is transported directly from the production site to the hydrogen refueling station in the form of high pressure gas, so the transportation cost is high and there are risks to road safety when transporting it over long distances. Storing hydrogen gas in the form of high pressure gas entails problems with the cost and land area required for hydrogen storage tanks, and is also highly dangerous.

[0005] Summary of the Invention The technical problem to be solved by the present invention is to provide a catalyst for producing hydrogen gas by dehydrogenating a hydrogen-absorbing organic compound, and a carrier for the catalyst. Another technical problem to be solved by the present invention is to provide a hydrogen-absorbing alloy used in a method for purifying an organic-containing hydrogen gas, and a method for preparing the same. A further technical problem to be solved by the present invention is to provide a method for supplying high-purity hydrogen gas, a highly efficient distributed method for producing high-purity high-pressure hydrogen gas, a supply system for high-purity high-pressure hydrogen gas, a mobile hydrogen supply system, and a distributed hydrogen supply device.

[0006] To this end, the present invention provides the following technical configurations: [1] A step (1) of contacting a liquid organic hydrogen storage raw material with a dehydrogenation catalyst to react with the raw material to obtain a dehydrogenation reaction product containing hydrogen gas; (2) cooling the dehydrogenation reaction product to obtain a liquid product and a hydrogen-rich gaseous product, and recovering the liquid product; (3) contacting the hydrogen-rich gas with a hydrogen storage alloy to obtain a hydrogen-containing alloy and recovering unabsorbed gas; Optionally, a step (3a) of removing organic matter within the containment vessel of the hydrogen-containing alloy; and (4) heating the hydrogen-containing alloy to release hydrogen gas.

[0007] [2] In step (1), The reaction temperature in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 150 to 450°C (for example, 200 to 400°C, 300 to 350°C), The weight space velocity per hour in the contact reaction between the liquid organic hydrogen storage material and the dehydrogenation catalyst is 0.5 to 50 h -1 (For example, 1~45h -1 , 2~30h -1 ) and The pressure in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 0.03 to 5 MPa (gauge pressure) (for example, 0.3 to 5 MPa, 0.1 to 3 MPa, 0.5 to 2 MPa, or 0.2 to 1.6 MPa); Optionally, when the mixture of the liquid organic hydrogen storage raw material and hydrogen gas is contacted with a dehydrogenation catalyst, the hydrogen to hydrocarbon ratio (the molar ratio of hydrogen gas to the liquid organic hydrogen storage raw material) is 0 to 10 (e.g., 0 to 8), according to any one of the above-mentioned technical configurations of the method for supplying high-purity hydrogen gas.

[0008] [3] In step (2), A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, wherein the cooling temperature for cooling the dehydrogenation reaction product is lower than the boiling point of the organic matter in the liquid product, and preferably lower than the boiling point of the organic matter with the lowest boiling point that becomes liquid at room temperature and normal pressure among the liquid product.

[0009] [4] In step (3), The hydrogen-rich gas is a hydrogen-rich gas product or a hydrogen-containing gas obtained by further separation of the hydrogen-rich gas product, the method of further separation including temperature swing separation, membrane separation, pressure swing adsorption separation, or a combination thereof; A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, wherein the mass fraction of hydrogen gas in the hydrogen-rich gas is ≧80% (e.g., 80 to 99%, preferably ≧85%, more preferably ≧90%).

[0010] [5] In step (3), contacting the hydrogen-rich gas with the hydrogen storage alloy in a containment vessel or vessels of the hydrogen storage alloy; The number of hydrogen storage alloys may be one or more, and the multiple hydrogen storage alloys may be used in a mixed form, and may be used in a series form, a parallel form, or a combination of series and parallel; the pressure at which the hydrogen-rich gas comes into contact with the hydrogen absorbing alloy is 0.001 to 5 MPa (e.g., 0.01 to 5 MPa, 0.03 to 4 MPa, 0.05 to 5 MPa, 0.08 to 2 MPa, 0.05 to 3 MPa, 0.1 to 1 MPa); and when there are a plurality of hydrogen absorbing alloy storage containers connected in series, the contact pressure (also called hydrogen adsorption pressure) at which the hydrogen-rich gas comes into contact with the most downstream hydrogen absorbing alloy in the flow direction is 0.05 to 5 MPa (e.g., 0.1 to 1 MPa); The temperature at which the hydrogen-rich gas comes into contact with the hydrogen storage alloy (also called the hydrogen adsorption temperature) is −70 to 100° C. (for example, −50 to 90° C., −30 to 80° C.); A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, wherein the temperature of the hydrogen-rich gas when in contact with the hydrogen storage alloy is lower than the boiling point of the liquid organic hydrogen storage raw material at normal pressure.

[0011] [6] In step (3), A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, wherein the number of storage vessels for the hydrogen storage alloy is one or more, the hydrogen storage alloy in the storage vessel for the hydrogen storage alloy that comes into contact with hydrogen gas last in the order of contact with hydrogen gas is a hydrogen storage alloy having a high equilibrium pressure, and the hydrogen storage alloy having high equilibrium pressure has at least one temperature point within a temperature range of 150 to 450°C at which the equilibrium pressure in hydrogen gas adsorption is 35 MPa or higher, and preferably the hydrogen storage alloy in at least one storage vessel for the hydrogen storage alloy is a hydrogen storage alloy having a high equilibrium pressure.

[0012] [7] A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, in which step (3a) is performed by a purging method for removing organic matter from a storage vessel of a hydrogen-containing alloy, for example, a purging method using hydrogen gas (for example, after a predetermined amount of adsorption in the hydrogen-absorbing alloy is reached, the supply of hydrogen-rich gas to the hydrogen-absorbing alloy is stopped, and hydrogen gas is passed through the hydrogen-containing alloy to expel organic gas from the hydrogen-containing alloy and the storage vessel of the hydrogen-containing alloy (also called the storage vessel of the hydrogen-absorbing alloy), and the organic gas is introduced into a storage tank for storage, or the organic gas is adsorbed by a hydrogen-absorbing alloy in a storage vessel of another hydrogen-absorbing alloy. The purity of the hydrogen gas for purging is preferably more than 90% by weight, more preferably more than 95% by weight, for example more than 99% by weight).

[0013] [8] In step (4), A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, wherein the temperature at which hydrogen gas is released from the hydrogen storage alloy (i.e., the temperature at which the hydrogen storage alloy is heated; abbreviated as hydrogen release temperature) is 150 to 450°C, the pressure of the released hydrogen gas is ≧35 MPa (e.g., 35 to 100 MPa) in order to obtain high-purity high-pressure hydrogen gas, or the partial pressure of the released hydrogen gas is 0.1 to 5 MPa in order to obtain high-purity hydrogen gas, and the hydrogen release temperature is higher than the hydrogen adsorption temperature.

[0014] [9] The method further includes a process of releasing hydrogen gas from a hydrogen-containing alloy and contacting the released hydrogen gas with another hydrogen storage alloy to form a hydrogen-containing alloy; A method for supplying high-purity hydrogen gas described in any one of the above-mentioned technical configurations, wherein the process is carried out once or multiple times, and the hydrogen storage alloy used in at least the last process is a hydrogen storage alloy having a high equilibrium pressure.

[0015]

[10] The hydrogen storage alloy is a combination of a first hydrogen storage alloy and a second hydrogen storage alloy, the first hydrogen storage alloy is a magnesium-based A2B-type hydrogen storage alloy for use in contact with a hydrogen-rich gas; The second hydrogen storage alloy is used for pressurizing the first hydrogen storage hydrogen gas and has a high equilibrium pressure, and the second hydrogen storage alloy is one or more of rare earth-based AB5 type, zirconium-titanium-based AB2 type, and titanium-based AB type hydrogen storage alloys; First, hydrogen-rich gas is passed through a first hydrogen storage alloy to separate impurities, then the high-purity hydrogen gas released from the first hydrogen storage alloy is brought into contact with a second hydrogen storage alloy, and then the hydrogen gas is released into the second hydrogen storage alloy under high pressure; The hydrogen desorption temperature of the first hydrogen storage alloy is higher than the hydrogen adsorption temperature of the second hydrogen storage alloy, and the temperature difference therebetween is preferably ≧100° C. (e.g., 350° C.≧temperature difference≧150° C.); the first hydrogen storage alloy and the second hydrogen storage alloy are present in storage tanks of different hydrogen storage alloys, and a heat exchange system is present between the storage tank of the first hydrogen storage alloy and the storage tank of the second hydrogen storage alloy; the hydrogen adsorption temperature during contact between the hydrogen-rich gas and the first hydrogen storage alloy is 20 to 150°C (e.g., 50 to 100°C), and the hydrogen partial pressure is 0.001 to 0.1 MPa (0.001 to 0.03 MPa); the temperature at which hydrogen gas is released from the first hydrogen storage alloy (hydrogen release temperature) is 150 to 450°C (e.g., 200 to 350°C), and the hydrogen gas partial pressure during hydrogen release is 0.1 to 5 MPa (e.g., 0.1 to 1 MPa); The hydrogen adsorption temperature at which the second hydrogen storage alloy adsorbs hydrogen gas is −70 to 100° C. (e.g., −30 to 100° C.), and the hydrogen gas partial pressure during hydrogen adsorption is 0.1 to 5 MPa (e.g., 0.1 to 1 MPa); A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, wherein the hydrogen release temperature of the second hydrogen storage alloy is 150 to 450°C (e.g., 200 to 350°C), and the hydrogen gas partial pressure during hydrogen release is ≧35 MPa (e.g., 35 to 100 MPa).

[0016]

[11] The liquid organic hydrogen storage raw material is an organic compound having a ring in the molecule and optionally containing a heteroatom, the heteroatom may be present in a ring shape; For example, saturated or unsaturated hydrocarbons containing a cycloalkane ring, for example, saturated or unsaturated hydrocarbons containing a cycloalkane ring but not a heterocyclic atom, more specifically, saturated or unsaturated hydrocarbons containing a cycloalkane ring but not a heterocyclic atom, in which the total number of aromatic rings and cycloalkane rings is 2 or less, for example, cyclohexane, methylcyclohexane, decahydronaphthalene, and bi(cyclohexane), and saturated or unsaturated hydrocarbons containing a cycloalkane ring containing a heteroatom, for example, nitrogen-containing heterocyclic compounds, and nitrogen / boron-containing heterocyclic compounds. The nitrogen-containing heterocyclic compound includes one or more of decahydrocarbazole, dodecahydroethylcarbazole, indoline, 4-aminopiperidine, piperidine-4-carboxamide, perhydro-4,7-phenanthroline, 2-methyl-1,2,3,4-tetrahydroquinoline, and 2,6-dimethyldecahydro-1,5-naphthyridine, and the nitrogen / boron-containing heterocyclic compound includes one or more of 1,2-azaborinate and 3-methyl-1,2-azaborolidine. A method for supplying high-purity hydrogen gas according to any one of the above technical configurations.

[0017]

[12] A method for supplying high-purity hydrogen gas according to any one of the above-mentioned technical configurations, further comprising a step of introducing the released hydrogen gas into a hydrogen gas storage tank to store the hydrogen gas, or a step of directly using the obtained high-purity high-pressure hydrogen gas to refuel a hydrogen fuel cell vehicle.

[0018]

[13] A step of performing a dehydrogenation reaction of a liquid organic hydrogen storage raw material in a dehydrogenation reactor in the presence of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas; cooling and separating the dehydrogenation reaction product in a cooling separation unit to obtain a hydrogen-rich stream and an organic liquid; contacting the hydrogen-rich stream or the purified hydrogen-rich stream with a hydrogen-absorbing alloy in a hydrogen-absorbing alloy containment vessel to obtain a hydrogen-containing alloy; A step of removing organic matter from within a hydrogen storage alloy containment vessel by a purging method using hydrogen gas, preferably with a hydrogen gas for purging having a purity of more than 90% by weight (e.g., more than 95% by weight, more than 99% by weight); a step of heating the hydrogen-containing alloy to release hydrogen gas, thereby obtaining high-pressure hydrogen gas, and supplying the obtained high-pressure hydrogen gas to a hydrogen consumption device or a high-pressure hydrogen gas storage tank for storage; A highly efficient distributed method for producing high-purity high-pressure hydrogen gas, comprising:

[0019]

[14] A high-purity high-pressure hydrogen gas supply system, a liquid organic hydrogen storage raw material storage-supply device for storing the liquid organic hydrogen storage raw material and supplying the liquid organic hydrogen storage raw material to the dehydrogenation reactor; a dehydrogenation liquid storage device for storing a liquid product obtained by dehydrogenating the liquid organic hydrogen storage raw material; a dehydrogenation reactor device for performing a dehydrogenation reaction of a liquid organic hydrogen storage raw material under the action of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas; a cooling and separating unit for separating the dehydrogenation reaction product to obtain a hydrogen-rich gaseous product and a liquid product; a hydrogen storage / hydrogen supply device that includes a hydrogen storage alloy storage vessel and a hydrogen storage alloy heating system, and that absorbs hydrogen by contacting a hydrogen-rich gas with the hydrogen storage alloy at low temperature and pressure and then dehydrogenating the hydrogen by heating after the hydrogen absorption is saturated; Optionally, a purge device used to remove organic matter from within the hydrogen storage container; A hydrogen gas supply device that supplies high-pressure hydrogen gas to a hydrogen consumption device or a hydrogen gas storage tank, Preferably, the system is installed in a hydrogen refueling station as a container-type hydrogen production system integrated into the interior of a container, or is directly incorporated in the hydrogen refueling station for use; Preferably, the hydrogen storage-hydrogen supply device includes one or more hydrogen storage alloy storage vessels, and the multiple hydrogen storage alloy storage vessels can be connected in parallel, in series, or in a combined parallel and series configuration; Preferably, the high-purity high-pressure hydrogen gas supply system has at least one hydrogen storage alloy storage vessel that is a high-pressure resistant vessel, and / or the hydrogen gas supply device that is a high-pressure resistant device, for example, a device with an allowable pressure of 35 MPa or more.

[0020]

[15] A mobile hydrogen supply system comprising a transport vehicle and a high-purity, high-pressure hydrogen gas supply system described in any one of the above-mentioned technical configurations installed on the transport vehicle.

[0021]

[16] A distributed hydrogen supply device comprising a high-purity high-pressure hydrogen supply system according to any one of the above-mentioned technical configurations, and optionally comprising a high-pressure hydrogen gas storage tank.

[0022]

[17] A hydrogen storage alloy, or a method, system, or device according to any one of the above-mentioned technical configurations, The hydrogen storage alloy is one or more of rare earth-based AB5 type, zirconium-titanium-based AB2 type, titanium-based AB type, magnesium-based A2B type, and vanadium-based solid solution type hydrogen storage alloys; The molecular formula for rare earth AB5 type hydrogen storage alloy is M m Ni x1 Co x2 Mn x3 Fe x4 Al x5 Sn x6 (4.5≦x1+x2+x3+x4+x5+x6≦5.5; M m La y1 Ce y2 Nd y3 Pr y4 Y y5 And;y1+y2+y3+y4+y5=1; 0.4≦y1≦0.99 (for example, 0.4≦y1≦0.8), 0≦y2≦0.45 (for example, 0.1≦y2≦0.45), 0≦y3≦0.2 (for example, 0≦y3≦0.2), 0≦y4≦0.05 (for example, 0≦y4≦0.05), 0.01≦y5≦0.1 (for example, 0.01≦y5≦0.05), 3≦x1≦5.45 (e.g., 3≦x1≦4.9), 0≦x2≦1.5 (e.g., 0.1≦x2≦1), 0≦x3≦0.8 (e.g., 0.1≦x3≦0.6), 0≦x4≦0.8 (e.g., 0.1≦x4≦0.6), 0≦x5≦0.75 (e.g., 0.05≦x5≦0.5), 0≦x6≦0.2 (e.g., 0≦x6≦0.15)). The molecular formula for the zirconium-titanium AB2 type hydrogen storage alloy is AB2 (A=Mg x1 Ca x2 Ti x3 Zr x4 Y x5 La x6 ;x1+x2+x3+x4+x5+x6=0.9~1.1; B=V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7 ;y1+y2+y3+y4+y5+y6+y7=1.9~2.1; 0≦x1≦0.54 (e.g. 0.01≦x1≦0.3, 0.01≦x1≦0.1), 0≦x2≦0.54 (e.g. 0≦x2≦0.25), 0.5≦x3≦1.04 (e.g. 0.6≦x3≦1), 0.05≦x4≦0.58 (e.g. 0.1≦x4≦0.58), 0.01≦x5≦0.2 (e.g. 0.01≦x5≦0.05), 0≦x6≦0.2 (e.g. 0≦x6≦0.05), 0.0 5≦y1≦1.95 (for example, 0.05≦y1≦1.8), 0≦y2≦1.9 (for example, 0≦y2≦1.85), 0.05≦y3≦1.95 (for example, 0.1≦y3≦1.95), 0≦y4≦1.6 (for example, 0≦y4≦1.5), 0≦y5≦0.5 (for example, 0≦y5≦0.3), 0.1≦y6≦0.5 (for example, 0.1≦y6≦0.3), 0≦y7≦0.5 (for example, 0.1≦y7≦0.2); Preferably, 0.7≦x3:(x3+x4)≦0.95; Preferably, 1.7≦y1+y2+y3+y4≦2), The molecular formula for titanium-based AB type hydrogen storage alloy is AB (A=Ti x1 Zr x2 Y x3 La x4 ;x1+x2+x3+x4=0.85~1.1; B=V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7 ;y1+y2+y3+y4+y5+y6+y7=0.95~1.05; 0≦x1≦1.09 (for example, 0.9≦x1≦1.05), 0≦x2≦1.09 (for example, 0≦x2≦0.5), 0.01≦x3≦0.2 (for example, 0.01≦x3≦0.05), 0≦x4≦0.2 (for example, 0≦x4≦0.05), 0.05≦y1≦0.5 (for example, 0.05≦y1≦0.2), 0≦y2≦0.8 (for example, for example, 0≦y2≦0.2), 0≦y3≦0.8 (for example, 0.05≦y3≦0.4, or 0.1≦y3≦0.4), 0.2≦y4≦1 (for example, 0.5≦y4≦0.9), 0≦y5≦0.35 (for example, 0≦y5≦0.1), 0≦y6≦0.45 (for example, 0≦y6≦0.2), 0≦y7≦0.3 (for example, 0≦y7≦0.2); It is preferable that x1 and x2 do not simultaneously take 0. The molecular formula for magnesium-based A2B type hydrogen storage alloy is A2B (A=Mg x1 Ca x2 Ti x3 La x4 Y x5 ;x1+x2+x3+x4+x5=1.9~2.1; B=Cr y1 Fe y2 Co y3 Ni y4 Cu y5 Mo y6 ;y1+y2+y3+y4+y5+y6=0.9~1.1; 1.29≦x1≦2.09 (for example, 1.7≦x1≦2.05), 0≦x2≦0.5 (for example, 0≦x2≦0.2), 0≦x3≦0.8 (for example, 0≦x3≦0.5), 0≦x4≦0.5 (for example, 0≦x4≦0.2), 0.01≦x5≦0.2 (for example, 0.05≦x5≦0.1), 0≦y1≦0.3 (for example, 0≦y 1≦0.2, 0.05≦y1≦0.2), 0≦y2≦0.2 (for example, 0≦y2≦0.1), 0≦y3≦0.6 (for example, 0≦y3≦0.5), 0.2≦y4≦1.1 (for example, 0.7≦y4≦1.05), 0≦y5≦0.5 (for example, 0≦y5≦0.4), 0≦y6≦0.15 (for example, 0≦y6≦0.1) The molecular formula for vanadium-based solid solution hydrogen storage alloy is A x1 B x2 (x1+x2=1; A=Ti y1 V y2 Zr y3 Nb y4 Y y5 La y6 Ca y7 ;y1+y2+y3+y4+y5+y6+y7=1; B=Mn z1 Fe z2 Co z3 Ni z4 ;z1+z2+z3+z4=1; 0.7≦x1≦0.95 (e.g. 0.8≦x1≦0.95, 0.9≦x1≦0.95), 0.05≦x2≦0.3 (e.g. 0.05≦x2≦0.2, 0.05≦x2≦0.1), 0.40≦y1≦0.9 (e.g. 0.45≦y1≦0.9, 0.5≦y1≦0.8), 0≦y2≦0.5 (e.g. 0≦y2≦0.4), 0≦y3≦0.5 (e.g. 0≦y3≦0.4), 0≦y4≦0.55 (e.g. 0≦y4≦0.4), 0≦y5≦0.2 (e.g. 0.01≦y5≦0.2, 0.05≦y5≦0.2 ), 0≦y6≦0.1 (e.g., 0≦y6≦0.05), 0≦y7≦0.1 (e.g., 0≦y7≦0.05), 0≦z1≦1 (e.g., 0.1≦z1≦1, 0.2≦z1≦0.95), 0≦z2≦0.95 (e.g., 0≦z2≦0.9), 0≦z3≦0.3 (e.g., 0≦z3≦0.2), 0≦z4≦0.45 (e.g., 0.05≦z4≦0.45, 0.05≦z4≦0.3), 0.55≦z1+z2≦1 (e.g., 0.7≦z1+z2≦1)).

[0023]

[18] Hydrogen storage alloys include La 0.61 Ce 0.16 Pr 0.04 Nd 0.19 Ni 3.55 Co 0.75 Mn 0.4 Al 0.3 , (Ti 0.8 V 0.2 ) 0.95 (Fe1) 0.05 , (Ti 0.8 Y 0.2 ) 0.95 (M 0.95 Ni 0.05 ) 0.05 , (Ti 0.4 V 0.4 Y 0.2 ) 0.9 (Fe 0.05 Mn 0.95 ) 0.1 , (Ti 0.4 V 0.4 Y 0.2 ) 0.9 (Fe 0.05 Mn 0.9 Ni 0.05 ) 0.1 , (Ti0.7 Nb 0.1 Y 0.2 ) 0.9 (Mn1) 0.1 、(You 0.7 Nb 0.1 Y 0.2 ) 0.9 (Mn 0.7 It’s 0.3 ) 0.1 、(You 0.4 Zr 0.4 Y 0.2 ) 0.93 (Fe 0.2 Mn 0.7 Co 0.1 ) 0.07 、(You 0.4 Zr 0.4 Y 0.2 ) 0.93 (Fe 0.2 Mn 0.7 It’s 0.1 ) 0.07 、(You 0.4 V 0.4 Zr 0.2 ) 0.95 (Fe 0.6 Mn 0.2 Co 0.1 It’s 0.1 ) 0.05 、(You 0.4 V 0.35 Zr 0.2 Y 0.05 ) 0.95 (Fe 0.6 Mn 0.2 Co 0.1 It’s 0.1 ) 0.05 、(You 0.88 Y 0.1 Ca 0.02 ) 0.95 (Fe 0.3 Mn 0.6 Co 0.1 ) 0.05 、(You 0.88 Y 0.1 Ca 0.02 ) 0.95 (Fe 0.3 Mn 0.6 It’s 0.1 ) 0.05 、(You 0.7 Nb 0.1 Y 0.2 ) 0.8(Mn 0.7 It’s 0.3 ) 0.2 、You 0.64 Zr 0.45 Y 0.01 VMn 0.9 It’s 0.1 、Mg 0.01 You 0.93 Zr 0.15 Y 0.01 VMn 0.9 It’s 0.1 、You 0.55 Zr 0.48 Y 0.05 The 0.02 V 0.33 Cr 0.05 Mn 1.5 Fe 0.09 It’s 0.1 、You 0.85 Zr 0.18 Y 0.05 The 0.02 V 0.23 Cr 0.05 Mn 1.5 Fe 0.09 It’s 0.1 Cu 0.1 、You 0.6 Zr 0.4 Y 0.05 V 0.1 Mn 1.8 It’s 0.2 、Mg 0.1 You 0.7 Zr 0.2 Y 0.05 V 0.1 Mn 1.6 It’s 0.2 Cu 0.2 、Ca 0.01 You 0.9 Zr 0.05 Y 0.05 V 1.2 Mn 0.6 It’s 0.3 、Ca 0.01 You 0.85 Zr 0.05 Y 0.05 V 1.2 Mn 0.6 It’s 0.1 Cu 0.2 、TiZr 0.05 Y 0.05 V 0.1 Cr 1.4 Mn 0.2Co 0.1 It’s 0.3 、Mg 0.1 You 0.8 Zr 0.15 Y 0.05 V 0.1 Cr 1.4 Mn 0.2 Co 0.1 It’s 0.1 Cu 0.2 、You 0.5 Zr 0.55 Y 0.05 V 1.79 Mn 0.1 Fe 0.01 It’s 0.2 、You 0.8 Zr 0.25 Y 0.05 V 1.79 Mn 0.1 Fe 0.01 It’s 0.1 Cu 0.1 、Mg 0.01 You 0.63 Zr 0.45 Y 0.01 VMn 0.9 It’s 0.1 、Mg 1.8 Y 0.1 Ni1、Mg 1.8 Y 0.1 Cr 0.05 Ni1、Mg 1.5 You 0.5 Y 0.05 It’s 1.1 、Mg 1.5 You 0.5 Y 0.05 Cr 0.1 Ni1、Mg2Y 0.1 It’s 0.6 Cu 0.4 、Mg2Y 0.1 Cr 0.05 It’s 0.6 Cu 0.4 、Mg 1.92 Y 0.08 It’s 0.95 Fe 0.05 、Mg 1.92 Y 0.08 Cr 0.2 It’s 0.75 Fe 0.05 、Mg 1.9 Y 0.1 Fe 0.1 It’s 0.8Cu 0.1 、Mg 1.9 Y 0.1 Cr 0.1 Feb 0.1 Ni 0.7 Cu 0.1 、Mg 1.9 Y 0.1 Ni 0.8 Co 0.2 、Mg 1.9 Y 0.1 Cr 0.1 Ni 0.8 Co 0.2 、Mg 1.8 Y 0.1 Day 0.1 Ni 0.9 Co 0.1 、Mg 1.8 Y 0.1 Day 0.1 Cr 0.05 Ni 0.9 Co 0.1 、Mg 1.7 Tea 0.2 Y 0.1 Ni 0.7 Co 0.32 、Mg 1.7 Tea 0.2 Y 0.1 Cr 0.05 Ni 0.7 Co 0.3 、TiY 0.01 V 0.1 Feb 0.7 Ni 0.2 、TiY 0.01 V 0.1 Feb 0.7 Mr 0.1 Ni 0.1 、TiY 0.02 V 0.2 Feb 0.8、 TiY 0.02 V 0.2 Feb 0.7 Mr 0.1 、Tea 0.97 Y 0.03 V 0.05 Cr 0.03 Feb 0.9 、Tea 0.97 Y 0.03 V 0.05 Cr 0.03 Feb 0.5 Mr 0.4 、Tea 0.9 Y0.04 V 0.15 Faith 0.9 ,You 0.9 AND 0.04 V 0.05 Faith 0.9 Mn 0.1 ,You 0.91 Zr 0.05 AND 0.04 V 0.1 Cr 0.2 Faith 0.7 ,You 0.91 Zr 0.05 AND 0.04 V 0.1 Cr 0.2 Faith 0.6 Mn 0.1 ,You 0.95 AND 0.05 V 0.26 Faith 0.7 Cu 0.05 ,You 0.95 AND 0.05 V 0.05 Faith 0.7 Mn 0.21 Cu 0.05 ,You 1.02 AND 0.03 V 0.05 Faith 0.9 Neither 0.1 ,You 1.02 AND 0.03 V 0.05 Faith 0.8 Mn 0.1 Neither 0.1 ,The 0.5 EC 0.32 Nd 0.15 Pr 0.02 AND 0.01 Neither 4.4 Faith 0.55 To the 0.05 ,The 0.5 EC 0.32 Nd 0.15 Pr 0.02 AND 0.01 Neither 4.4 Faith 0.6 ,The 0.8 EC 0.15 AND 0.05 Ni4Mn 0.5 To the 0.5 ,The 0.8 EC 0.15 AND 0.05 Neither 4.5 Mn0.5 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni4Co 0.8 Al 0.2 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4.2 Co 0.8 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.7 Al 0.1 Fe 0.2 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.8 Fe 0.2 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.3 Mn 0.1 Al 0.1 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.4 Mn 0.1 , La 0.97 Y 0.03 The hydrogen storage alloy, method, system or device according to any one of the above technical configurations, wherein the alloy is selected from Ni4Co1.

[0024]

[19] Hydrogen storage alloys are (Ti 0.8 Y 0.2 ) 0.95 (M 0.95 Ni 0.05 ) 0.05 , (Ti 0.4 V 0.4 Y 0.2 ) 0.9 (Fe 0.05 Mn 0.9 Ni 0.05) 0.1 、(You 0.7 Nb 0.1 Y 0.2 ) 0.9 (Mn 0.7 It’s 0.3 ) 0.1 、(You 0.4 Zr 0.4 Y 0.2 ) 0.93 (Fe 0.2 Mn 0.7 It’s 0.1 ) 0.07 、(You 0.4 V 0.35 Zr 0.2 Y 0.05 ) 0.95 (Fe 0.6 Mn 0.2 Co 0.1 It’s 0.1 ) 0.05 、(You 0.88 Y 0.1 Ca 0.02 ) 0.95 (Fe 0.3 Mn 0.6 It’s 0.1 ) 0.05 、Mg 0.01 You 0.93 Zr 0.15 Y 0.01 VMn 0.9 It’s 0.1 、You 0.85 Zr 0.18 Y 0.05 The 0.02 V 0.23 Cr 0.05 Mn 1.5 Fe 0.09 It’s 0.1 Cu 0.1 、Mg 0.1 You 0.7 Zr 0.2 Y 0.05 V 0.1 Mn 1.6 It’s 0.2 Cu 0.2 、Ca 0.01 You 0.85 Zr 0.05 Y 0.05 V 1.2 Mn 0.6 It’s 0.1 Cu 0.2 、Mg 0.1Tea 0.8 Zr 0.15 Y 0.05 V 0.1 Cr 1.4 Mr 0.2 Co 0.1 Ni 0.1 Cu 0.2 、Tea 0.8 Zr 0.25 Y 0.05 V 1.79 Mr 0.1 Feb 0.01 Ni 0.1 Cu 0.1 、Mg 1.8 Y 0.1 Cr 0.05 Ni1、Mg 1.5 Tea 0.5 Y 0.05 Cr 0.1 Ni1、Mg2Y 0.1 Cr 0.05 Ni 0.6 Cu 0.4 、Mg 1.92 Y 0.08 Cr 0.2 Ni 0.75 Feb 0.05 、Mg 1.9 Y 0.1 Cr 0.1 Feb 0.1 Ni 0.7 Cu 0.1 、Mg 1.9 Y 0.1 Cr 0.1 Ni 0.8 Co 0.2 、Mg 1.8 Y 0.1 Day 0.1 Cr 0.05 Ni 0.9 Co 0.1 、Mg 1.7 Tea 0.2 Y 0.1 Cr 0.05 Ni 0.7 Co 0.3 、TiY 0.01 V 0.1 Feb 0.7 Mr 0.1 Ni 0.1 、TiY 0.02 V 0.2 Feb 0.7 Mr 0.1 、Tea 0.97 Y<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Cr<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.4 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 0.9 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.04 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.9 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 0.91 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.04 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Cr<h2 style=";text-align:left;direction:ltr"> 0.2 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.6 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 0.95 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.7 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.21 <h2 style=";text-align:left;direction:ltr"> Cu<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 1.02 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.8 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> No<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Ce<h2 style=";text-align:left;direction:ltr"> 0.32 <h2 style=";text-align:left;direction:ltr"> Nd<h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Pr<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.01 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 4.4 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.55 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> No<h2 style=";text-align:left;direction:ltr"> 0.8 <h2 style=";text-align:left;direction:ltr"> Ce<h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Ni4Mn<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> No<h2 style=";text-align:left;direction:ltr"> 0.45 <h2 style=";text-align:left;direction:ltr"> Ce<h2 style=";text-align:left;direction:ltr"> 0.4 <h2 style=";text-align:left;direction:ltr"> Nd<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Pr<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Ni4Co<h2 style=";text-align:left;direction:ltr"> 0.8 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.2 <h2 style=";text-align:left;direction:ltr"> No<h2 style=";text-align:left;direction:ltr"> 0.75 <h2 style=";text-align:left;direction:ltr"> Ce<h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Nd<h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> Pr<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 4.7 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 0.2 <h2 style=";text-align:left;direction:ltr"> No<h2 style=";text-align:left;direction:ltr"> 0.8 <h2 style=";text-align:left;direction:ltr"> Ce<h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Nd<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 0.02 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 4.5 <h2 style=";text-align:left;direction:ltr"> Co<h2 style=";text-align:left;direction:ltr"> 0.3 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.1The hydrogen storage alloy, method, system, or device according to any one of the above technical configurations, selected from the above.

[0025]

[20] A hydrogen storage alloy is prepared by the following method: The method comprises the steps of: A step (1) of weighing each of the raw materials of the hydrogen storage alloy so as to obtain a composition of the hydrogen storage alloy, and mixing the raw materials; and (2) melting the mixture obtained in step (1) and then annealing the mixture, The melting is performed by an electric furnace or induction heating. Preferably, the melting conditions include a temperature of 1200 to 3000°C, preferably 1800 to 2200°C, under vacuum or inert atmosphere; More preferably, under vacuum, 1×10 -5 ~1×10 -3 Pa (absolute pressure), preferably 0.5 x 10 -4 ~5×10 -4 It melts at a pressure of Pa (absolute pressure), More preferably, the melting is carried out under an inert atmosphere at a pressure of 0.5 to 1 bar (e.g., 0.6 to 1 bar, 0.7 to 1 bar) (gauge pressure), The annealing conditions include a vacuum or an inert atmosphere (e.g., an argon atmosphere), a temperature of 500 to 900°C (e.g., 700 to 1000°C), and a time of 12 to 360 hours. Optionally, the method further comprises a step of crushing the material obtained by the annealing in step (2) after cooling to obtain a product of 10 to 400 mesh (e.g., 20 to 400 mesh); Optionally, the method further comprises a step of subjecting the material obtained by the annealing in step (2) to an activation treatment, and preferably the activation treatment conditions include a temperature of 50 to 300°C under vacuum and a time of 1 to 10 hours. The hydrogen storage alloy, method, system or apparatus according to any one of the technical configurations described above.

[0026]

[21] A support composition for an organic dehydrogenation catalyst, comprising: The support composition comprises alumina and a modifying metal oxide, the modifying metal oxide is titanium oxide and / or zirconium oxide; η<0.3, preferably η=0, θ≧5, preferably θ is 5 to 40 (e.g., 5.4 to 34.3) (η=wt% content of the crystalline phase of the modified metal oxide in the support composition / wt% content of the chemical composition of the modified metal oxide in the support composition; θ=wt% content of modified metal oxide at the surface of the support composition / wt% content of modified metal oxide chemical composition in the support composition; Titanium oxide is calculated as TiO2 and zirconium oxide is calculated as ZrO2), a support composition for an organic dehydrogenation catalyst.

[0027]

[22] A support composition for an organic dehydrogenation catalyst according to any one of the above-mentioned technical configurations, wherein the mass fraction of alumina in the support composition is 80 to 98.5% (e.g., 83 to 97.5%, 85 to 95%, or 90 to 95%) and the mass fraction of the modifying metal oxide is 1.5 to 20% (e.g., 2.5 to 17%, 5 to 15%, or 5 to 10%).

[0028]

[23] A support composition for a dehydrogenation catalyst of an organic substance according to any one of the above-mentioned technical configurations, wherein the modifying metal oxide comprises titanium oxide, and in the support composition, the mass fraction of titanium dioxide is 2 to 20% (e.g., 2.5 to 17%, 5 to 15%, or 5 to 10%) and the mass fraction of zirconium dioxide is 0 to 8% (e.g., 0 to 6%, 0 to 3%, or 1 to 6%), and preferably the modifying metal oxide (e.g., titanium dioxide) is dispersed as a monolayer on an alumina substrate.

[0029]

[24] In comparison with the pure phase of TiO2, the XPS spectra of the support composition show that the Ti 2P 3 / 2 The peak at 458.8 eV of the orbital electron binding energy shifts to the high binding energy side by 0.6 to 0.7 eV, and / or the Ti 2P 1 / 2A carrier composition for an organic dehydrogenation catalyst according to any one of the above-mentioned technical configurations, in which the peak of orbital electron binding energy at 464.5 eV is shifted by 0.8 to 0.9 eV to the high binding energy side.

[0030]

[25] A support composition for an organic dehydrogenation catalyst according to any one of the above-mentioned technical configurations, wherein the support composition has at least one phase structure of γ-alumina, η-alumina, ρ-alumina or χ-alumina.

[0031]

[26] The specific surface area of ​​the carrier composition is 100 to 350 m 2 / g, and the pore volume of the support composition is 0.3 to 1.3 mL / g.

[0032]

[27] A method for preparing a support composition for a dehydrogenation catalyst of an organic substance according to any one of the above technical configurations, comprising: (1) contacting an alumina substrate with a gas stream of modified metal oxide precursors carried by a gas to obtain an alumina substrate carrying titanium oxide precursors and / or zirconium oxide precursors as modified metal oxide precursors; and (2) hydrolyzing and calcining the alumina substrate carrying the modified metal oxide precursor to obtain a support composition.

[0033]

[28] The titanium oxide precursor is selected from titanium tetrachloride, (tetra)ethyl titanate, tetrabutyl titanate, (tetra)isopropyl titanate, titanium acetate, and mixtures thereof (preferably titanium tetrachloride), and the zirconium oxide precursor is selected from zirconium tetrachloride, zirconium ethoxide, zirconium methoxide, zirconium isopropoxide, tetrabutyl zirconate, and mixtures thereof (preferably zirconium tetrachloride and / or zirconium methoxide), a method for preparing a carrier composition according to any one of the above technical configurations.

[0034]

[29] The method for preparing a carrier composition according to any one of the above technical configurations, wherein the alumina substrate is selected from the group consisting of γ-alumina, η-alumina, ρ-alumina, χ-alumina, hydrated alumina, and mixtures thereof.

[0035]

[30] The specific surface area of ​​the alumina substrate is 100-350 m 2 / g, and preferably the ratio of the specific surface area of ​​the support composition to the specific surface area of ​​the alumina substrate is 90% or more.

[0036]

[31] A method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein the alumina substrate has a pore volume of 0.3 to 1.3 mL / g.

[0037]

[32] The gas is an anhydrous inert gas (e.g., nitrogen gas, helium gas, neon gas, argon gas), and the water content in the anhydrous inert gas is 10 ppm or less; Preferably, the content of modified metal oxide precursor (calculated as metal oxide) in the gas stream of modified metal oxide precursor carried by the gas is between 0.1 and 3 g / L (e.g. between 0.2 and 2 g / L), in the method for preparing a carrier composition according to any one of the above technical configurations.

[0038]

[33] A method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein in step (1), the temperature of the gas is room temperature to 350°C (e.g., room temperature (room temperature means 15 to 40°C) to 300°C, or 15 to 300°C).

[0039]

[34] The method for preparing a carrier composition according to any one of the above technical configurations, wherein in step (1), the pressure during contact is 0.05 to 5 atm (for example, 1 to 3 atm) (gauge pressure).

[0040]

[35] A method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein the ratio of the volumetric flow rate of the gas per minute to the volume of the alumina substrate is 3 to 80:1 (e.g., 5 to 30:1, 10 to 25:1), the volume of the gas is calculated as the volume under standard conditions, and the volume of the alumina substrate is calculated as the bulk volume.

[0041]

[36] The method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein when the alumina substrate is contacted with the gas stream of modified metal oxide precursor carried by the gas, the alumina substrate is under fluidized conditions or under stirring, and the fluidized conditions can be, for example, a bubbling bed, a turbulent bed, a high velocity bed or a conveying bed.

[0042]

[37] A method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein in step (2), the hydrolysis of the alumina substrate carrying the modified metal oxide precursor is carried out by contacting the alumina substrate carrying the modified metal oxide precursor with a water vapor-containing gas.

[0043]

[38] The method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein the hydrolysis in step (2) is performed such that the ratio of the water vapor-containing gas to the alumina substrate with which the water vapor-containing gas comes into contact (the ratio of the volume of the water vapor-containing gas to the bulk volume of the alumina substrate under standard conditions) is 3 to 80:1 (e.g., 5 to 30:1, or 10 to 25:1), the proportion of water vapor in the water vapor-containing gas to the total gas volume is 0.1 volume % to 100 volume % (e.g., 3 volume % to 100 volume %), and gases other than water vapor in the water vapor-containing gas may be an inert gas, nitrogen gas, or air.

[0044]

[39] The method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein the hydrolysis time in the step (2) is 1 hour to 50 hours, for example, 2 hours to 30 hours.

[0045]

[40] The method for preparing a carrier composition according to any one of the above-mentioned technical configurations, wherein the calcination is performed at a calcination temperature of 350°C to 700°C for a calcination time of 0.5 to 12 hours (the calcination atmosphere may be an oxygen gas-free atmosphere or an oxygen gas-containing atmosphere, and in one embodiment, the oxygen gas content in the oxygen gas-containing atmosphere may be 3 to 100 volume %, for example, an air atmosphere or an oxygen gas atmosphere).

[0046]

[41] A catalyst for producing hydrogen gas by dehydrogenating organic matter, or a hydrogen storage alloy, method, system, or device described in any one of the above-mentioned technical configurations, wherein the catalyst comprises a support composition for a dehydrogenation catalyst of organic matter described in any one of the above-mentioned technical configurations and an active component.

[0047]

[42] A catalyst for producing hydrogen gas by dehydrogenating an organic substance according to any one of the above-mentioned technical configurations, or a hydrogen storage alloy, method, system, or device according to any one of the above-mentioned technical configurations, The active ingredient is any one of the following (1), (2), and (3): (1) at least one element of the precious metal group, preferably Pt, and optionally at least one element of the precious metal group other than Pt; (2) Pt and at least one element of the first metal group; (3) Ni, at least one element of the second metal group, and optionally phosphorus; The precious metal group is a group consisting of elements selected from Pt, Pd, Ru, Re, Rh, Ir and Os; the first metal group is the group consisting of elements selected from Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca; the second group of metals is the group consisting of elements selected from Zn, Sn, Cu, Fe, Ag, In, Re, Mo, Co, Ca and W; A catalyst, a hydrogen storage alloy, a method, a system or an apparatus, wherein the content of the carrier in the catalyst is 70 to 99.9% by weight, and the content of the active component is 0.1 to 30% by weight.

[0048]

[43] A catalyst for producing hydrogen gas by dehydrogenating an organic substance according to any one of the above-mentioned technical configurations, or a hydrogen storage alloy, method, system, or device according to any one of the above-mentioned technical configurations, the active component is at least one element selected from the group consisting of (1) precious metals, the content of the carrier in the catalyst is 90 to 99.9% by weight (e.g., 92 to 99.4% by weight, 92 to 99.5% by weight, 95 to 99.4% by weight, 98 to 99.2% by weight, or 98.5 to 99.5% by weight), and the content of the active component is 0.1 to 10% by weight (e.g., 0.6 to 8% by weight, 0.5 to 8% by weight, 0.6 to 5% by weight, 0.8 to 2% by weight, or 0.5 to 1.5% by weight); Preferably, the active components are Pt and, optionally, at least one element other than Pt from the group of precious metals, the content of Pt is 0.1 to 10 wt % (e.g., 0.1 to 2 wt %, 0.6 to 10 wt %, or 0.6 to 0.8 wt %), and the content of the at least one element other than Pt from the group of precious metals is 0 to 9.9 wt % (e.g., 0.1 to 2 wt % or 0.1 to 0.8 wt %).

[0049]

[44] A catalyst for producing hydrogen gas by dehydrogenating an organic substance according to any one of the above-mentioned technical configurations, or a hydrogen storage alloy, method, system, or device according to any one of the above-mentioned technical configurations, The active component is (2) Pt and at least one element of the first metal group; In the catalyst, the content of the carrier is 75 to 99.5 wt % (e.g., 75 to 99.4 wt %, 79.9 to 98.5 wt %), and the content of the active component is 0.5 to 25 wt % (e.g., 0.6 to 25 wt %, 1.5 to 20.1 wt %), Among the active components, the content of Pt (calculated as a simple substance) is 0.01 to 10 wt% (e.g., 0.2 to 8 wt%, 0.4 to 2 wt%, 0.3 to 0.6 wt%, or 0.1 to 0.7 wt%), and the content of at least one element (calculated as an oxide) of the first metal group is 0.5 to 20 wt% (e.g., 0.5 to 15 wt% or 1 to 10 wt%), Preferably, at least one element of the first metal group is Ni or a combination of Ni and at least one element of the first metal group other than Ni, and the mass ratio of Pt (calculated as a simple substance) to Ni (calculated as NiO) is (0.01:16) to (0.5:0.1). A catalyst, or a hydrogen storage alloy, a method, a system or an apparatus.

[0050]

[45] A catalyst for producing hydrogen gas by dehydrogenating an organic substance according to any one of the above-mentioned technical configurations, or a hydrogen storage alloy, method, system, or device according to any one of the above-mentioned technical configurations, the active component is (3) Ni, at least one element of the second metal group, and optionally phosphorus; In the catalyst, the content of the carrier is 70 to 95% by weight (e.g., 75 to 93% by weight, or 75 to 90% by weight), and the content of the active component (calculated as an oxide) is 5 to 30% by weight (e.g., 7 to 25% by weight); A catalyst, or a hydrogen storage alloy, method, system, or device, wherein the active components have a nickel (calculated as NiO) content of 0.5 to 25 weight % (e.g., 5 to 25 weight %, 6 to 20 weight %, or 6 to 11 weight %), a content of at least one element of a second metal group (calculated as an oxide) of 0 to 15 weight % (e.g., 0 to 10 weight %), and a phosphorus (calculated as P2O5) content of 0 to 15 weight %.

[0051]

[46] Steps (1) and (2) in the method for preparing a carrier composition according to any one of the above technical configurations; (1) contacting an alumina substrate with a gas stream of modified metal oxide precursors carried by a gas to obtain an alumina substrate carrying titanium oxide precursors and / or zirconium oxide precursors as modified metal oxide precursors; (2) hydrolyzing and calcining the alumina substrate carrying the modified metal oxide precursor to obtain a support composition, (3) impregnating the support composition with the solution of the active ingredient precursor to obtain a support impregnated with the active ingredient precursor; and (4) drying and calcining the carrier impregnated with the active ingredient precursor, Preferably, the active ingredient is any one of the following (1), (2) and (3): (1) at least one element of the precious metal group, preferably Pt, and optionally at least one element of the precious metal group other than Pt; (2) Pt and at least one element of the first metal group; (3) Ni, at least one element of the second metal group, and optionally phosphorus; The precious metal group is a group consisting of elements selected from Pt, Pd, Ru, Re, Rh, Ir and Os; the first metal group is a group consisting of elements selected from Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca; The second group of metals is a group consisting of elements selected from Zn, Sn, Cu, Fe, Ag, In, Re, Mo, Co, Ca and W.

[0052]

[47] The method for preparing a catalyst according to any one of the above-mentioned technical configurations, wherein the calcination in the step (4) is performed at a calcination temperature of 400 to 700° C. for a calcination time of 0.5 to 12 hours.

[0053]

[48] ​​The method for preparing a catalyst according to any one of the above technical configurations, wherein the active component precursor is a soluble salt of the active component (e.g., one or more of metal nitrates, metal acetates, metal chlorides, metal carbonates, metal acetate complexes, metal hydroxides, metal oxalate complexes, high-valent metal acids, high-valent metal acid salts, metal complexes, and ammonium salts).

[0054]

[49] A method for preparing a catalyst according to any one of the above-mentioned technical configurations, comprising placing a support impregnated with an active component precursor in an environment of less than -40°C for 1 to 24 hours, removing water adsorbed on the support by vacuum drying, and calcining the support to obtain a catalyst.

[0055] BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 shows an X-ray diffraction (XRD) spectrum of a support composition containing alumina and titanium oxide. In the figure, "1" shows the XRD spectrum of the support composition (alumina supporting titanium oxide) provided by the present invention, "2" shows the XRD spectrum of a support composition prepared by an impregnation method in which alumina supports Ti oxide, and "3" shows the XRD spectrum of a mixture obtained by mechanically mixing alumina and titanium dioxide. In the XRD curve, the peaks at 2θ=25.37°, 48.12°, 53.97°, and 55.1° are the diffraction peaks of TiO2 (anatase).

[0056] Figure 2 shows X-ray photoelectron spectroscopy (XPS) spectra. In the figure, 1 shows the XPS spectrum of pure TiO2, and the other curves show the XPS spectrum of support compositions (alumina supported titanium oxide) with different TiO2 contents prepared by the method of the present invention. M-2, M-4, M-7 and M-8 show the supports of Examples 2, 4, 7 and 8, respectively. In Figure 2, the support composition provided by the present invention has Ti 2P 3 / 2 The peak of the orbital electron binding energy (abbreviated as binding energy) at 458.8 eV shifts to the high binding energy side by 0.6 to 0.7 eV, and the Ti 2P 1 / 2The peak of the orbital electron binding energy at 464.5 eV shifts to the higher binding energy side by 0.8 to 0.9 eV, indicating the existence of an interaction between Ti and the alumina support.

[0057] 3 is a schematic diagram of the high-purity high-pressure hydrogen gas provided by the present invention, in which 1 indicates an organic liquid storage tank, 2 indicates a raw material pump, 3 indicates a heat exchanger, 4 indicates a dehydrogenation reactor, 5 indicates a heat exchanger, 6 indicates a hydrogen storage tank, 7 indicates a one-way valve, 8 indicates an energy transmission system, 9 indicates a purge system, and 10 indicates a hydrogen storage control system.

[0058] Detailed Description of the Invention The pressure referred to in the present invention refers to gauge pressure unless otherwise specified.

[0059] In one aspect, the present invention provides a support composition for a catalyst for dehydrogenation of organic matter, the support composition comprising alumina and a modifying metal oxide, the modifying metal oxide being titanium oxide and / or zirconium oxide, η<0.3, preferably η=0; θ≧5, preferably θ is 5-40 (e.g. 5.4-34.3), where η=wt. % content of crystalline phase of the modifying metal oxide in the support composition / wt. % content of chemical composition of the modifying metal oxide in the support composition; θ=wt. % content of the modifying metal oxide at the surface of the support composition / wt. % content of chemical composition of the modifying metal oxide in the support composition; titanium oxide is calculated as TiO2 and zirconium oxide is calculated as ZrO2.

[0060] Preferably, some or all of the alumina and the modifying metal oxide form the support composition, hi one embodiment, the modifying metal oxide is supported on the surface of the support.

[0061] According to the carrier composition of the present invention, in the carrier composition, the mass fraction of alumina is 80-98.5% (e.g., 83-97.5%, 85-95%, or 90-95%), and the mass fraction of the modifying metal oxide is 1.5-20% (e.g., 2.5-17%, 5-15%, or 5-10%).

[0062] According to the support composition of the present invention, the modified metal oxide comprises titanium oxide, and in the support composition, the mass fraction of titanium dioxide is 2-20% (e.g., 2.5-17%, 5-15% or 5-10%) and the mass fraction of zirconium dioxide is 0-8% (e.g., 0-6%, 0-3% or 1-6%), and preferably, the modified metal oxide (e.g., titanium dioxide) is dispersed as a monolayer on the alumina substrate.

[0063] According to one embodiment of the present invention, when measured by XPS, if the content of the modifying metal oxide in a surface layer having a thickness of 0 to 5 nm from the surface of the support is greater than 90, preferably greater than 95, the modifying metal oxide is said to be dispersed as a monolayer on the alumina substrate.

[0064] According to the support composition of the present invention, in the XPS spectrum of the support composition, compared with the pure phase of TiO2, the 2P 3 / 2 The peak at 458.8 eV of the orbital electron binding energy shifts to the high binding energy side by 0.6 to 0.7 eV, and / or the Ti 2P 1 / 2 The peak of the orbital electron binding energy at 464.5 eV shifts to the higher binding energy side by 0.8 to 0.9 eV.

[0065] According to the support composition of the present invention, the support composition has at least one phase structure of γ-alumina, η-alumina, ρ-alumina or χ-alumina.

[0066] According to the carrier composition of the present invention, the specific surface area of ​​the carrier composition is 100 to 350 m 2 / g (e.g. 110~340m 2 / g or 130~250m 2 / g or 140~200m 2 / g), and the pore volume of the carrier composition is 0.3 to 1.3 mL / g (e.g., 0.32 to 1.0 mL / g, or 0.35 to 0.6 mL / g, or 0.35 to 0.8 mL / g). The ratio of the specific surface area of ​​the carrier composition to the specific surface area of ​​the alumina substrate is 90% or more, that is, the reduction rate of the specific surface area of ​​the carrier composition compared to the specific surface area of ​​pure alumina (alumina not modified by the introduction of a modifying element) is ≦10%.

[0067] The support composition provided by the present invention may be used to prepare a catalyst for dehydrogenating organics to produce hydrogen gas, or may be used as a catalyst for oxidative dehydrogenation of alkane organics to produce olefins or oxygen-containing organics. In general, the catalyst comprises the support composition provided by the present invention and an active metal component supported on the support composition, the active metal component being an oxide of the active metal and / or an elemental active metal. The active metal may be, for example, one or more of a Group VIIIB metal, a Group VIIB metal, a Group VB metal, a Group VIB metal, a Group IB metal, a rare earth element, an alkaline earth metal, or a Group IVA metal. This may result in a higher dehydrogenation activity and / or a higher selectivity than catalysts prepared using conventional supports and similar active metals.

[0068] The carrier composition provided by the present invention has a relatively low η value and a relatively high θ value, and therefore can be used as a carrier for a dehydrogenation catalyst, in particular, as a catalyst for producing hydrogen gas by dehydrogenating a liquid organic hydrogen storage compound containing a cycloalkane ring, and can improve the dehydrogenation activity and / or selectivity of the catalyst.

[0069] The preparation method of the carrier composition provided by the present invention can obtain the carrier composition provided by the present invention, and the obtained carrier composition has a relatively low η value and a relatively high θ value, and the preparation method is easy to carry out.

[0070] The dehydrogenation catalyst for producing hydrogen gas by dehydrogenating liquid organic hydrogen storage compounds prepared using the carrier composition provided by the present invention has higher activity and relatively high hydrogen gas selectivity, and the prepared oxidative dehydrogenation catalyst has high activity and higher oxidative selectivity.

[0071] The support provided by the present invention may be used in the preparation of a catalyst for dehydrogenating a hydrogen-storing organic compound to produce hydrogen gas, or may be used as a support in other hydrogen-related reaction catalysts or oxidation catalysts, such as organic oxidation dehydrogenation catalysts, unsaturated hydrocarbon hydrogenation catalysts, organic complete oxidation catalysts, or NO oxidation catalysts.

[0072] In one aspect, the present invention provides a method for preparing a support composition comprising the steps of: (1) contacting an alumina substrate with a gas stream of modified metal oxide precursors carried by a gas to obtain an alumina substrate supported with titanium oxide precursor and / or zirconium oxide precursor as modified metal oxide precursors; and (2) hydrolyzing and calcining the alumina substrate supported with the modified metal oxide precursor to obtain a support composition.

[0073] According to the method for preparing the support composition of the present invention, the modified metal oxide precursor is preferably a substance capable of vaporizing to form a metal oxide precursor gas at room temperature to 350° C. The titanium oxide precursor is one or more selected from titanium tetrachloride, (tetra)ethyl titanate, tetrabutyl titanate, (tetra)isopropyl titanate, and titanium acetate (preferably titanium tetrachloride), and the zirconium oxide precursor is one or more selected from zirconium tetrachloride, zirconium ethoxide, zirconium methoxide, zirconium isopropoxide, and tetrabutyl zirconate (preferably zirconium tetrachloride and / or zirconium methoxide).

[0074] According to the method for preparing the carrier composition of the present invention, the alumina substrate is selected from γ-alumina, η-alumina, ρ-alumina, χ-alumina, hydrated alumina (e.g., boehmite, diaspore, pseudoboehmite, gibbsite, bayerite, nordstrandite, amorphous aluminum hydroxide), and mixtures thereof, and preferably the average particle size (diameter) of the alumina substrate is 5 to 100 μm, for example 5 to 50 μm.

[0075] According to the preparation method of the carrier composition of the present invention, the specific surface area of ​​the alumina substrate is 100 m 2 / g or more (e.g. 100m 2 / g and 380m 2 / g or less, 100~350m 2 / g, 125-335m 2 / g), and preferably the ratio of the specific surface area of ​​the support composition to the specific surface area of ​​the alumina substrate is 90% or more, i.e. the percentage reduction in the specific surface area of ​​the resulting support composition compared to the specific surface area of ​​the alumina substrate is ≦10%.

[0076] According to the method for preparing the carrier composition of the present invention, the pore volume of the alumina substrate is 0.3 mL / g or more (for example, greater than 0.3 mL / g and less than 1.45 mL / g, 0.3 to 1.3 mL / g, 0.35 to 1.2 mL / g, 0.35 to 1.0, or 0.4 to 0.8 mL / g).

[0077] According to the method for preparing the carrier composition of the present invention, the gas is an anhydrous inert gas (e.g., nitrogen gas, helium gas, neon gas, argon gas), the water content in the anhydrous inert gas is 10 ppm or less, and preferably, the content of the modified metal oxide precursor (calculated as metal oxide) in the gas stream of the modified metal oxide precursor carried by the gas is 0.1-3 g / L (e.g., 0.2-2 g / L).

[0078] According to the method for preparing a carrier composition of the present invention, in step (1), the temperature of the gas is room temperature to 350°C (e.g., room temperature (room temperature means 15 to 40°C) to 300°C, or 15 to 300°C), and the temperature during contact is 15 to 350°C (e.g., 15 to 300°C, or 15 to 100°C, or 15 to 200°C, or 18 to 60°C, or 15 to 40°C).

[0079] According to the method for preparing a carrier composition of the present invention, in step (1), the pressure during contact is 0.05 to 5 atm (for example, 1 to 3 atm) (gauge pressure).

[0080] According to the method for preparing a carrier composition of the present invention, the ratio of the volumetric flow rate of the gas per minute to the volume of the alumina substrate is 3 to 80:1 (e.g., 5 to 30:1, 10 to 25:1), the volume of the gas is calculated as the volume under standard conditions, and the volume of the alumina substrate is calculated as the bulk volume.

[0081] According to the method for preparing the support composition of the present invention, when the alumina substrate is contacted with the gas stream of modified metal oxide precursor carried by the gas, the alumina substrate is under fluidized or agitated conditions, which can be, for example, a bubbling bed, a turbulent bed, a high velocity bed or a conveying bed.

[0082] In one embodiment, the alumina substrate is contacted with a gas stream of modified metal oxide precursors carried by a gas (also referred to as gas flow), and the alumina substrate may be contacted with the gas stream in a fixed bed, or may be contacted with the gas stream of modified metal oxide precursors carried by a gas under fluidized conditions, or may be contacted with the gas stream under stirring. Contacting under fluidized conditions may be, for example, in the form of a bubbling bed, turbulent bed, high velocity bed, or conveying bed. The ratio of the volumetric flow rate of the gas per minute to the volume of the alumina substrate is 3-80:1, for example 5-30:1, or 10-25:1, the volume of the gas being calculated as the volume under standard conditions, and the volume of the alumina substrate being calculated as the bulk volume. In another embodiment, the gas stream and the alumina substrate are contacted in a fluidized bed, and the volumetric space velocity of the contacting is 3-80:1 min -1 , for example 5 to 30: 1 minute-1 Or 10-25: 1 minute -1 where the volumetric flow rate of the gas stream is calculated as the volume of gas under standard conditions, the volume of the alumina substrate is calculated as the bulk volume, and the fluidized bed can be a bulk fluidized bed, a bubbling bed or a turbulent bed.

[0083] According to the method for preparing the support composition of the present invention, in step (2), the hydrolysis of the alumina substrate carrying the modified metal oxide precursor is carried out by contacting the alumina substrate carrying the modified metal oxide precursor with a water vapor-containing gas.

[0084] According to the method for preparing a carrier composition of the present invention, the hydrolysis in step (2) is carried out such that the ratio of the water vapor-containing gas to the alumina substrate with which the water vapor-containing gas comes into contact (the ratio of the volume of the water vapor-containing gas to the bulk volume of the alumina substrate under standard conditions) is 3 to 80:1 (e.g., 5 to 30:1, or 10 to 25:1), the proportion of water vapor in the water vapor-containing gas to the total gas volume is 0.1 volume % to 100 volume % (e.g., 3 volume % to 100 volume %, 10 volume % to 70 volume %), and the gas other than water vapor in the water vapor-containing gas can be an inert gas, nitrogen gas, or air.

[0085] According to the method for preparing the support composition of the present invention, the hydrolysis in step (2) has a hydrolysis time of 1 hour to 50 hours, for example, 2 hours to 30 hours (usually, the hydrolysis time is equal to or longer than the support time, which refers to the time during which the alumina substrate is in contact with the gas stream of the modified metal oxide precursor carried by the gas).

[0086] According to the preparation method of the carrier composition of the present invention, the firing atmosphere may be an atmosphere that does not contain oxygen gas or that contains oxygen gas. In one embodiment, the content of oxygen gas in the atmosphere that contains oxygen gas may be 3 to 100% by volume, for example, an air atmosphere or an oxygen gas atmosphere. The firing temperature is 350°C to 700°C (for example, 400 to 700°C), and the firing time is 0.5 to 12 hours (for example, 1 to 10 hours, or 2 to 9 hours, or 4 to 8 hours).

[0087] In one aspect of the present invention, the present invention provides a catalyst for producing hydrogen gas by dehydrogenating an organic compound, the catalyst comprising the support composition of the present invention for catalyzing the dehydrogenation of an organic compound, and an active component.

[0088] The active component contained in the catalyst provided by the present invention may be present in the form of an oxide and / or an active metal element.

[0089] According to the catalyst of the present invention for producing hydrogen gas by dehydrogenating organic matter, the active component is any one of the following (1), (2) and (3): (1) at least one element of the precious metal group, preferably Pt, and optionally at least one element of the precious metal group other than Pt; (2) Pt and at least one element of the first metal group; (3) Ni, at least one element of the second metal group, and optionally phosphorus, The precious metal group is a group consisting of elements selected from Pt, Pd, Ru, Re, Rh, Ir and Os; the first metal group is the group consisting of elements selected from Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca; the second group of metals is the group consisting of elements selected from Zn, Sn, Cu, Fe, Ag, In, Re, Mo, Co, Ca and W; In the catalyst, the content of the carrier is 70 to 99.9% by weight, and the content of the active component is 0.1 to 30% by weight.

[0090] According to the catalyst for producing hydrogen gas by dehydrogenating an organic substance of the present invention, the active component is (1) at least one element selected from the group consisting of precious metals, and the content of the carrier in the catalyst is 90 to 99.9% by weight (e.g., 92 to 99.4% by weight, 92 to 99.5% by weight, 95 to 99.4% by weight, 98 to 99.2% by weight, 98.5 to 99.5% by weight), and the content of the active component is 0.1 to 10% by weight (e.g., 0.6 to 8% by weight, 0.5 to 8% by weight, 0.6 to 5% by weight, 0.8 to 10% by weight, 0.9 to 10% by weight). %, 0.8 to 2 wt %, or 0.5 to 1.5 wt %, and preferably the active component is Pt and, optionally, at least one element other than Pt from the group of precious metals, the content of Pt is 0.1 to 10 wt % (e.g., 0.1 to 2 wt %, 0.6 to 10 wt %, or 0.6 to 0.8 wt %) and the content of the at least one element other than Pt from the group of precious metals is 0 to 9.9 wt % (e.g., 0.1 to 2 wt %, 0.1 to 0.8 wt %).

[0091] According to the catalyst of the present invention for producing hydrogen gas by dehydrogenating an organic substance, the active components are (2) Pt and at least one element of a first metal group (e.g., one or more of Sn, Ni, Mn, and Cu), the content of the carrier in the catalyst is 75 to 99.5% by weight (e.g., 75 to 99.4% by weight, 79.9 to 98.5% by weight), the content of the active components is 0.5 to 25% by weight (e.g., 0.6 to 25% by weight, 1.5 to 20.1% by weight), and the content of Pt (calculated as a simple substance) in the active components is 0.01 to 10% by weight (e.g., 0.2 to 8% by weight, 0.4 to 2% by weight). , 0.3-0.6 wt%, 0.1-0.7 wt%, the content of at least one element (calculated as oxide) in the first metal group is 0.5-20 wt% (e.g., 0.5-15 wt% or 1-10 wt%), preferably, at least one element in the first metal group is Ni or a combination of Ni and at least one element other than Ni in the first metal group (e.g., Sn, Mn and Cu, preferably Cu), and the mass ratio of Pt (calculated as simple substance) to Ni (calculated as NiO) is (0.01:16)-(0.5:0.1). Preferably, in the catalyst, the content of Pt is 0.1-0.5 wt%, the content of Ni (calculated as oxide) is 0.5-15 wt%, e.g., 1-10 wt%, and the content of elements other than Ni in the first metal group (calculated as oxide) is 0-10 wt%, e.g., 1-6 wt%. The active components are more preferably Pt, Ni and Cu.

[0092] According to the catalyst for producing hydrogen gas by dehydrogenating organic matter of the present invention, the active components are (3) Ni, at least one element of the second metal group (preferably Sn, Cu, Zn, Fe, Ag, more preferably Sn, Ag, Cu and Zn, even more preferably Sn, Zn and Cu, even more preferably Sn and Zn), and optionally phosphorus. According to this preferred embodiment, it has a high conversion rate and hydrogen gas production rate, and has a higher hydrogen gas selectivity than other active metals. In the catalyst, the content of the carrier is 70 to 95% by weight (e.g., 75 to 93% by weight, or 75 to 90% by weight), the content of the active component (calculated as oxide) is 5 to 30% by weight (e.g., 7 to 25% by weight, 10 to 25% by weight, 8 to 20% by weight, or 10 to 16% by weight), the content of nickel (calculated as NiO) among the active components is 0.5 to 25% by weight (e.g., 0.5 to 20% by weight, 5 to 25% by weight, 6 to 20% by weight, 5 to 15% by weight, 8 to 10% by weight, or 6 to 11% by weight), the content of at least one element (calculated as oxide) of the second metal group is 0 to 15% by weight (e.g., 0 to 10% by weight, 2 to 6% by weight), and the content of phosphorus (calculated as P2O5) is 0 to 15% by weight (e.g., 0 to 8% by weight, 0 to 6% by weight).

[0093] According to the catalyst of the present invention for producing hydrogen gas by dehydrogenating organic matter, the specific surface area of ​​the catalyst is 100 to 350 m 2 / g (e.g. 120~330m 2 / g) and the pore volume of the catalyst is 0.3 to 1.3 ml / g (for example, 0.35 to 1.2 ml / g).

[0094] In one aspect of the present invention, the present invention provides a method for preparing the catalyst of the present invention for dehydrogenating organic matter to produce hydrogen gas, comprising the steps of: (1) contacting an alumina substrate with a gas stream of modified metal oxide precursor carried by a gas to obtain an alumina substrate carrying titanium oxide precursor and / or zirconium oxide precursor as modified metal oxide precursor; (2) hydrolyzing and calcining the alumina substrate carrying the modified metal oxide precursor to obtain a support composition; (3) impregnating the support composition with a solution of an active component precursor to obtain a support impregnated with the active component precursor; and (4) drying and calcining the support impregnated with the active component precursor, wherein preferably the active component is any one of the following (1), (2) and (3): (2) Pt and at least one element from the first group of metals; (3) Ni, at least one element from the second group of metals, and optionally phosphorus, the group of precious metals being the group consisting of elements selected from Pt, Pd, Ru, Re, Rh, Ir, and Os, the first group of metals being the group consisting of elements selected from Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca, and the second group of metals being the group consisting of elements selected from Zn, Sn, Cu, Fe, Ag, In, Re, Mo, Co, Ca, and W.

[0095] According to the preparation method of the present invention for a catalyst for producing hydrogen gas by dehydrogenating an organic substance, the calcination in step (4) is performed at a calcination temperature of 400 to 700° C. for a calcination time of 0.5 to 12 hours.

[0096] In one embodiment, when the solution of the active component precursor is impregnated into the support composition, the method generally includes a step of impregnating the support composition with the active metal component precursor dissolved in water to obtain a support impregnated with the active metal component precursor. The impregnation method may be a conventional impregnation method, for example, an equal volume impregnation method or an excess amount impregnation method. The water may be, for example, one or more of deionized water, distilled water, or decationized water. In addition, the metal precursor may be dissolved in water to obtain a metal precursor solution, and the metal precursor solution may be introduced into the support by a method of co-impregnation or stepwise impregnation, and the impregnation may be saturated impregnation or supersaturated impregnation. When the catalyst contains two or more types of metal active components, in the co-impregnation, the impregnation liquid obtained by dissolving two or more types of metal elements together in deionized water may be impregnated into the support, and then dried and calcined. In the stepwise impregnation, the metal impregnation liquid obtained by dissolving two or more types of metal elements individually in deionized water may be impregnated into the support, and the support may be dried and calcined after each impregnation. The order of introducing the metals is not particularly limited. For example, a Pt precursor and a precursor of one of the elements in the first metal group may be prepared as a solution and impregnated into the support composition, or the Pt precursor may be impregnated first, dried, and then impregnated with the precursor of the element in the first metal group. For example, when impregnating, the liquid / solid volume ratio of the impregnation liquid to the support is 0.3 to 5.0, preferably 0.6 to 4.0, and the impregnation temperature is 10 to 50°C, preferably 15 to 40°C. After impregnation, the support is preferably dried by leaving it at room temperature for 2 to 10 hours, and then calcined. The calcination temperature is preferably 400 to 700°C, and the calcination time is preferably 0.5 to 12 hours, for example, 1 to 10 hours, or 2 to 9 hours, or 4 to 8 hours. The calcination atmosphere is not particularly limited, and calcination may be performed, for example, in air. During calcination, the volume ratio of air (under standard conditions) / catalyst is, for example, 400 to 1000:1, and the calcination time is preferably 4 to 8 hours.

[0097] According to the present invention's preparation method of a catalyst for dehydrogenating organics to produce hydrogen gas, the active component precursor is a soluble salt of the active component (e.g., one or more of metal nitrates, acetates, chlorides, carbonates, acetate complexes, hydroxides, oxalates, high valent metal acids, high valent metal salts, metal complexes, and ammonium salts). In one embodiment, the high valent metal acid / salt is, for example, one or more of chloroplatinic acid, ammonium chloroplatinate, tetraammineplatinum nitrate, and tetraammineplatinum hydroxide. The phosphorus precursor is, for example, one or more of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and metal phosphate salts.

[0098] According to the method of the present invention for preparing a catalyst for producing hydrogen gas by dehydrogenating organic matter, a carrier impregnated with an active component precursor is placed in an environment of less than -40°C for 1 to 24 hours, and then water adsorbed on the carrier is removed by vacuum drying, followed by calcination to obtain a catalyst.

[0099] In one aspect of the present invention, the present invention provides a hydrogen storage alloy, the hydrogen storage alloy being one or more of rare earth-based AB5 type, zirconium-titanium-based AB2 type, titanium-based AB type, magnesium-based A2B type, and vanadium-based solid solution type hydrogen storage alloys; The molecular formula for rare earth AB5 type hydrogen storage alloy is M m Ni x1 Co x2 Mn x3 Fe x4 Al x5 Sn x6 (4.5≦x1+x2+x3+x4+x5+x6≦5.5; M m La y1 Ce y2 Nd y3 Pr y4 Y y5 And;y1+y2+y3+y4+y5=1; 0.4≦y1≦0.99 (for example, 0.4≦y1≦0.8), 0≦y2≦0.45 (for example, 0.1≦y2≦0.45), 0≦y3≦0.2 (for example, 0≦y3≦0.2), 0≦y4≦0.05 (for example, 0≦y4≦0.05), 0.01≦y5≦0.1 (for example, 0.01≦y5≦0.05), 3≦x1≦5.45 (for example, 3≦x1≦4.9), 0≦x2≦1.5 (for example, 0.1≦x2≦1), 0≦x3≦0.8 (for example, 0.1≦x3≦0.6), 0≦x4≦0.8 (for example, 0.1≦x4≦0.6), 0≦x5≦0.75 (for example, 0.05≦x5≦0.5), 0≦x6≦0.2 (for example, 0≦x6≦0.15)).

[0100] The molecular formula for the zirconium-titanium AB2 type hydrogen storage alloy is AB2 (A=Mg x1 Ca x2 Ti x3 Zr x4 Y x5 La x6 ;x1+x2+x3+x4+x5+x6=0.9~1.1; B=V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7 ;y1+y2+y3+y4+y5+y6+y7=1.9~2.1; 0≦x1≦0.54 (e.g. 0.01≦x1≦0.3, 0.01≦x1≦0.1), 0≦x2≦0.54 (e.g. 0≦x2≦0.25), 0.5≦x3≦1.04 (e.g. 0.6≦x3≦1), 0.05≦x4≦0.58 (e.g. 0.1≦x4≦0.58), 0.01≦x5≦0.2 (e.g. 0.01≦x5≦0.05), 0≦x6≦0.2 (e.g. 0≦x6≦0.05), 0.05≦y1≦1.95 (e.g. 0.05≦y1≦1.8), 0 ≦y2≦1.9 (e.g., 0≦y2≦1.85), 0.05≦y3≦1.95 (e.g., 0.1≦y3≦1.95), 0≦y4≦1.6 (e.g., 0≦y4≦1.5), 0≦y5≦0.5 (e.g., 0≦y5≦0.3), 0.1≦y6≦0.5 (e.g., 0.1≦y6≦0.3), 0≦y7≦0.5 (e.g., 0.1≦y7≦0.2); preferably, 0.7≦x3:(x3+x4)≦0.95; preferably, 1.7≦y1+y2+y3+y4≦2).

[0101] The molecular formula for titanium-based AB type hydrogen storage alloy is AB (A=Ti x1 Zr x2 Y x3 La x4 ;x1+x2+x3+x4=0.85~1.1; B=V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7 ;y1+y2+y3+y4+y5+y6+y7=0.95~1.05; 0≦x1≦1.09 (e.g. 0.9≦x1≦1.05), 0≦x2≦1.09 (e.g. 0≦x2≦0.5), 0.01≦x3≦0.2 (e.g. 0.01≦x3≦0.05), 0≦x4≦0.2 (e.g. 0≦x4≦0.05), 0.05≦y1≦0.5 (e.g. 0.05≦y1≦0.2), 0≦y2≦0.8 (e.g. 0≦y2≦0.2), 0≦y3 ≦0.8 (e.g., 0.05≦y3≦0.4, or 0.1≦y3≦0.4), 0.2≦y4≦1 (e.g., 0.5≦y4≦0.9), 0≦y5≦0.35 (e.g., 0≦y5≦0.1), 0≦y6≦0.45 (e.g., 0≦y6≦0.2), 0≦y7≦0.3 (e.g., 0≦y7≦0.2); it is preferable that x1 and x2 do not take 0 at the same time); The molecular formula for magnesium-based A2B type hydrogen storage alloy is A2B (A=Mg x1 Ca x2 Ti x3 La x4 Y x5 ;x1+x2+x3+x4+x5=1.9~2.1; B=Cr y1 Fe y2 Co y3 Ni y4 Cu y5 Mo y6 ;y1+y2+y3+y4+y5+y6=0.9~1.1; 1.29≦x1≦2.09 (for example, 1.7≦x1≦2.05), 0≦x2≦0.5 (for example, 0≦x2≦0.2), 0≦x3≦0.8 (for example, 0≦x3≦0.5), 0≦x4≦0.5 (for example, 0≦x4≦0.2), 0.01≦x5≦0.2 (for example, 0.05≦x5≦0.1), 0≦y1≦0.3 (for example, 0≦y 1≦0.2, 0.05≦y1≦0.2), 0≦y2≦0.2 (e.g., 0≦y2≦0.1), 0≦y3≦0.6 (e.g., 0≦y3≦0.5), 0.2≦y4≦1.1 (e.g., 0.7≦y4≦1.05), 0≦y5≦0.5 (e.g., 0≦y5≦0.4), 0≦y6≦0.15 (e.g., 0≦y6≦0.1)); The molecular formula for vanadium-based solid solution hydrogen storage alloy is A x1 B x2 (x1+x2=1; A=Tiy1 V y2 Zr y3 Nb y4 Y y5 La y6 Ca y7 ;y1+y2+y3+y4+y5+y6+y7=1; B=Mn z1 Fe z2 Co z3 Ni z4 ;z1+z2+z3+z4=1; 0.7≦x1≦0.95 (e.g. 0.8≦x1≦0.95, 0.9≦x1≦0.95), 0.05≦x2≦0.3 (e.g. 0.05≦x2≦0.2, 0.05≦x2≦0.1), 0.4≦y1≦0.9 (e.g. 0.45≦y1≦0.9, 0.5≦y1≦0.8), 0≦y2≦0.5 (e.g. 0≦y2≦0.4), 0≦y3≦0.5 (e.g. 0≦y3≦0.4), 0≦y4≦0.55 (e.g. 0≦y4≦0.4), 0≦y5≦0.2 (e.g. 0.01≦y5≦0.2 , 0.05≦y5≦0.2), 0≦y6≦0.1 (for example, 0≦y6≦0.05), 0≦y7≦0.1 (for example, 0≦y7≦0.05), 0≦z1≦1 (for example, 0.1≦z1≦1, 0.2≦z1≦0.95), 0≦z2≦0.95 (for example, 0≦z2≦0.9), 0≦z3≦0.3 (for example, 0≦z3≦0.2), 0≦z4≦0.45 (for example, 0.05≦z4≦0.45, 0.05≦z4≦0.3), 0.55≦z1+z2≦1 (for example, 0.7≦z1+z2≦1)).

[0102] In one embodiment, the hydrogen storage alloy of the present invention is 0.61 Ce 0.16 Pr 0.04 Nd 0.19 Ni 3.55 Co 0.75 Mn 0.4 Al 0.3 , (Ti 0.8 V 0.2 ) 0.95 (Fe1) 0.05 , (Ti 0.8 Y 0.2 ) 0.95 (M 0.95 Ni 0.05 ) 0.05 , (Ti 0.4 V0.4 Y 0.2 ) 0.9 (Fe 0.05 Mn 0.95 ) 0.1 、(You 0.4 V 0.4 Y 0.2 ) 0.9 (Fe 0.05 Mn 0.9 It’s 0.05 ) 0.1 、(You 0.7 Nb 0.1 Y 0.2 ) 0.9 (Mn1) 0.1 、(You 0.7 Nb 0.1 Y 0.2 ) 0.9 (Mn 0.7 It’s 0.3 ) 0.1 、(You 0.4 Zr 0.4 Y 0.2 ) 0.93 (Fe 0.2 Mn 0.7 Co 0.1 ) 0.07 、(You 0.4 Zr 0.4 Y 0.2 ) 0.93 (Fe 0.2 Mn 0.7 It’s 0.1 ) 0.07 、(You 0.4 V 0.4 Zr 0.2 ) 0.95 (Fe 0.6 Mn 0.2 Co 0.1 It’s 0.1 ) 0.05 、(You 0.4 V 0.35 Zr 0.2 Y 0.05 ) 0.95 (Fe 0.6 Mn 0.2 Co 0.1 It’s 0.1 ) 0.05 、(You 0.88 Y 0.1 Ca 0.02 ) 0.95 (Fe 0.3 Mn 0.6Co 0.1 ) 0.05 、(You 0.88 Y 0.1 Ca 0.02 ) 0.95 (Fe 0.3 Mn 0.6 It’s 0.1 ) 0.05 、(You 0.7 Nb 0.1 Y 0.2 ) 0.8 (Mn 0.7 It’s 0.3 ) 0.2 、You 0.64 Zr 0.45 Y 0.01 VMn 0.9 It’s 0.1 、Mg 0.01 You 0.93 Zr 0.15 Y 0.01 VMn 0.9 It’s 0.1 、You 0.55 Zr 0.48 Y 0.05 The 0.02 V 0.33 Cr 0.05 Mn 1.5 Fe 0.09 It’s 0.1 、You 0.85 Zr 0.18 Y 0.05 The 0.02 V 0.23 Cr 0.05 Mn 1.5 Fe 0.09 It’s 0.1 Cu 0.1 、You 0.6 Zr 0.4 Y 0.05 V 0.1 Mn 1.8 It’s 0.2 、Mg 0.1 You 0.7 Zr 0.2 Y 0.05 V 0.1 Mn 1.6 It’s 0.2 Cu 0.2 、Ca 0.01 You 0.9 Zr 0.05 Y 0.05 V 1.2 Mn 0.6It’s 0.3 、Ca 0.01 You 0.85 Zr 0.05 Y 0.05 V 1.2 Mn 0.6 It’s 0.1 Cu 0.2 、TiZr 0.05 Y 0.05 V 0.1 Cr 1.4 Mn 0.2 Co 0.1 It’s 0.3 、Mg 0.1 You 0.8 Zr 0.15 Y 0.05 V 0.1 Cr 1.4 Mn 0.2 Co 0.1 It’s 0.1 Cu 0.2 、You 0.5 Zr 0.55 Y 0.05 V 1.79 Mn 0.1 Fe 0.01 It’s 0.2 、You 0.8 Zr 0.25 Y 0.05 V 1.79 Mn 0.1 Fe 0.01 It’s 0.1 Cu 0.1 、Mg 0.01 You 0.63 Zr 0.45 Y 0.01 VMn 0.9 It’s 0.1 、Mg 1.8 Y 0.1 Ni1、Mg 1.8 Y 0.1 Cr 0.05 Ni1、Mg 1.5 You 0.5 Y 0.05 It’s 1.1 、Mg 1.5 You 0.5 Y 0.05 Cr 0.1 Ni1、Mg2Y 0.1 It’s 0.6 Cu 0.4 、Mg2Y 0.1 Cr 0.05 It’s 0.6Cu 0.4 、Mg 1.92 Y 0.08 Ni 0.95 Feb 0.05 、Mg 1.92 Y 0.08 Cr 0.2 Ni 0.75 Feb 0.05 、Mg 1.9 Y 0.1 Feb 0.1 Ni 0.8 Cu 0.1 、Mg 1.9 Y 0.1 Cr 0.1 Feb 0.1 Ni 0.7 Cu 0.1 、Mg 1.9 Y 0.1 Ni 0.8 Co 0.2 、Mg 1.9 Y 0.1 Cr 0.1 Ni 0.8 Co 0.2 、Mg 1.8 Y 0.1 Day 0.1 Ni 0.9 Co 0.1 、Mg 1.8 Y 0.1 Day 0.1 Cr 0.05 Ni 0.9 Co 0.1 、Mg 1.7 Tea 0.2 Y 0.1 Ni 0.7 Co 0.32 、Mg 1.7 Tea 0.2 Y 0.1 Cr 0.05 Ni 0.7 Co 0.3 、TiY 0.01 V 0.1 Feb 0.7 Ni 0.2 、TiY 0.01 V 0.1 Feb 0.7 Mr 0.1 Ni 0.1 、TiY 0.02 V 0.2 Feb 0.8、 TiY 0.02 V 0.2 Feb0.7 Mn 0.1 ,You 0.97 AND 0.03 V 0.05 Cr 0.03 Faith 0.9 ,You 0.97 AND 0.03 V 0.05 Cr 0.03 Faith 0.5 Mn 0.4 ,You 0.9 AND 0.04 V 0.15 Faith 0.9 ,You 0.9 AND 0.04 V 0.05 Faith 0.9 Mn 0.1 ,You 0.91 Zr 0.05 AND 0.04 V 0.1 Cr 0.2 Faith 0.7 ,You 0.91 Zr 0.05 AND 0.04 V 0.1 Cr 0.2 Faith 0.6 Mn 0.1 ,You 0.95 AND 0.05 V 0.26 Faith 0.7 Cu 0.05 ,You 0.95 AND 0.05 V 0.05 Faith 0.7 Mn 0.21 Cu 0.05 ,You 1.02 AND 0.03 V 0.05 Faith 0.9 Neither 0.1 ,You 1.02 AND 0.03 V 0.05 Faith 0.8 Mn 0.1 Neither 0.1 ,The 0.5 EC 0.32 Nd 0.15 Pr 0.02 AND 0.01 Neither 4.4 Faith 0.55 To the 0.05 ,The 0.5 EC 0.32 Nd0.15 Pr 0.02 Y 0.01 Ni 4.4 Fe 0.6 , La 0.8 Ce 0.15 Y 0.05 Ni4Mn 0.5 Al 0.5 , La 0.8 Ce 0.15 Y 0.05 Ni 4.5 Mn 0.5 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni4Co 0.8 Al 0.2 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4.2 Co 0.8 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.7 Al 0.1 Fe 0.2 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.8 Fe 0.2 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.3 Mn 0.1 Al 0.1 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.4 Mn 0.1 , La 0.97 Y 0.03 Selected from Ni4Co1.

[0103] In a preferred embodiment, the hydrogen storage alloy of the present invention is0.8 AND 0.2 ) 0.95 (Mn 0.95 Neither 0.05 ) 0.05 ,(You 0.4 V 0.4 AND 0.2 ) 0.9 (Faith 0.05 Mn 0.9 Neither 0.05 ) 0.1 ,(You 0.7 Nb 0.1 AND 0.2 ) 0.9 (Mn 0.7 Neither 0.3 ) 0.1 ,(You 0.4 Zr 0.4 AND 0.2 ) 0.93 (Faith 0.2 Mn 0.7 Neither 0.1 ) 0.07 ,(You 0.4 V 0.35 Zr 0.2 AND 0.05 ) 0.95 (Faith 0.6 Mn 0.2 Co 0.1 Neither 0.1 ) 0.05 ,(You 0.88 AND 0.1 AC 0.02 ) 0.95 (Faith 0.3 Mn 0.6 Neither 0.1 ) 0.05 Mg 0.01 You 0.93 Zr 0.15 AND 0.01 VMn 0.9 Neither 0.1 ,You 0.85 Zr 0.18 AND 0.05 The 0.02 V 0.23 Cr 0.05 Mn 1.5 Faith 0.09 Neither 0.1 Cu 0.1 Mg 0.1 You 0.7 Zr 0.2 AND 0.05 V0.1 Mr 1.6 Ni 0.2 Cu 0.2 、Ca 0.01 Tea 0.85 Zr 0.05 Y 0.05 V 1.2 Mr 0.6 Ni 0.1 Cu 0.2 、Mg 0.1 Tea 0.8 Zr 0.15 Y 0.05 V 0.1 Cr 1.4 Mr 0.2 Co 0.1 Ni 0.1 Cu 0.2 、Tea 0.8 Zr 0.25 Y 0.05 V 1.79 Mr 0.1 Feb 0.01 Ni 0.1 Cu 0.1 、Mg 1.8 Y 0.1 Cr 0.05 Ni1、Mg 1.5 Tea 0.5 Y 0.05 Cr 0.1 Ni1、Mg2Y 0.1 Cr 0.05 Ni 0.6 Cu 0.4 、Mg 1.92 Y 0.08 Cr 0.2 Ni 0.75 Feb 0.05 、Mg 1.9 Y 0.1 Cr 0.1 Feb 0.1 Ni 0.7 Cu 0.1 、Mg 1.9 Y 0.1 Cr 0.1 Ni 0.8 Co 0.2 、Mg 1.8 Y 0.1 Day 0.1 Cr 0.05 Ni 0.9 Co 0.1 、Mg 1.7 Tea 0.2 Y 0.1 Cr0.05 It’s 0.7 Co 0.3 、TiY 0.01 V 0.1 Fe 0.7 Mn 0.1 It’s 0.1 、TiY 0.02 V 0.2 Fe 0.7 Mn 0.1 、You 0.97 Y 0.03 V 0.05 Cr 0.03 Fe 0.5 Mn 0.4 、You 0.9 Y 0.04 V 0.05 Fe 0.9 Mn 0.1 、You 0.91 Zr 0.05 Y 0.04 V 0.1 Cr 0.2 Fe 0.6 Mn 0.1 、You 0.95 Y 0.05 V 0.05 Fe 0.7 Mn 0.21 Cu 0.05 、You 1.02 Y 0.03 V 0.05 Fe 0.8 Mn 0.1 It’s 0.1 、The 0.5 What 0.32 Nd 0.15 Pr 0.02 Y 0.01 It’s 4.4 Fe 0.55 Heavy 0.05 、The 0.8 What 0.15 Y 0.05 Ni4Mn 0.5 Heavy 0.5 、The 0.45 What 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni4Co 0.8 Heavy 0.2 、The 0.75 What 0.15 Nd 0.05 Pr 0.02 Y0.03 Ni 4.7 Al 0.1 Fe 0.2 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.3 Mn 0.1 Al 0.1 Selected from.

[0104] In one aspect of the present invention, the present invention provides a method for preparing a hydrogen storage alloy, the method comprising the steps of: step (1) of weighing out each of the raw materials of the hydrogen storage alloy so as to obtain a composition of the hydrogen storage alloy, and mixing the raw materials; and step (2) of melting the mixture obtained in step (1) and then annealing the mixture, the melting being performed by electric furnace melting or induction heating melting, and preferably, the melting conditions include a temperature of 1200 to 3000°C, preferably 1800 to 2200°C, more preferably under vacuum, and a temperature of 1×10 -5 ~1×10 -3 Pa (absolute pressure), preferably 0.5 x 10 -4 ~5×10 -4 The annealing conditions include a vacuum or an inert atmosphere (e.g., an argon atmosphere), a temperature of 500 to 900°C (e.g., 700 to 1000°C), and a time of 12 to 360 hours. Optionally, the method further includes a step of crushing the material obtained by the annealing in step (2) after cooling the material to obtain a product of 10 to 400 mesh (e.g., 20 to 400 mesh). Optionally, the method further includes a step of subjecting the material obtained by the annealing in step (2) to an activation treatment, and the activation conditions preferably include a vacuum, a temperature of 50 to 300°C, and a time of 1 to 10 hours.

[0105] In one aspect of the present invention, there is provided a method for supplying high purity hydrogen gas, the method including the steps of: (1) contacting a liquid organic hydrogen storage feedstock with a dehydrogenation catalyst to react with the feedstock to obtain a dehydrogenation reaction product containing hydrogen; (2) cooling the dehydrogenation reaction product to obtain a liquid product and a hydrogen-rich gas product, and recovering the liquid product; (3) contacting the hydrogen-rich gas with a hydrogen storage alloy to obtain a hydrogen-containing alloy, and recovering unadsorbed gas; and, optionally, (3a) removing organic matter in a containment vessel for the hydrogen-containing alloy; and (4) heating the hydrogen-containing alloy to release hydrogen gas.

[0106] According to the method for supplying high-purity hydrogen gas of the present invention, the catalyst of the present invention and / or the hydrogen-absorbing alloy of the present invention are used for producing hydrogen gas by dehydrogenating organic matter.

[0107] According to the method for supplying high-purity hydrogen gas of the present invention, the reaction temperature in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 150 to 450°C (for example, 200 to 400°C, 300 to 350°C), and the weight space velocity per hour in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 0.5 to 50 h -1 (For example, 1~45h -1 , 2~30h -1 ), the pressure in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 0.03 to 5 MPa (gauge pressure) (for example, 0.3 to 5 MPa, 0.1 to 3 MPa, 0.5 to 2 MPa, or 0.2 to 1.6 MPa), and optionally, when a mixture of the liquid organic hydrogen storage raw material and hydrogen gas is contacted with the dehydrogenation catalyst, the hydrogen to hydrocarbon ratio (molar ratio of hydrogen gas to the liquid organic hydrogen storage raw material) is 0 to 10 (for example, 0 to 8). The introduction of hydrogen gas is advantageous in reducing coke generated in the dehydrogenation reaction.

[0108] According to the method for supplying high-purity hydrogen gas of the present invention, in step (2), the cooling temperature for cooling the dehydrogenation reaction product is lower than the boiling point of the organic matter in the liquid product, and preferably lower than the boiling point of the organic matter with the lowest boiling point that becomes liquid at room temperature and normal pressure among the liquid product.

[0109] According to the method for supplying high-purity hydrogen gas of the present invention, in step (3), the hydrogen-rich gas is a hydrogen-rich gas product or a hydrogen-containing gas obtained by further separation of the hydrogen-rich gas product, and the method of further separation includes temperature swing separation, membrane separation, pressure swing adsorption separation, or a combination thereof, and the mass fraction of hydrogen gas in the hydrogen-rich gas is ≧80% (e.g., 80 to 99%, preferably ≧85%, more preferably ≧90%). By adsorbing the hydrogen-rich gas containing a certain amount of hydrogen gas obtained by cooling separation into a hydrogen storage alloy, the adsorption ability of the hydrogen storage alloy can be fully exerted, and the adsorption efficiency of the hydrogen storage alloy can be improved.

[0110] According to the method for supplying high-purity hydrogen gas of the present invention, in step (3), the contact between the hydrogen-rich gas and the hydrogen absorbing alloy is carried out in a container for storing one or more hydrogen absorbing alloys, the number of the hydrogen absorbing alloys may be one or more, and the multiple hydrogen absorbing alloys may be used in a mixed form, and may be used in a series form, a parallel form, or a combined form of series and parallel, and the pressure during contact between the hydrogen-rich gas and the hydrogen absorbing alloy is 0.001 to 5 MPa (for example, 0.01 to 5 MPa, 0.03 to 4 MPa, 0.05 to 5 MPa, 0.08 to 2 MPa, 0.05 to 3 MPa, 0.1 to 1 MPa), and when there are multiple hydrogen storage alloy storage containers connected in series, the contact pressure (also referred to as hydrogen adsorption pressure) at which the hydrogen-rich gas comes into contact with the hydrogen storage alloy at the most downstream position in the flow direction is 0.05 to 5 MPa (e.g., 0.1 to 1 MPa), the temperature (also referred to as hydrogen adsorption temperature) at which the hydrogen-rich gas comes into contact with the hydrogen storage alloy is -70 to 100°C (e.g., -50 to 90°C, -30 to 80°C), and the temperature of the hydrogen-rich gas when in contact with the hydrogen storage alloy is lower than the boiling point of the liquid organic hydrogen storage material at normal pressure.

[0111] According to the method for supplying high-purity hydrogen gas of the present invention, in step (3), the number of hydrogen storage alloy storage vessels is one or more, and the hydrogen storage alloy in the hydrogen storage alloy storage vessel that is last to contact with hydrogen gas in the contact order with hydrogen gas is a hydrogen storage alloy having a high equilibrium pressure, and the hydrogen storage alloy having a high equilibrium pressure has at least one temperature point within a temperature range of 150 to 450 ° C. at which the equilibrium pressure in adsorption of hydrogen gas is 35 MPa or more, and preferably, the hydrogen storage alloy in at least one hydrogen storage alloy storage vessel is a hydrogen storage alloy having a high equilibrium pressure. The hydrogen storage alloy having a high equilibrium pressure can provide high-purity high-pressure hydrogen gas, and the obtained high-purity high-pressure hydrogen gas can be directly used for supplying hydrogen fuel cell vehicles.

[0112] According to the method for supplying high-purity hydrogen gas of the present invention, the step (3a) is carried out by a purging method for removing organic matter in a storage vessel of a hydrogen-containing alloy. For example, the purging method uses hydrogen gas. For example, the method includes stopping the supply of hydrogen-rich gas to the hydrogen-absorbing alloy after the amount of adsorption in the hydrogen-absorbing alloy reaches a predetermined amount, passing hydrogen gas through the hydrogen-absorbing alloy to expel organic gas in the hydrogen-containing alloy and the storage vessel of the hydrogen-containing alloy (also called the storage vessel of the hydrogen-absorbing alloy), and introducing the organic gas into a storage tank for storage, or allowing the organic gas to be adsorbed by the hydrogen-absorbing alloy in the storage vessel of another hydrogen-absorbing alloy. The purity of the hydrogen gas for purging is preferably more than 90% by weight, more preferably more than 95% by weight, for example more than 99% by weight.

[0113] According to the method for supplying high-purity hydrogen gas of the present invention, in step (4), the temperature at which hydrogen gas is released from the hydrogen storage alloy (i.e., the temperature at which the hydrogen storage alloy is heated; abbreviated as hydrogen release temperature) is 150 to 450°C, the pressure of the released hydrogen gas is ≧35 MPa (e.g., 35 to 100 MPa) in order to obtain high-purity high-pressure hydrogen gas, or the partial pressure of the released hydrogen gas is 0.1 to 5 MPa in order to obtain high-purity hydrogen gas, and the hydrogen release temperature is higher than the hydrogen adsorption temperature.

[0114] According to the method for supplying high-purity hydrogen gas of the present invention, the method further includes a process of releasing hydrogen gas from a hydrogen-containing alloy and contacting the released hydrogen gas with another hydrogen-absorbing alloy to form a hydrogen-containing alloy, the process being carried out once or a plurality of times, and the hydrogen-absorbing alloy used in at least the last process is a hydrogen-absorbing alloy having a high equilibrium pressure.

[0115] According to the method for supplying high purity hydrogen gas of the present invention, the hydrogen storage alloy is a combination of a first hydrogen storage alloy and a second hydrogen storage alloy, the first hydrogen storage alloy is a magnesium-based A2B type hydrogen storage alloy according to the present invention used for contact with a hydrogen-rich gas, the second hydrogen storage alloy is a hydrogen storage alloy used for pressurizing the first hydrogen storage hydrogen gas and has a high equilibrium pressure, and the second hydrogen storage alloy is one or more of the rare earth-based AB5 type, zirconium titanium-based AB2 type, and titanium-based AB type hydrogen storage alloys according to the present invention, and the hydrogen-rich gas is first contacted with the first hydrogen storage alloy. impurities are separated by passing the alloy through a high-purity separator; then, the high-purity hydrogen gas released from the first hydrogen storage alloy is contacted with a second hydrogen storage alloy; then, the second hydrogen storage alloy is made to release hydrogen gas under high pressure; the hydrogen release temperature of the first hydrogen storage alloy is higher than the hydrogen adsorption temperature of the second hydrogen storage alloy, and the temperature difference therebetween is preferably ≧100°C (e.g., 350°C≧temperature difference≧150°C); the first hydrogen storage alloy and the second hydrogen storage alloy are present in storage tanks of different hydrogen storage alloys, and a heat exchange system is present between the storage tank of the first hydrogen storage alloy and the storage tank of the second hydrogen storage alloy; The hydrogen adsorption temperature when the hydrogen-rich gas comes into contact with the first hydrogen storage alloy is 20 to 150°C (for example, 50 to 100°C), and the hydrogen gas partial pressure is 0.001 to 0.1 MPa (0.001 to 0.03 MPa). The temperature at which hydrogen gas is released from the first hydrogen storage alloy (hydrogen release temperature) is 150 to 450°C (for example, 200 to 350°C), and the hydrogen gas partial pressure during hydrogen release is 0.1 to 5 MPa (for example, 0.1 The second hydrogen absorbing alloy has a hydrogen adsorption temperature of -70 to 100°C (e.g., -30 to 100°C), a hydrogen gas partial pressure during hydrogen adsorption is 0.1 to 5 MPa (e.g., 0.1 to 1 MPa), a hydrogen release temperature of the second hydrogen absorbing alloy is 150 to 450°C (e.g., 200 to 350°C), and a hydrogen gas partial pressure during hydrogen release is ≧35 MPa (e.g., 35 to 100 MPa).

[0116] According to the method for supplying high-purity hydrogen gas of the present invention, the liquid organic hydrogen storage raw material is an organic compound having a ring in the molecule, optionally containing a heteroatom, and the heteroatom may be present in a ring shape, and examples of the liquid organic hydrogen storage raw material include saturated or unsaturated hydrocarbons containing a cycloalkane ring, for example, saturated or unsaturated hydrocarbons containing no heterocyclic atoms and containing a cycloalkane ring, more specifically, saturated or unsaturated hydrocarbons having a total number of rings of an aromatic ring and a cycloalkane ring of 2 or less, containing no heterocyclic atoms and containing a cycloalkane ring, for example, cyclohexane, methylcyclohexane, decahydronaphthalene, and bi(cyclohexane), and saturated or unsaturated hydrocarbons containing a heteroatom. and saturated or unsaturated hydrocarbons containing a cycloalkane ring, such as nitrogen-containing heterocyclic compounds, and nitrogen / boron-containing heterocyclic compounds; the nitrogen-containing heterocyclic compounds include one or more of decahydrocarbazole, dodecahydroethylcarbazole, indoline, 4-aminopiperidine, piperidine-4-carboxamide, perhydro-4,7-phenanthroline, 2-methyl-1,2,3,4-tetrahydroquinoline, and 2,6-dimethyldecahydro-1,5-naphthyridine, and the nitrogen / boron-containing heterocyclic compounds include one or more of 1,2-azaborinates, and 3-methyl-1,2-azaborolidine.

[0117] The method for supplying high-purity hydrogen gas of the present invention further includes a step of introducing the released hydrogen gas into a hydrogen gas storage tank to store the hydrogen gas, or a step of directly using the obtained high-purity high-pressure hydrogen gas to refuel a hydrogen fuel cell vehicle.

[0118] In one aspect, the present invention provides a highly efficient, distributed method for producing high purity, high pressure hydrogen gas. The method includes the steps of: performing a dehydrogenation reaction of a liquid organic hydrogen storage raw material in a dehydrogenation reactor in the presence of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas; cooling and separating the dehydrogenation reaction product in a cooling and separation device to obtain a hydrogen-rich stream and an organic liquid; contacting the hydrogen-rich stream or the purified hydrogen-rich stream with a hydrogen storage alloy in a storage vessel for the hydrogen storage alloy to obtain a hydrogen-containing alloy; removing organic matter in the storage vessel for the hydrogen storage alloy by a purging method using hydrogen gas, preferably with a purge hydrogen gas having a purity of more than 90% by weight (e.g., more than 95% by weight, more than 99% by weight); heating the hydrogen-containing alloy to release hydrogen gas, thereby obtaining high-pressure hydrogen gas, and supplying the obtained high-pressure hydrogen gas to a hydrogen consumption device or a high-pressure hydrogen gas storage tank for storage (e.g., the obtained high-pressure hydrogen gas may be used directly for refilling a hydrogen fuel cell vehicle).

[0119] In one aspect of the present invention, the present invention provides a system for supplying high-purity high-pressure hydrogen gas. The system includes a liquid organic hydrogen storage raw material storage-supply device for storing a liquid organic hydrogen storage raw material and supplying the liquid organic hydrogen storage raw material to a dehydrogenation reactor, a dehydrogenation liquid storage device for storing a liquid product obtained by dehydrogenating the liquid organic hydrogen storage raw material, a dehydrogenation reactor device for performing a dehydrogenation reaction of the liquid organic hydrogen storage raw material under the action of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas, a cooling and separating device for separating the dehydrogenation reaction product to obtain a hydrogen-rich gas product and a liquid product, a hydrogen storage-hydrogen supply device including a hydrogen storage alloy storage container and a hydrogen storage alloy heating system, which brings a hydrogen-rich gas into contact with a hydrogen storage alloy at low temperature and low pressure to adsorb hydrogen and, after saturated adsorption, performs dehydrogenation by heating, and, optionally, a catalytic converter for converting the hydrogen-rich gas into hydrogen gas, which is then heated to adsorb hydrogen. The system includes a purging device used to remove the equipment, and a hydrogen gas supplying device that supplies high-pressure hydrogen gas to a hydrogen consuming device or a hydrogen gas storage tank, and preferably the system is installed in a hydrogen refueling station as a container-type hydrogen production system integrated with the inside of a container, or is directly incorporated into the hydrogen refueling station for use, and preferably the hydrogen absorption-hydrogen supplying device includes one or more hydrogen storage alloy storage vessels, and the multiple hydrogen storage alloy storage vessels may be connected in a parallel form, a series form, or a combined form of parallel and series, and preferably at least one hydrogen storage alloy storage vessel is a high-pressure resistant vessel, and / or the hydrogen gas supplying device is a high-pressure resistant device, for example a device with an allowable pressure of 35 MPa or more.

[0120] FIG. 3 shows a supply system for high-purity high-pressure hydrogen gas provided by the present invention. In the figure, 1 indicates an organic liquid storage tank, 2 indicates a feed pump, 3 indicates a heat exchanger, 4 indicates a dehydrogenation reactor, 5 indicates a heat exchanger, 6 indicates a hydrogen storage tank, 7 indicates a one-way valve, 8 indicates an energy transmission system, 9 indicates a purge system, and 10 indicates a hydrogen storage control system. The organic liquid feedstock storage system shown in FIG. 3 includes an organic liquid storage tank (1) provided with an inlet for an organic liquid feedstock and an outlet for an organic liquid feedstock, and a feedstock pump (2) connected to an organic liquid dehydrogenation reactor. The illustrated organic liquid dehydrogenation reaction system includes a dehydrogenation reactor (4) and an organic liquid heat exchanger (3) connected to the inlet and outlet of the organic liquid dehydrogenation reactor for cooling the gas from the outlet of the reactor and preheating the feedstock. The gas from the outlet of the reactor may further pass through a heat exchange / cooling device (5) to obtain a hydrogen-rich stream by cooling and separation. The hydrogen-rich stream may or may not pass through one or more of the membrane separation device and the pressure swing adsorption device. The illustrated purification and pressurization system includes one or more hydrogen storage tanks (6), each connected to a set of backflow prevention devices (7) and connected in parallel to at least one hydrogen supply pipeline, at least one energy transmission system (8) for supplying energy into each hydrogen storage tank to separate hydrogen gas from the solid hydrogen storage material, at least one vacuum pump (9) and purge system having respective flow meters connected to the outlet and inlet of the hydrogen storage tank for removing impurity gases in the hydrogen storage tank, and a control system (10) for comprehensively controlling the hydrogen adsorption time, hydrogen release time, and operation time of the energy transmission system for each hydrogen storage tank according to the amount of hydrogen produced by the dehydrogenation reaction. The flow meters at the inlets of the hydrogen storage tanks are used to calculate the total amount of hydrogen adsorption in the hydrogen storage alloy. When the amount of hydrogen absorbed by the hydrogen storage alloy in a single hydrogen storage tank reaches 80% or more of the total hydrogen saturation adsorption amount, the supply valve of the hydrogen-rich stream of the hydrogen storage tank is closed, and the purge system is started to remove impurities in the hydrogen storage tank, and when the purity of the hydrogen gas in the purge pipeline reaches 99% or more, the purge system is stopped.The total amount of hydrogen adsorbed simultaneously in the hydrogen storage tank is preferably higher than 120% of the hydrogen gas production rate. The hydrogen storage alloy is connected to at least one hydrogen supply pipeline via a hydrogen release valve, and the hydrogen supply pipeline conveys the hydrogen gas to the hydrogen gas storage device. The hydrogen release valves on the hydrogen supply pipeline for the hydrogen storage alloy are not opened or closed at the same time.

[0121] In one aspect of the present invention, the present invention provides a mobile hydrogen supply system including a transportation vehicle and a high-purity, high-pressure hydrogen gas supply system according to the present invention installed on the transportation vehicle.

[0122] In one aspect of the present invention, the present invention provides a distributed hydrogen supply apparatus comprising a supply system for high purity high pressure hydrogen gas according to the present invention and optionally comprising a high pressure hydrogen gas storage tank.

[0123] The method for preparing high-purity hydrogen gas provided by the present invention can efficiently provide high-purity hydrogen gas, and can provide high-purity high-pressure hydrogen gas when a hydrogen storage alloy having a high equilibrium pressure is used. The present invention may also have at least one of the following beneficial effects, and preferably has two or more of the following beneficial effects: (1) According to the method of the present invention, a high dehydrogenation efficiency can be achieved for a liquid organic hydrogen storage compound. (2) It can have a higher dehydrogenation conversion rate relative to liquid organic hydrogen storage compounds; (3) It may have higher dehydrogenation selectivity than liquid organic hydrogen storage compounds. (4) It can have a higher hydrogen adsorption efficiency in hydrogen storage metals. (5) In the presence of organic matter, hydrogen storage metals exhibit favorable hydrogen adsorption efficiency. (6) By combining the dehydrogenation of organic matter, the cooling separation, and the hydrogen absorption by the hydrogen storage alloy, the conversion rate of the dehydrogenation of organic matter can be improved. (7) The dehydrogenation of organic feedstocks and the hydrogen adsorption of hydrogen-absorbing alloys become more efficient.

[0124] The dehydrogenation catalyst for producing hydrogen gas by dehydrogenating an organic compound provided by the present invention has advantages of high dehydrogenation activity, hydrogen gas selectivity and / or hydrogen gas production rate.

[0125] The dehydrogenation catalyst for producing hydrogen gas by dehydrogenating an organic substance provided by the present invention can use a non-precious metal instead of a part of a precious metal, and can reduce the amount of precious metal used while maintaining high dehydrogenation activity, hydrogen gas selectivity and / or hydrogen gas production rate.

[0126] The catalyst provided by the present invention can be used to produce hydrogen gas by dehydrogenating a hydrogen-storing organic compound, in particular, by dehydrogenating a ring-containing organic compound, such as a cycloalkane ring- or heterocyclic ring-containing organic compound, and has a high conversion, selectivity and / or hydrogen gas production rate.

[0127] According to the present invention, the percentage content of the modified metal oxide as a crystalline phase may be measured by X-ray diffraction and a modified Rietveld model with phase filtering based on RV. Siriwardane, JA Poston, G. Evans, Jr. Ind. Eng. Chem. Res. 33 (1994), 2810-2818, and the modified Rietveld model based on RIQAS Rietveld Analysis, Guidebook, Material Data, Inc., Berkley, CA (1999), to calculate the weight percent content of the modified metal oxide as a crystalline phase in an approximate manner.

[0128] According to the present invention, the percentage content of the modified metal oxide chemical composition is the total amount of the modified metal oxide in the support composition, and the percentage content of the modified metal oxide chemical composition may be measured by X-ray fluorescence analysis or chemical analysis.

[0129] According to the present invention, the weight percent content of the modified metal oxide on the surface of the support composition is measured by XPS method, and the thickness of the measured surface layer is within a thickness of 5 nm from the outer surface.

[0130] The present invention also provides the following technical configurations: [1] A support composition for a catalyst for producing hydrogen gas by dehydrogenating an organic substance, the support composition comprising alumina and a modified metal oxide, the modifying metal oxide is titanium oxide and / or zirconium oxide; A support composition, wherein the η of the modified metal oxide is η<0.3 (η=wt.% content of the crystalline phase of the modified metal oxide in the support composition / wt.% content of the chemical composition of the modified metal oxide in the support composition; titanium oxide is calculated as TiO2 and zirconium oxide is calculated as ZrO2).

[0131] [2] The support composition of claim [1], wherein η=0, preferably the first metal oxide is dispersed as a monolayer on the alumina substrate.

[0132] [3] The support composition according to the configuration [1], wherein the mass fraction of alumina in the support composition is 80 to 98.5%, preferably 83 to 97.5%, or 85 to 95%, or 90 to 95%, and the mass fraction of the modifying metal oxide is 1.5 to 20%, preferably 2.5 to 17%, or 5 to 15%, or 5 to 10%.

[0133] [4] The carrier composition according to the configuration [3], wherein the modified metal oxide comprises a titanium oxide, and preferably in the carrier composition, the mass fraction of titanium dioxide is preferably 2 to 20%, for example 5 to 15%, or 5 to 10%, or 2.5 to 17%, and the mass fraction of zirconium dioxide is preferably 0 to 8%, for example 0 to 6%, or 0 to 3%, or 1 to 6%.

[0134] [5] In comparison with the pure phase of TiO2, the XPS spectrum of the support composition shows that the Ti 2P 3 / 2There is a shift in the orbital electron binding energy, and the peak at 458.8 eV of the binding energy shifts by 0.6 to 0.7 eV to the high binding energy side to 459.4 to 459.5 eV, and / or Ti 2P 1 / 2 The carrier composition according to the configuration [4], wherein the peak of the orbital electron binding energy at 464.5 eV is shifted by 0.8 to 0.9 eV to the high binding energy side to 465.3 to 465.4 eV.

[0135] [6] The support composition according to the structure [1], wherein the oxide substrate has at least one phase structure of γ-alumina, η-alumina, ρ-alumina or χ-alumina.

[0136] [7] The specific surface area of ​​the carrier composition is 100 to 350 m 2 / g of the carrier composition described in [1].

[0137] [8] The carrier composition according to the above aspect [1], wherein the pore volume of the carrier composition is 0.3 to 1.3 mL / g.

[0138] [9] A step (1) of contacting an alumina substrate with a gas flow of a modified metal oxide precursor carried by a gas, and stopping the introduction of the gas flow of the modified metal oxide precursor carried by the gas when a predetermined amount of titanium tetrachloride is supported, thereby obtaining an alumina substrate supported with a titanium oxide precursor and / or a zirconium oxide precursor as a modified metal oxide precursor; and (2) hydrolyzing and calcining the alumina substrate carrying the modified metal oxide precursor to obtain a support composition.

[0139]

[10] The method for preparing a carrier composition according to the above-mentioned configuration [9], wherein the titanium oxide precursor is selected from titanium tetrachloride, ethyl titanate, isopropyl titanate, titanium acetate, and mixtures thereof, and is preferably titanium tetrachloride, and the zirconium oxide precursor is selected from zirconium tetrachloride, zirconium ethoxide, zirconium methoxide, zirconium isopropoxide, tetrabutyl zirconate, and mixtures thereof, and is preferably zirconium tetrachloride and / or zirconium methoxide.

[0140]

[11] The method for preparing the carrier composition according to the above aspect [9], wherein the alumina substrate is one or more of γ-alumina, η-alumina, ρ-alumina and χ-alumina.

[0141]

[12] The specific surface area of ​​the alumina substrate is 100 to 350 m 2 / g, and preferably, the reduction rate of the specific surface area of ​​the resulting support composition compared to the specific surface area of ​​the alumina substrate is ≦10%.

[0142]

[13] The method for preparing a carrier composition according to the above aspect [9], wherein the alumina substrate has a pore volume of 0.3 to 1.3 mL / g.

[0143]

[14] The method for preparing a support composition according to the above aspect [9], wherein the gas is an anhydrous inert gas, and the water content in the anhydrous inert gas is 10 ppm or less. Preferably, the content of the modified metal oxide precursor (calculated as metal oxide) in the gas stream of the modified metal oxide precursor carried by the gas is 0.1-3 g / L.

[0144]

[15] The method for preparing a carrier composition according to the above aspect [9], wherein in step (1), the temperature of the gas is from room temperature to 350°C, for example, from room temperature to 300°C, or from 15 to 300°C.

[0145]

[16] The method for preparing a carrier composition according to the above aspect [9], wherein in the step (1), the pressure in the contact is 0.05 to 5 atm, for example, 1 to 3 atm.

[0146]

[17] A method for preparing a carrier composition according to the above aspect [9], wherein the ratio of the volumetric flow rate of the gas per minute to the volume of the alumina substrate is 3 to 80:1, for example 5 to 30:1, and preferably 10 to 25:1, the volume of the gas being calculated as the volume under standard conditions, and the volume of the alumina substrate being calculated as the bulk volume.

[0147]

[18] A method for preparing a support composition according to the above aspect [9], wherein when the alumina substrate is contacted with the gas stream of modified metal oxide precursor carried by the gas, the alumina substrate is under fluidized conditions or under stirring, and the fluidized conditions can be, for example, a bubbling bed, a turbulent bed, a high velocity bed or a conveying bed.

[0148]

[19] The method for preparing the carrier composition according to the configuration [9], wherein in step (2), the hydrolysis of the alumina substrate carrying the modified metal oxide precursor is carried out by contacting the alumina substrate carrying the modified metal oxide precursor with a steam-containing gas. In one embodiment, the ratio of the steam-containing gas to the alumina substrate with which the steam-containing gas is in contact (the ratio of the volume of the steam-containing gas to the bulk volume of the alumina substrate under standard conditions) is 3 to 80:1, for example 5 to 30:1, preferably 10 to 25:1, the proportion of the steam in the steam-containing gas in the total gas volume is 0.1 volume % to 100 volume %, preferably 3 volume % to 100 volume %, more preferably 10 volume % to 70 volume %, and the gas other than the steam can be an inert gas or air. The hydrolysis time is, for example, 1 hour to 50 hours, preferably 2 hours to 30 hours. Typically, the hydrolysis time is equal to or greater than the support time (support time refers to the time during which the alumina substrate is in contact with the gas stream of gas-borne modified metal oxide precursor).

[0149]

[20] The method for preparing a carrier composition according to the above item [9], wherein the calcination is performed at a calcination temperature of 350° C. to 700° C. for a calcination time of 0.5 to 12 hours.

[0150]

[21] A catalyst for producing hydrogen gas by dehydrogenating an organic compound, the catalyst comprising a support including alumina and a modified metal oxide, and an active metal component, the modified metal oxide being titanium oxide and / or zirconium oxide, the active metal component being an oxide of an active metal and / or an active metal element, the active metal being, for example, one or more of a Group VIIIB metal, a Group VIIB metal, a Group VB metal, a Group VIB metal, a Group IB metal, a rare earth element, an alkaline earth metal, and a Group IVA metal; Preferably, the active metal comprises Pt and / or Ni, and optionally comprises other elements. Preferably, the other elements are one or more of V, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Mo, Sn, Ca, Pt, Pd, Ru, Re, Rh, Ir, Os, Zn, P, and In. Preferably, the support is a support composition according to any one of the configurations [1] to [8], or a support composition prepared by the method according to any one of the configurations [9] to

[20] .

[0151]

[22] A catalyst for producing hydrogen gas by dehydrogenating an organic substance, comprising a support and a supported active metal component, the support being the support composition according to any one of structures [1] to [8], or the support composition prepared by the method according to any one of structures [9] to

[20] , the active metal comprising Pt and optionally other metals, which may be precious or non-precious metals, the other metals being one or more of the elements Pd, Ru, Re, Rh, Ir, Os, Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca.

[0152]

[23] The catalyst according to the configuration

[22] , wherein the content of the active metal in the catalyst is 0.1 to 20% by weight, for example, 0.1 to 15% by weight, the content of the carrier is 85 to 99.9% by weight, and the content of Pt is 0.1 to 10% by weight. Note that, in the composition of the catalyst of the present invention, the content of the active metal is calculated as a simple substance for the noble metal, and is calculated as an oxide for the non-noble metal.

[0153]

[24] The catalyst according to the structure

[22] , wherein the other metal is one or more of Pd, Ru, Re, Rh, Ir and Os.

[0154]

[25] The catalyst according to the above-mentioned configuration

[24] , wherein the content of the active metal in the catalyst is 0.1 to 10% by weight, preferably 0.5 to 8% by weight, and the content of the support is 90 to 99.9% by weight, preferably 92 to 99.5% by weight.

[0155]

[26] The catalyst according to the above-mentioned configuration

[25] , wherein the content of Pt in the catalyst is 0.1 to 2% by weight, for example, 0.3 to 1.5% by weight or 0.5 to 1% by weight, the content of the other metal is 0 to 9.9% by weight, for example, 0.1 to 2, or 0.2 to 1% by weight or 0.1 to 0.8% by weight, and the content of the support is preferably 90 to 99.9% by weight, for example, 96 to 99.6% by weight, or 98 to 99.5% by weight, or 98.5 to 99.3% by weight.

[0156]

[27] The catalyst according to the structure

[22] , wherein the other metal is one or more of Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu and Ca.

[0157]

[28] The catalyst according to the above aspect

[27] , wherein the content of Pt in the catalyst is 0.1 to 10% by weight, and the content of the other metal is 0 to 15% by weight.

[0158]

[29] The catalyst according to the above-mentioned configuration

[28] , wherein the content of Pt in the catalyst is 0.1 to 2% by weight, for example, 0.5 to 1.5% by weight, the content of other metals is 0 to 15% by weight, for example, 1 to 10% by weight, or 2 to 8% by weight, or 3 to 7% by weight, and the content of the support is preferably 85 to 99.9% by weight, for example, 90 to 99% by weight, or 90 to 98% by weight, or 92 to 97% by weight.

[0159]

[30] A catalyst for producing hydrogen gas by dehydrogenating an organic substance, comprising a support and a supported active metal component, the support being the support composition according to any one of structures [1] to [8], or the support composition prepared by the method according to any one of structures [9] to

[20] , the active metal comprising nickel and optionally other metals comprising one or more of Zn, Sn, Cu, Fe, Ag, p, In, Re, Mo, Co, Ca, and W.

[0160]

[31] The catalyst according to the above-mentioned configuration

[30] , wherein the mass fraction of the active metal is 5% to 30% and the mass fraction of the support is 70 to 95%, preferably the mass fraction of the support is 75 to 90%, and the mass fraction of the active metal is preferably 10% to 25%.

[0161]

[32] The catalyst according to the above-mentioned configuration

[30] , wherein the content of nickel (calculated as oxide) in the catalyst is 5 to 25% by weight, preferably 6 to 20% by weight, for example, 7 to 15% by weight, or 7 to 12% by weight, or 8 to 11% by weight, and the content of other metals (calculated as oxides) in the catalyst is 0 to 15% by weight, preferably 0 to 10% by weight, for example, 0.5 to 8% by weight, or 1 to 5% by weight.

[0162]

[33] A method for preparing the catalyst according to any one of the above

[21] to

[32] , A step (1) of impregnating a support with a solution of an active metal component precursor in water to obtain a support impregnated with the active metal component precursor; (2) drying and calcining the support impregnated with the active metal component precursor; Preferably, the support is a support composition according to any one of the configurations [1] to [8], or a support composition prepared by the method according to any one of the configurations [9] to

[20] .

[0163]

[34] A method for preparing a catalyst according to the above-mentioned configuration

[33] , wherein the active metal comprises a non-precious metal, and in the step (2), the support impregnated with the active metal component precursor is placed in an environment of less than -40°C for 1 to 24 hours, and then water adsorbed on the support is removed by vacuum drying, followed by calcination to obtain a catalyst composition.

[0164]

[35] The method for preparing a catalyst according to the above-mentioned structure

[33] , wherein the active metal component precursor is one or more of a metal nitrate, a metal chloride, a metal acetate, a metal carbonate, a metal acetate complex, a metal hydroxide, a metal oxalate complex, and a high valent metal acid salt.

[0165]

[36] The method for preparing the catalyst according to the above item

[32] , wherein the calcination in the step (2) is carried out at a calcination temperature of 400 to 700° C. for a calcination time of preferably 0.5 to 12 hours.

[0166]

[37] A method for using a catalyst composition, comprising a step of contacting a hydrogen-storing organic compound with the dehydrogenation catalyst according to any one of the configurations

[21] to

[32] or the dehydrogenation catalyst prepared by the method according to any one of the configurations

[33] to

[36] , and generating hydrogen gas by a dehydrogenation reaction.

[0167]

[38] The dehydrogenation reaction temperature is 150-450°C, and the weight hourly space velocity is 0.5-50 h -1 The method according to configuration

[37] , wherein the reaction pressure is 0.3-5 MPa, the contact is carried out in the presence or absence of hydrogen gas, and the hydrogen-to-oil ratio (the molar ratio of hydrogen gas introduced into the dehydrogenation reactor to the hydrogen-storing organic compound) is 0-10.

[0168]

[39] The method according to the above-mentioned structure

[37] , wherein the hydrogen-storing organic compound is a saturated or unsaturated hydrocarbon containing a cycloalkane ring, for example, the hydrogen-storing organic compound is one or more of cyclohexane, methylcyclohexane, decahydronaphthalene, bi(cyclohexane), decahydrocarbazole, dodecahydroethylcarbazole, indoline, 4-aminopiperidine, piperidine-4-carboxamide, perhydro-4,7-phenanthroline, 2-methyl-1,2,3,4-tetrahydroquinoline, 2,6-dimethyldecahydro-1,5-naphthyridine, 1,2-BN-cyclohexane, and 3-methyl-1,2-BN-cyclopentane.

[0169] The present invention also provides the following technical configurations: [1] A method for supplying high-purity hydrogen gas, comprising: a step of contacting the liquid organic hydrogen storage raw material with a dehydrogenation catalyst to react with the liquid organic hydrogen storage raw material and obtaining a dehydrogenation reaction product containing hydrogen gas; cooling the dehydrogenation reaction product to obtain a liquid product and a hydrogen-rich gaseous product, and recovering the liquid product; contacting the hydrogen-rich gas with a hydrogen storage alloy to obtain a hydrogen-containing alloy and recovering unadsorbed gas; Optionally, removing organic matter within the containment vessel of the hydrogen-containing alloy; and heating the hydrogen-containing alloy to release hydrogen gas and obtain high purity hydrogen gas.

[0170] [2] The method of claim [1], wherein the hydrogen-rich gas is a hydrogen-rich gas product or a hydrogen gas-containing gas obtained by further separation of the hydrogen-rich gas product, and the method of further separation includes temperature swing separation, membrane separation, pressure swing adsorption separation, or a combination thereof.

[0171] [3] The method according to the configuration [1] or [2], wherein the mass fraction of hydrogen gas in the hydrogen-rich gas is ≧80%, for example, 80 to 99%, preferably ≧85%, and more preferably ≧90%.

[0172] [4] The method according to configuration [1], wherein the temperature during contact between the hydrogen-rich gas and the hydrogen storage alloy is -70 to 100°C, preferably -50 to 90°C, and more preferably -30 to 80°C.

[0173] [5] The method according to the above-mentioned configuration [1], wherein the temperature to which the dehydrogenation reaction product is cooled is lower than the boiling point of the organic matter, and preferably lower than the boiling point of the organic matter having the lowest boiling point among the liquid products that becomes liquid at room temperature and normal pressure.

[0174] [6] The method according to any one of the configurations [1] to [5], wherein the temperature of the hydrogen-rich gas when contacted with the hydrogen storage alloy is lower than the boiling point of the liquid organic hydrogen storage raw material under normal pressure.

[0175] [7] The method according to the above item [1], wherein the number of hydrogen storage alloys may be one or more, and the multiple hydrogen storage alloys may be used in a mixed form, or in a series form, a parallel form, or a combined form of series and parallel, and preferably, the pressure at which the hydrogen-rich gas contacts the hydrogen storage alloy is 0.001 to 5 MPa, for example, 0.01 to 5 MPa, or 0.03 to 4 MPa, or 0.05 to 5 MPa, or 0.08 to 2 MPa, or 0.005 to 3 MPa, or 0.1 to 1 MPa.

[0176] [8] The contact between the hydrogen-rich gas and the hydrogen storage alloy is carried out in one or more hydrogen storage alloy storage vessels, and the pressure during contact between the hydrogen-rich gas and the hydrogen storage alloy is 0.05 to 5 MPa, preferably 0.1 to 1 MPa; The method according to configuration [1], wherein when there are multiple hydrogen storage alloy storage containers connected in series, the contact pressure with the hydrogen storage alloy located most downstream in the flow direction of the hydrogen-rich gas is preferably 0.05 to 5 MPa, and more preferably 0.1 to 1 MPa.

[0177] [9] The method according to configuration [1], wherein the number of storage vessels for hydrogen storage alloys is one or more, the hydrogen storage alloy in the storage vessel for the hydrogen storage alloy that comes into contact with hydrogen gas last in the order of contact with hydrogen gas is a hydrogen storage alloy having a high equilibrium pressure, and the hydrogen storage alloy having high equilibrium pressure has at least one temperature point within a temperature range of 150 to 450°C at which the equilibrium pressure in hydrogen gas adsorption is 35 MPa or higher, and preferably the hydrogen storage alloy in at least one storage vessel for the hydrogen storage alloy is a hydrogen storage alloy having a high equilibrium pressure.

[0178]

[10] The method according to the above-mentioned configuration [1], further comprising a process of releasing hydrogen gas from the hydrogen-containing alloy and contacting the released hydrogen gas with another hydrogen-absorbing alloy to form a hydrogen-containing alloy, the process being carried out one or more times, and the hydrogen-absorbing alloy used in at least the last process is a hydrogen-absorbing alloy having a high equilibrium pressure.

[0179]

[11] The method according to any one of the above [1] to

[10] , wherein the hydrogen storage alloy is one or more of rare earth-based AB5 type, zirconium-titanium-based AB2 type, titanium-based AB type, magnesium-based A2B type, and vanadium-based solid solution type alloys.

[0180]

[12] The molecular formula specifically showing the rare earth-based AB5 type hydrogen storage alloy is M m Ni x1 Co x2 Mn x3 Fe x4 Al x5 Sn x6 4.5≦x1+x2+x3+x4+x5+x6≦5.5, 3≦x1≦5.5, preferably 3≦x1≦4.9, 0≦x2≦1.5, preferably 0.1≦x2≦1, 0≦x3≦0.8, preferably 0.1≦x3≦0.6, 0≦x4≦0.8, preferably 0.1≦x4≦0.6, 0≦x5≦0.75, preferably 0≦x5≦0.5, 0≦x6≦0.2, preferably 0≦x6≦0.15; and M m includes La, Ce, Pr, Nd and Y, M m =La y1 Ce y2Nd y3 Pr y4 Y y5 The method according to claim 11, wherein the mixed rare earth metal is represented by the formula: y1+y2+y3+y4+y5=1, 0.4≦y1≦1, preferably 0.4≦y1≦0.8, 0≦y2≦0.45, preferably 0.1≦y2≦0.45, 0≦y3≦0.2, 0≦y4≦0.05, and 0≦y5≦0.05.

[0181]

[13] In the zirconium-titanium AB2 type hydrogen storage alloy, A=Mg x1 Ca x2 Ti x3 Zr x4 Y x5 La x6 , x1+x2+x3+x4+x5+x6=0.9-1.1, 0≦x1≦1.1, preferably 0.90≦x1≦1.05, 0≦x2≦0.7, preferably 0≦x2≦0.25, 0≦x3≦1.05, preferably 0.8≦x3≦1, 0≦x4≦1.05, preferably 0.85≦x4≦1, 0≦x5≦0.2, preferably 0≦x5≦0.05, 0≦x6≦0.2, preferably 0≦x6≦0.05, and x3 / (x3+x4)≧0.7 or x3 / (x3+x4)≦0.3; B=V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7 , y1+y2+y3+y4+y5+y6+y7=1.9 to 2.1, 0≦y1≦2.1, preferably 0≦y1≦1.8, 0≦y2≦2.1, preferably 0≦y2≦1.85, 0≦y3≦2.1, preferably 0≦y3≦2.05, 0≦y4≦1.6, preferably 0≦y4≦1.5, 0≦y5≦0.5, preferably 0≦y5≦0.3, 0≦y6≦0.5, preferably 0≦y6≦0.3, 0≦y7≦0.5, preferably 0≦y7≦0.2, and 1.7≦y1+y2+y3+y4≦2.1.

[0182]

[14] In AB type hydrogen storage alloy, A=Ti x1 Zr x2 Y x3 Lax4 、 x1 + x2 + x3 + x4 = 0.85 to 1.1, 0 ≤ x1 ≤ 1.1, preferably 0.90 ≤ x1 ≤ 1.05, 0 ≤ x2 ≤ 1.1, preferably 0 ≤ x2 ≤ 0.5, 0 ≤ x3 ≤ 0.2, preferably 0 ≤ x3 ≤ 0.05, 0 ≤ x4 ≤ 0.2, preferably 0 ≤ x4 ≤ 0.05; B = V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7 、 y1 + y2 + y3 + y4 = 0.95 to 1.05, 0 ≤ y1 ≤ 0.5, preferably 0 ≤ y1 ≤ 0.2, 0 ≤ y2 ≤ 0.8, preferably 0 ≤ y2 ≤ 0.2, 0 ≤ y3 ≤ 0.8, preferably 0.05 ≤ y3 ≤ 0.3, 0 < y4 ≤ 1.05, preferably 0.7 ≤ y4 ≤ 1.05, 0 ≤ y5 ≤ 0.35, preferably 0 ≤ y5 ≤ 0.10, 0 ≤ y6 ≤ 0.45, preferably 0 ≤ y6 ≤ 0.20, 0 ≤ y7 ≤ 0.3, preferably 0 ≤ y7 ≤ 0.2, the method according to configuration

[11] .

[0183] 〔15〕The molecular formula specifically showing the vanadium-based solid solution type hydrogen storage alloy is A x1 B x2 where x1 + x2 = 1, 0.85 ≤ x1 ≤ 0.95, preferably 0.90 ≤ x1 ≤ 0.95, 0.05 ≤ x2 ≤ 0.15, preferably 0.05 ≤ x2 ≤ 0.10; A = Ti y1 V y2 Zr y3 Nb y4 Y y5 La y6 Ca y7 、 y1 + y2 + y3 + y4 + y5 + y6 + y7 = 1, 0 ≤ y1 ≤ 0.9, preferably 0 ≤ y1 ≤ 0.8, 0 ≤ y2 ≤ 0.95, preferably 0 ≤ y2 ≤ 0.95, 0 ≤ y3 ≤ 0.90, preferably 0 ≤ y3 ≤ 0.8, 0 ≤ y4 ≤ 0.55, preferably 0 ≤ y4 ≤ 0.4, 0 ≤ y5 ≤ 0.2, preferably 0.25 ≤ y5 ≤ 0.05, 0 ≤ y6 ≤ 0.1, preferably 0 ≤ y6 ≤ 0.05, 0 ≤ y7 ≤ 0.1, preferably 0 ≤ y7 ≤ 0.05; B = Mn z1 Fe z2 Co z3 Ni z4, z1+z2+z3+z4=1, 0≦z1≦1, preferably 0≦z1≦0.95, 0≦z2≦0.95, preferably 0≦z2≦0.95, 0.7≦z1+z2≦1.0, 0≦z3≦0.3, preferably 0≦z3≦0.2, 0≦z4≦0.45, preferably 0≦z4≦0.3.

[0184]

[16] The method according to configuration [1] or

[11] , wherein the hydrogen storage alloy is a combination of a first hydrogen storage alloy and a second hydrogen storage alloy, the first hydrogen storage alloy being a magnesium-based A2B-type hydrogen storage alloy used for contact with a hydrogen-rich gas, and the second hydrogen storage alloy being a hydrogen storage alloy used for pressurizing the first hydrogen storage hydrogen gas and having a high equilibrium pressure.

[0185]

[17] The method according to the above

[16] , wherein the second hydrogen storage alloy is one or more of rare earth-based AB5 type, zirconium-titanium-based AB2 type, and titanium-based AB type alloys.

[0186]

[18] A method according to configuration [1] or

[16] , in which first, impurities are separated by passing a hydrogen-rich gas through a first hydrogen storage alloy, then the high-purity hydrogen gas released from the first hydrogen storage alloy is contacted with a second hydrogen storage alloy, and then the hydrogen gas is released into the second hydrogen storage alloy under high pressure.

[0187]

[19] The method according to the above feature

[16] , wherein the hydrogen release temperature of the first hydrogen storage alloy is higher than the hydrogen adsorption temperature of the second hydrogen storage alloy, and the temperature difference therebetween is preferably ≧100°C, preferably 350°C≧temperature difference≧150°C.

[0188]

[20] The method of configuration

[16] , wherein the first hydrogen storage alloy and the second hydrogen storage alloy are present in storage tanks of different hydrogen storage alloys, and a heat exchange system is present between the storage tank of the first hydrogen storage alloy and the storage tank of the second hydrogen storage alloy.

[0189]

[21] In the molecular formula specifically showing the first hydrogen storage alloy of the A2B type, A=Mg x1Ca x2 Ti x3 La x4 Y x5 , x1+x2+x3=1.9-2.1, 1.5≦x1≦2.1, preferably 1.70≦x1≦2.05, 0≦x2≦0.5, preferably 0≦x2≦0.2, 0≦x3≦0.8, preferably 0≦x3≦0.50; B=Cr y1 Fe y2 Co y3 Ni y4 Cu y5 Mo y6 , y1+y2+y3+y4+y5+y6=0.9~1.1, 0≦y1≦0.30, preferably 0≦y1≦0.2, 0≦y2≦0.20, preferably 0≦x2≦0.10, 0≦y3≦1.1, preferably 0≦y3≦1, 0≦y4≦1.1, preferably 0≦y4≦1.05, 0≦y5≦0.4, 0≦y6≦0.15, preferably 0≦y6≦0.10; The molecular formula specifically showing the second hydrogen storage alloy of the AB5 type is M m Ni x1 Co x2 Mn x3 Fe x4 Al x5 Sn x6 4.5≦x1+x2+x3+x4+x5+x6≦5.5, 3≦x1≦5.5, preferably 3≦x1≦4.9, 0≦x2≦1.5, preferably 0.1≦x2≦1, 0≦x3≦0.8, preferably 0.1≦x3≦0.6, 0≦x4≦0.8, preferably 0.1≦x4≦0.6, 0≦x5≦0.75, preferably 0≦x5≦0.5, 0≦x6≦0.2, preferably 0≦x6≦0.15; M m includes La, Ce, Pr, Nd and Y, Mm=La y1 Ce y2 Nd y3 Pr y4 Y y5 wherein y1+y2+y3+y4+y5=1, 0.4≦y1≦1, preferably 0.4≦y1≦0.8, 0≦y2≦0.45, preferably 0.1≦y2≦0.45, 0≦y3≦0.2, 0≦y4≦0.05, 0≦y5≦0.05; In the second hydrogen storage alloy of the zirconium-titanium system AB2 type, A=Mg x1 Ca x2 Ti x3 Zr x4 Y x5 La x6 , x1+x2+x3+x4+x5+x6=0.9-1.1, 0≦x1≦1.1, preferably 0.90≦x1≦1.05, 0≦x2≦0.7, preferably 0≦x2≦0.25, 0≦x3≦1.05, preferably 0.8≦x3≦1, 0≦x4≦1.05, preferably 0.85≦x4≦1, 0≦x5≦0.2, preferably 0≦x5≦0.05, 0≦x6≦0.2, preferably 0≦x6≦0.05, and x3 / (x3+x4)≧0.7 or x3 / (x3+x4)≦0.3; B=V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7 , y1+y2+y3+y4+y5+y6+y7=1.9~2.1, 0≦y1≦2.1, preferably 0≦y1≦1.8, 0≦y2≦2.1, preferably 0≦y2≦1.85, 0≦y3≦2.1, preferably 0≦y3≦2.05, 0≦y4≦1.6, preferably 0≦y4≦1.5, 0≦y5≦0.5, preferably 0≦y5≦0.3, 0≦y6≦0.5, preferably 0≦y6≦0.3, 0≦y7≦0.5, preferably 0≦y7≦0.2, and 1.7≦y1+y2+y3+y4≦2.1; In the second hydrogen storage alloy of titanium-based AB type, A=Ti x1 Zr x2 Y x3 La x4 , x1+x2+x3+x4=0.85~1.1, 0≦x1≦1.1, preferably 0.90≦x1≦1.05, 0≦x2≦1.1, preferably 0≦x2≦0.5, 0≦x3≦0.2, preferably 0≦x3≦0.05, 0≦x4≦0.2, preferably 0≦x4≦0.05; B=V y1 Cr y2 Mn y3 Fe y4 Co y5 Ni y6 Cu y7That is, y1 + y2 + y3 + y4 = 0.95 to 1.05, 0 ≤ y1 ≤ 0.5, preferably 0 ≤ y1 ≤ 0.2, 0 ≤ y2 ≤ 0.8, preferably 0 ≤ y2 ≤ 0.2, 0 ≤ y3 ≤ 0.8, preferably 0.05 ≤ y3 ≤ 0.3, 0 < y4 ≤ 1.05, preferably 0.7 ≤ y4 ≤ 1.05, 0 ≤ y5 ≤ 0.35, preferably 0 ≤ y5 ≤ 0.10, 0 ≤ y6 ≤ 0.45, preferably 0 ≤ y6 ≤ 0.20, 0 ≤ y7 ≤ 0.3, preferably 0 ≤ y7 ≤ 0.2, which is the method described in Configuration

[16] or

[17] .

[0190] 〔22〕The temperature in the contact of the hydrogen-rich gas and the first hydrogen storage alloy is 20 to 150 °C, the hydrogen gas partial pressure is 0.001 to 0.1 MPa, the temperature at which hydrogen gas is released from the first hydrogen storage alloy (hydrogen release temperature) is 150 to 450 °C, and the hydrogen gas partial pressure in the hydrogen release is 0.1 to 5 MPa, which is the method described in Configuration

[16] .

[0191] 〔23〕The hydrogen adsorption temperature of the second hydrogen storage alloy is -70 to 100 °C, the hydrogen gas partial pressure in the hydrogen adsorption is 0.1 to 5 MPa, the hydrogen release temperature of the second hydrogen storage alloy is 150 to 450 °C, and the hydrogen partial pressure in the hydrogen release is ≥ 35 MPa, for example, 35 to 100 MPa, which is the method described in Configuration

[16] or

[22] .

[0192] 〔24〕The hydrogen adsorption temperature in the contact of the hydrogen-rich gas and the first hydrogen storage alloy is preferably 50 to 100 °C, the hydrogen gas partial pressure is preferably 0.001 to 0.03 MPa, the hydrogen release temperature of the first hydrogen storage alloy is preferably 200 to 350 °C, and the hydrogen gas partial pressure in the hydrogen release is preferably 0.1 to 1 MPa; the hydrogen adsorption temperature at which the second hydrogen storage alloy adsorbs hydrogen gas is preferably -30 to 100 °C, the hydrogen gas partial pressure in the hydrogen adsorption is preferably 0.1 to 1 MPa, the hydrogen release temperature of the second hydrogen storage alloy is preferably 200 to 350 °C, and the hydrogen partial pressure in the hydrogen release is preferably ≥ 35 MPa, which is the method described in Configuration

[16] or

[22] .

[0193]

[25] The method according to the above item [1], wherein the temperature at which hydrogen gas is released from the hydrogen storage alloy (the temperature at which the hydrogen storage alloy is heated; abbreviated as hydrogen release temperature) is 150 to 450°C, and the pressure of the released hydrogen gas is ≧35 MPa, for example 35 to 100 MPa, in order to obtain high-purity high-pressure hydrogen gas, or the hydrogen gas partial pressure in hydrogen release is 0.1 to 5 MPa in order to obtain high-purity hydrogen gas, and the hydrogen release temperature is higher than the hydrogen adsorption temperature.

[0194]

[26] The method according to the above aspect [1], for example, removing organic matter in a hydrogen-containing alloy by a purging method using hydrogen gas, for example, the purging method including stopping the supply of hydrogen-rich gas to the hydrogen-absorbing alloy after a predetermined amount of adsorption in the hydrogen-absorbing alloy is reached, and passing hydrogen gas through the hydrogen-containing alloy to expel organic gas in the hydrogen-containing alloy and (also called the storage vessel of the hydrogen-absorbing alloy), and introducing the organic gas into a storage tank for storage, or adsorbing the organic gas to a hydrogen-absorbing alloy in a storage vessel of another hydrogen-absorbing alloy, and the purity of the hydrogen gas for purging is preferably more than 90% by weight, more preferably more than 95% by weight, for example more than 99% by weight.

[0195]

[27] The method according to the above aspect [1], wherein the reaction temperature in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 150 to 450°C, preferably 200 to 400°C, and more preferably 300 to 350°C.

[0196]

[28] The weight hourly space velocity in the contact between the liquid organic hydrogen storage material and the dehydrogenation catalyst is 0.5 to 50 h -1 , preferably 1 to 45 hours -1 , more preferably 2 to 30 hours -1 The method according to configuration [1],

[0197]

[29] The method according to the above aspect [1], wherein the pressure in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 0.03 to 5 MPa or 0.3 to 5 MPa, preferably 0.1 to 3 MPa, for example, 0.5 to 2 MPa or 0.2 to 1.6 MPa.

[0198]

[30] The method according to the above-mentioned configuration [1], wherein when a mixture of the liquid organic hydrogen storage raw material and hydrogen gas is contacted with a dehydrogenation catalyst, the hydrogen to hydrocarbon ratio (the molar ratio of hydrogen gas to the liquid organic hydrogen storage raw material) is 0 to 10.

[0199]

[31] Dehydrogenation of organic liquid in the presence or absence of hydrogen gas. The temperature in the dehydrogenation of organic liquid is 150 to 450°C, and the weight space velocity per hour is 0.5 to 50 h -1 The reaction pressure is 0.3 to 5 MPa, the hydrogen to hydrocarbon ratio is 0 to 10 molar ratio, and preferably the reaction temperature is 200 to 400°C, and the hourly weight space velocity is 1 to 30 h -1 and the hydrogen to hydrocarbon ratio is 0 to 8 molar ratio.

[0200]

[32] The dehydrogenation catalyst is a metal-supported catalyst, which comprises a support and a supported active metal component, the support, the active metal preferably comprises one or more metals selected from the group VIII metals, more preferably the active metal component comprises a first active metal and optionally a second active metal, the first active metal being one or more of Pt, Pd, Ru, Rh and Ir, the second active metal being one or more of Ni, Re, Sn, Mo, Cu, Fe, Ca, Co and W, preferably the second active metal being one or more of Ni, Re and Sn, more preferably the first active metal being Pt; Or, The method of claim 1, wherein the dehydrogenation catalyst comprises a support and a supported active metal component, the support being selected from one or more of alumina, silicon dioxide, titanium dioxide, zirconium oxide, activated carbon, and silicoaluminum materials, the active metal being selected from at least two metals of Ni, Zn, Sn, Cu, Fe, Ag, p, In, Re, Mo, Co, Ca, and W, more preferably two or more of Ni, Zn, Sn, and Cu, or the active metal comprises Ni and one or more selected from Zn, Sn, Cu, Fe, Ag, p, In, Re, Mo, Co, Ca, and W.

[0201]

[33] The method according to

[32] , wherein in the dehydrogenation catalyst, the mass fraction of the support is 70 to 99.9%, and the mass fraction of the metal component is 0.1 to 30%.

[0202]

[34] The method according to claim [1], wherein the dehydrogenation catalyst comprises a support and an active metal component, the support is a support composition, the support composition comprises alumina and a modifying metal oxide, the modifying metal oxide is titanium oxide and / or zirconium oxide, and the modifying metal oxide has η<0.3, and η=wt% content of the crystalline phase of the modifying metal oxide in the support composition / wt% content of the chemical composition of the modifying metal oxide in the support composition; the titanium oxide is calculated as TiO2 and the zirconium oxide is calculated as ZrO2.

[0203]

[35] The method of claim

[34] , wherein the support composition has η=0, and preferably the first metal oxide is dispersed as a monolayer on the alumina substrate.

[0204]

[36] The method according to the above-mentioned configuration

[34] , wherein in the support composition, the mass fraction of alumina is 80 to 98.5%, preferably 83 to 97.5%, 85 to 95% or 90 to 95%, and the mass fraction of the modifying metal oxide is 1.5 to 20%, preferably 2.5 to 17%, 5 to 15% or 5 to 10%.

[0205]

[37] The method according to the above aspect

[34] , wherein the modified metal oxide comprises titanium oxide, and preferably, in the carrier composition, the mass fraction of titanium dioxide is preferably 2 to 20%, for example 5 to 15%, or 5 to 10%, or 2.5 to 17%, and the mass fraction of zirconium dioxide is preferably 0 to 8%, for example 0 to 6%, or 0 to 3%, or 1 to 6%.

[0206]

[38] In comparison with the pure phase of TiO2, the XPS spectra of the support composition show that the Ti 2P 3 / 2 There is a shift in the orbital electron binding energy, and the peak at 458.8 eV of the binding energy shifts by 0.6 to 0.7 eV to the high binding energy side to 459.4 to 459.5 eV, and / or Ti 2P 1 / 2The method according to the above-mentioned configuration

[34] , wherein the peak of the orbital electron binding energy at 464.5 eV is shifted by 0.8 to 0.9 eV to the high binding energy side to 465.3 to 465.4 eV.

[0207]

[39] The method according to the structure

[34] , wherein the oxide substrate has at least one phase structure of γ-alumina, η-alumina, ρ-alumina or χ-alumina.

[0208]

[40] The specific surface area of ​​the carrier composition is 100 to 350 m 2 The method according to claim 34, wherein:

[0209]

[41] The method according to

[34] , wherein the pore volume of the carrier composition is 0.3 to 1.3 ml / g.

[0210]

[42] The method according to the above-mentioned configuration [1] or

[34] , wherein the dehydrogenation catalyst comprises a support comprising alumina and a modifying metal oxide, and an active metal component, the modifying metal oxide being titanium oxide and / or zirconium oxide, and the active metal component being an oxide of the active metal and / or an elemental active metal. The active metal is, for example, one or more of a Group VIIIB metal, a Group VIIB metal, a Group VB metal, a Group VIB metal, a Group IB metal, a rare earth element, an alkaline earth metal, and a Group IVA metal; Preferably, the active metal comprises Pt and / or Ni, and optionally other elements, preferably one or more of V, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Mo, Sn, Ca, Pt, Pd, Ru, Re, Rh, Ir, Os, Zn, P and In.

[0211]

[43] The method of claim

[42] , wherein the active metal comprises Pt and optionally other metals, which may be precious or non-precious metals, and which are one or more of Pd, Ru, Re, Rh, Ir, Os, Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca.

[0212]

[44] The method according to the above aspect

[42] , wherein the dehydrogenation catalyst has an active metal content of 0.1 to 20% by weight, for example, 0.1 to 15% by weight, a support content of 75 to 99.9% by weight, and a Pt content of 0.1 to 10% by weight. In the composition of the dehydrogenation catalyst of the present invention, the active metal content is calculated as a simple substance for noble metals and as an oxide for non-noble metals.

[0213]

[45] The method according to the structure

[43] , wherein the other metal is one or more of Pd, Ru, Re, Rh, Ir and Os.

[0214]

[46] The method according to the above-mentioned configuration

[43] , wherein the content of the active metal in the dehydrogenation catalyst is 0.1 to 10% by weight, preferably 0.5 to 8% by weight, and the content of the support is 90 to 99.9% by weight, preferably 92 to 99.5% by weight.

[0215]

[47] The method according to the above-mentioned configuration

[43] , wherein the content of Pt in the catalyst is 0.1 to 2 wt%, for example, 0.3 to 1.5 wt%, or 0.5 to 1 wt%, the content of the other metal is 0 to 9.9 wt%, for example, 0.1 to 2, or 0.2 to 1 wt%, or 0.1 to 0.8 wt%, and the content of the support is preferably 90 to 99.9 wt%, for example, 96 to 99.6 wt%, or 98 to 99.5 wt%, or 98.5 to 99.3 wt%.

[0216]

[48] ​​The method according to the structure

[43] , wherein the other metal elements are one or more of Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu and Ca.

[0217]

[49] The method according to the above aspect

[43] , wherein the content of Pt in the catalyst is 0.1 to 10% by weight, and the content of the other metal is 0 to 15% by weight.

[0218]

[50] The method according to the above item

[43] , wherein the catalyst has a Pt content of 0.1 to 2% by weight, for example, 0.5 to 1.5% by weight, a content of other metals of 0 to 15% by weight, for example, 1 to 10% by weight, or 2 to 8% by weight, or 3 to 7% by weight, and a content of the support of 85 to 99.9% by weight, for example, 90 to 99% by weight, or 90 to 98% by weight, or 92 to 97% by weight.

[0219]

[51] The method of claim

[34] , wherein the active metal comprises nickel and optionally other metals, the other metals being one or more of Zn, Sn, Cu, Fe, Ag, P, In, Re, Mo, Co, Ca and W.

[0220]

[52] The method according to the above-mentioned configuration

[51] , wherein in the catalyst, the mass fraction of the active metal is 5% to 30%, and the mass fraction of the support is 70 to 95%, preferably the mass fraction of the support is 75 to 90%, and the mass fraction of the active metal is preferably 10% to 25%.

[0221]

[53] The method according to the above item

[51] , wherein the content of nickel (calculated as oxide) in the catalyst is 5 to 25% by weight, preferably 6 to 20% by weight, for example 7 to 15% by weight, or 7 to 12% by weight, or 8 to 11% by weight, and the content of other metals (calculated as oxides) is 0 to 15% by weight, preferably 0 to 10% by weight, for example 0.5 to 8% by weight or 1 to 5% by weight.

[0222]

[54] The method according to the configuration [1], wherein the liquid organic hydrogen storage raw material is a saturated and / or unsaturated hydrocarbon containing a cycloalkane ring and optionally containing a heteroatom, and the hydrogen storage organic compound containing a heteroatom is an organic substance obtained by heteroatom substitution on the cycloalkane ring of a hydrocarbon containing a cycloalkane ring. Among them, the liquid organic hydrogen storage raw material is preferably a saturated or unsaturated hydrocarbon containing a cycloalkane ring but not a hetero ring atom. More preferably, the liquid organic hydrogen storage raw material is a saturated or unsaturated hydrocarbon containing no hetero ring atom and in which the sum of the number of aromatic rings and the number of cycloalkane rings is 2 or less; Even more preferably, the organic hydrogen storage raw material is a saturated or unsaturated hydrocarbon that does not contain a hetero ring atom and has a total number of rings of an aromatic ring and a cycloalkane ring of 2 or less, the saturated or unsaturated hydrocarbon that does not contain a hetero ring atom and has a cycloalkane ring includes one or more of cyclohexane, methylcyclohexane, decahydronaphthalene, and bi(cyclohexane), and the saturated or unsaturated hydrocarbon that contains a hetero atom and has a cycloalkane ring includes a nitrogen-containing heterocyclic compound and a nitrogen / boron-containing heterocyclic compound. For example, nitrogen-containing heterocyclic compounds include one or more of decahydrocarbazole, dodecahydroethylcarbazole, indoline, 4-aminopiperidine, piperidine-4-carboxamide, perhydro-4,7-phenanthroline, 2-methyl-1,2,3,4-tetrahydroquinoline, 2,6-dimethyldecahydro-1,5-naphthyridine, and nitrogen / boron heteroatom-containing unsaturated hydrocarbons include one or more of 1,2-BN-cyclohexane, and 3-methyl-1,2-BN-cyclopentane.

[0223]

[55] The method according to configuration [1], further comprising a step of introducing the released hydrogen gas into a hydrogen gas storage tank to store the hydrogen gas, or a step of allowing the obtained high purity high pressure hydrogen gas to be used directly for refueling a hydrogen fuel cell vehicle.

[0224]

[56] A step of carrying out a dehydrogenation reaction of a liquid organic hydrogen storage raw material in a dehydrogenation reactor in the presence of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas; cooling and separating the dehydrogenation reaction product in a cooling separation unit to obtain a hydrogen-rich stream and an organic liquid; contacting the hydrogen-rich stream or the purified hydrogen-rich stream with a hydrogen-absorbing alloy in a hydrogen-absorbing alloy containment vessel to obtain a hydrogen-containing alloy; A step of removing organic matter from within a hydrogen storage alloy containment vessel by a purging method using hydrogen gas, preferably with a hydrogen gas for purging having a purity of more than 90% by weight, more preferably more than 95% by weight; a step of heating the hydrogen-containing alloy to release hydrogen gas, thereby obtaining high-pressure hydrogen gas, and supplying the obtained high-pressure hydrogen gas to a hydrogen consumption device or a high-pressure hydrogen gas storage tank for storage; A highly efficient distributed method for producing high-purity high-pressure hydrogen gas, comprising:

[0225]

[57] A high-purity high-pressure hydrogen gas supply system, comprising: a liquid organic hydrogen storage raw material storage-supply device for storing the liquid organic hydrogen storage raw material and supplying the liquid organic hydrogen storage raw material to the dehydrogenation reactor; a dehydrogenation liquid storage device for storing a liquid product obtained by dehydrogenating the liquid organic hydrogen storage raw material; a dehydrogenation reactor device for performing a dehydrogenation reaction of a liquid organic hydrogen storage raw material under the action of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas; a cooling and separating unit for separating the dehydrogenation reaction product to obtain a hydrogen-rich gaseous product and a liquid product; a hydrogen storage / hydrogen supply device that includes a hydrogen storage alloy storage vessel and a hydrogen storage alloy heating system, and that absorbs hydrogen by contacting a hydrogen-rich gas with the hydrogen storage alloy at low temperature and pressure and then dehydrogenating the hydrogen by heating after the hydrogen absorption is saturated; Optionally, a purge device used to remove organic matter from within the hydrogen storage container; a hydrogen gas supplying device that supplies high-pressure hydrogen gas to a hydrogen consuming device or a hydrogen gas storage tank.

[0226]

[58] The system described in configuration

[57] , wherein the system is installed in a hydrogen refueling station as a container-type hydrogen production system integrated into the interior of a container, or is directly incorporated into the hydrogen refueling station for use.

[0227]

[59] The system described in configuration

[57] , wherein the hydrogen storage-hydrogen supply device includes one or more hydrogen storage alloy storage containers, and the multiple hydrogen storage alloy storage containers may be connected in a parallel configuration, a series configuration, or a combination of parallel and series configurations.

[0228]

[60] The system according to any one of the configurations

[57] to

[59] , wherein at least one hydrogen storage alloy storage vessel is a high-pressure vessel and / or the hydrogen gas supply device is a high-pressure device. Preferably, the allowable pressure of the device is 35 MPa or more.

[0229]

[61] A mobile hydrogen supply system comprising a transportation vehicle and a high-purity hydrogen gas supply system according to any one of the configurations

[57] to

[60] installed on the transportation vehicle.

[0230]

[62] A distributed hydrogen supply device comprising the high-purity hydrogen gas supply system according to any one of the configurations

[57] to

[60] , and optionally comprising a high-pressure hydrogen gas storage tank.

[0231] [Example] The following examples further illustrate the invention without, however, limiting it.

[0232] (Ingredients and measurement methods) SB powder: manufactured by Sasol, Germany, solid content 75% by weight.

[0233] P25 (titanium dioxide): manufactured by Degussa, Germany, solid content 98% by weight.

[0234] Metallates and metal salts were purchased from Sinopharm Chemical Reagents Beijing Co., Ltd.

[0235] Liquid organic hydrogen storage materials were purchased from J&K Scientific Co., Ltd.

[0236] In each of the examples and comparative examples, the composition of the dehydrogenation catalyst for the supported organic liquid was measured by X-ray fluorescence analysis, and the dehydrogenation product of the liquid organic hydrogen storage raw material was obtained by chromatography analysis. The purity of the hydrogen gas was analyzed by gas chromatography.

[0237] In the examples and comparative examples of the present invention, the dehydrogenation tests of organic liquids were carried out in a fixed bed reactor.

[0238] For separation, a coolant was used for cooling and separation. The hydrogen storage vessel was connected after the separation system, and the energy transfer medium was hot water or hot steam, and the steam was generated by a steam generator.

[0239] In the following examples, in the preparation of the support for the dehydrogenation catalyst of the liquid organic hydrogen storage feedstock, the percentage content of the crystalline phase of the modified metal oxide was measured by the following method: All X-ray diffraction measurements were performed using a Philips XRG3100 generator with a long fine focus copper X-ray source driven at 40 kV and 30 mA, a Philips 3020 digital goniometer, a Philips 3710 MPD control computer, and a Kevex PSI Peltier cooled silicon detector; the Kevex detector was operated using a Kevex 4601 ion pump controller, a Kevex 4608 Peltier power supply, a Kevex 4621 detector bias, a Kevex 4561A pulse processor, and a Kevex 4911-A single channel analyzer; the diffraction patterns were obtained using Philips APD 4.1C version software; all Rietveld calculations were performed using Material Data, Inc., Riqas 3.1C version software (Qutokumpu HSC Chemistry for Windows; User Guide, Qutokumpo Research Oy, Pori, Finland (1999)).

[0240] In the following examples, XPS tests were performed using an ESCALab250 X-ray photoelectron spectrometer manufactured by Thermo Fisher Scientific. The excitation source was a monochromated AlK α X-rays. The transmission energy in the narrow scan was 30 eV. The basic vacuum during the analysis was about 6.5×10 -10The pressure was 1000 psi (mbar). The binding energy was calibrated by the C1s peak of contaminating carbon (284.8 eV). The weight percent content of the modified metal oxide on the surface of the support composition was determined by measuring 10 sample particles and taking the average value.

[0241] In the following examples, the specific surface area and pore volume were measured by static low-temperature adsorption volume method (method conforming to GB / T5816-1995) using an automatic adsorption device ASAP2400 manufactured by Micromeritics Instruments, USA. The specific method was as follows: the test sample was evacuated at 250°C and 1.33 Pa for 4 hours, degassed, and then contacted with nitrogen gas, which is an adsorbent, at -196°C until static adsorption reaches adsorption equilibrium; the amount of nitrogen adsorbed by the adsorbent was calculated from the difference between the amount of nitrogen gas introduced and the amount of nitrogen gas remaining in the gas phase after adsorption, and the specific surface area and pore volume were calculated by the BET formula.

[0242] <Preparation of carrier for dehydrogenation catalyst of liquid organic hydrogen storage material> (Carrier Example 1) The SB powder was sintered at 500°C for 4 hours to obtain γ-Al2O3. The specific surface area of ​​γ-Al2O3 is 176 m 2 / g and the pore volume was 0.48 mL / g.

[0243] The above γ-Al2O3 (500 g) was placed in a fluidized reactor (reactor inner diameter: 10 cm, height: 40 cm). Titanium tetrachloride was placed in a constant temperature bath at 20°C, and nitrogen gas (temperature: 25°C) was introduced into the fluidized reactor from the bottom while passing it through titanium tetrachloride at a flow rate of 10 L / min. After fluidization for 1 hour, the introduction of nitrogen gas into the titanium tetrachloride bath was stopped. Nitrogen gas (temperature: 25°C) was introduced into the fluidized reactor from the bottom while being introduced into deionized water placed in a constant temperature bath at 50°C at a flow rate of 10 L / min. Fluidization was carried out for 4 hours to hydrolyze the mixture, and a hydrolyzed support was obtained. The hydrolyzed support was calcined in an air atmosphere at 550°C for 4 hours to obtain a final support. The final support is referred to as support 1. The composition and properties of the support are shown in Table 1, and the X-ray diffraction (XRD) spectrum is shown in FIG.

[0244] (Carrier Examples 2 to 8) Carriers 2 to 8 were prepared in the same manner as Carrier 1 in Carrier Example 1, except that the time for introducing titanium tetrachloride carried by nitrogen gas into the fluidized bed and the time for hydrolysis by introducing nitrogen gas into deionized water were different. The preparation conditions, composition, and properties of the carriers are shown in Table 1.

[0245] (Carrier Examples 9 to 11) Carriers 9 to 11 were prepared in the same manner as Carrier 1 in Carrier Example 1, except that nitrogen gas was first passed through titanium tetrachloride and then through a zirconium tetrachloride vapor generator (zirconium tetrachloride vapor temperature: 300° C.). The preparation conditions, composition, and properties of the carriers are shown in Table 1.

[0246] (Comparative Carrier Example 1) The SB powder was calcined at 500°C for 4 hours to obtain γ-Al2O3 directly. The support was named support C1. The composition and properties of the support were shown in Table 1.

[0247] (Comparative Carrier Example 2) A support was prepared by referring to the method of support example 1, except that γ-Al2O3 obtained by calcining SB powder at 500°C for 4 hours was physically mixed with TiO2. This support is called support C2. The composition and properties of the support are shown in Table 1, and the X-ray diffraction (XRD) spectrum is shown in Figure 1 as "2".

[0248] (Comparative Carrier Example 3) A carrier was prepared with reference to Comparative Carrier Example 2. This carrier is called Carrier C3. The composition and properties of the carrier are shown in Table 1.

[0249] (Comparative Carrier Example 4) A support was prepared by referring to the method of support example 6, except that the support, γ-Al2O3, obtained by calcining SB powder at 500°C for 4 hours was physically mixed with titanium tetrachloride solution. The support is called support C4. The composition of the support and the properties of the support are shown in Table 1.

[0250] (Comparative Carrier Example 5) The SB powder was calcined at 500°C for 4 hours to obtain γ-Al2O3. Tetrabutyl titanate and deionized water were mixed by stirring for 30 minutes, and impregnated into γ-Al2O3 by equal volume impregnation. The mixture was dried and calcined at 550°C for 4 hours to obtain an oxide composite support. This support is called support C5. The composition and properties of the support are shown in Table 1, and the X-ray diffraction (XRD) spectrum is shown as "5" in Figure 1.

[0251] (Comparative Carrier Example 6) A support was prepared according to the formulation of Support Example 9, except that γ-Al2O3 obtained by calcining SB powder at 500°C for 4 hours was physically mixed with TiO2 and ZrO2. The support was designated as Support C6. The support composition and support properties were shown in Table 1.

[0252] (Comparative Carrier Example 7) A carrier was prepared with reference to Comparative Carrier Example 6. This carrier is called Carrier C7. The composition and properties of the carrier are shown in Table 1.

[0253] The properties of each of the supports prepared in Support Examples 1 to 11 and Support Comparative Examples 1 to 7 are shown in Table 1.

[0254] <Preparation and evaluation of dehydrogenation catalysts for liquid organic hydrogen storage materials> Example 1 0.34g of chloroplatinic acid was added to water to prepare 20mL of impregnation solution. The impregnation solution was slowly added to 19.84g of carrier 1 while stirring, and the impregnation solution was uniformly supported on the oxide composite carrier. The impregnation temperature was 25°C, and the solid after impregnation was dried for 3 hours by purging with nitrogen gas at 120°C. Then, it was calcined in an air atmosphere. The calcination temperature was 600°C, the gas-to-carrier ratio (air / solid volume ratio) during calcination was 600:1, and the calcination time was 4 hours, and finally a catalyst was obtained. The composition of the catalyst is shown in Table 2.

[0255] The dehydrogenation reaction of methylcyclohexane was carried out in a fixed-bed reactor, and the catalyst prepared above was evaluated. The dehydrogenation reaction was carried out in a fixed-bed microreactor. The conditions for evaluation were reaction temperature of 350°C, reaction pressure (pressure at the inlet of the reactor) of 1 MPa, flow rate of additional hydrogen gas of 150 mL / min H2, methylcyclohexane supply amount of 2 mL / min, and catalyst loading amount of 20 g. The evaluation results of the catalyst are shown in Table 2. Note that conversion rate = reacted methylcyclohexane / total methylcyclohexane supply amount; selectivity = methylcyclohexane that produced toluene / reacted methylcyclohexane.

[0256] Example 5 In the same manner as in Example 1, chloroplatinic acid and nickel nitrate were added to water to prepare 20 mL of impregnation solution. The impregnation solution was slowly added to 19.7 g of carrier 1 while stirring, and the impregnation solution was uniformly supported on the oxide composite carrier. The impregnation temperature was 25°C, and the solid after impregnation was dried for 3 hours by purging with nitrogen gas at 120°C. Then, it was calcined in an air atmosphere. The calcination temperature was 600°C, the gas-to-carrier ratio (air / solid volume ratio) during calcination was 600:1, and the calcination time was 4 hours, and a catalyst was finally obtained. The composition of the catalyst is shown in Table 2.

[0257] The dehydrogenation reaction of methylcyclohexane was carried out in a fixed-bed reactor, and the catalyst prepared above was evaluated. The dehydrogenation reaction was carried out in a fixed-bed microreactor. The conditions for evaluation were reaction temperature 350°C, reaction pressure (pressure at the inlet of the reactor) 1MPa, flow rate of additional hydrogen gas 150mL / minH2, methylcyclohexane feed rate 2.5mL / min, and catalyst loading 20g. The evaluation results of the catalyst are shown in Table 2. Note that conversion rate = reacted methylcyclohexane / total methylcyclohexane feed rate; selectivity = methylcyclohexane that produced toluene / reacted methylcyclohexane.

[0258] Example 10 Nickel nitrate and tin chloride were added to water to prepare 20 mL of impregnation solution. The impregnation solution was slowly added to 17.8 g of support 1 while stirring, and the impregnation solution was uniformly supported on the oxide composite support. The impregnation temperature was 25°C, and the solid after impregnation was dried under nitrogen purge at 120°C for 3 hours. Then, it was calcined in an air atmosphere. The calcination temperature was 600°C, the gas-to-support ratio (air / solid volume ratio) during calcination was 600:1, and the calcination time was 4 hours, and finally a catalyst was obtained. The composition of the catalyst is shown in Table 2.

[0259] The dehydrogenation reaction of methylcyclohexane was carried out in a fixed-bed reactor, and the catalyst prepared above was evaluated. The dehydrogenation reaction was carried out in a fixed-bed microreactor. The conditions for evaluation were reaction temperature 400°C, reaction pressure (pressure at the inlet of the reactor) 1MPa, flow rate of additional hydrogen gas 150mL / minH2, methylcyclohexane feed rate 1.0mL / min, and catalyst loading 20g. The catalyst evaluation results are shown in Table 2. Note that conversion rate = reacted methylcyclohexane / total methylcyclohexane feed rate; selectivity = methylcyclohexane that produced toluene / reacted methylcyclohexane.

[0260] (Examples 2, 4, 7-9, and 12-39, and Comparative Examples 1-17) Catalysts were prepared using the impregnation method according to Examples 1, 5, or 10. The catalyst formulations are shown in Table 2. Supports were calculated on a dry basis (calcined at 800° C. for 1 hour), platinum (Pt) was calculated on a dry basis, palladium (Pd) was calculated on a dry basis, iridium (Ir) was calculated on a dry basis, rhenium (Re) was calculated on a dry basis, nickel (Ni) was calculated as NiO, tin (Sn) was calculated as SnO2, zinc (Zn) was calculated as ZnO, copper (Cu) was calculated as CuO, iron (Fe) was calculated as Fe2O3, silver (Ag) was calculated as AgO, phosphorus (P) was calculated as P2O5, and manganese (Mn) was calculated as MnO2.

[0261] The prepared catalyst was evaluated according to the evaluation method of Examples 1, 5, or 10. The evaluation conditions were a reaction pressure (pressure at the inlet of the reactor) of 1 MPa and a catalyst loading of 20 g. The reaction temperature, the flow rate of additional hydrogen gas, and the amount of methylcyclohexane fed are shown in Table 2.

[0262] (Examples 3, 6, and 11) The catalysts of Examples 3, 6, and 11 were prepared in the same manner as in Examples 2, 5, and 10, except that the impregnated solid was frozen at -45°C for 10 hours, then dried at -5°C under a vacuum condition of 0.1 atm (absolute pressure), and then calcined.

[0263] The prepared catalyst was evaluated according to the evaluation method of Example 1. The conditions for evaluation were a reaction pressure (pressure at the inlet of the reactor) of 1 MPa and a catalyst loading of 20 g. The reaction temperature, the flow rate of additional hydrogen gas, and the amount of methylcyclohexane supplied are shown in Table 2.

[0264] The dehydrogenation catalyst provided by the present invention can have higher conversion activity than the dehydrogenation catalyst prepared by the conventional method. Under similar reaction conditions, the dehydrogenation catalyst has a higher hydrogen gas production rate. The use of freezing and vacuum drying methods improves the activity and selectivity of the catalyst, and increases the hydrogen gas production rate.

[0265] <Preparation and evaluation of hydrogen storage alloys> (Hydrogen Storage Alloy Examples 1 to 13 and C1 to C4) According to the alloy composition, a total of about 1000 g of metal was weighed out, placed in a water-cooled crucible of an induction heating vacuum melting furnace, and melted under vacuum to obtain an alloy. The preparation conditions included the following: 1×10 -4 Melting was carried out at the melting temperatures and times shown in Table 3 under a background vacuum of 1×10 Pa; -4 The temperature was lowered to the annealing temperature at a rate of 10° C. / min under a background vacuum of 1×10 Pa, and annealing was performed at the annealing temperature and time shown in Table 3. -4 The alloys were naturally cooled to room temperature under a background vacuum of 0.1 Pa; the obtained alloys were crushed and sieved to obtain metal powders of 70 to 200 mesh; the powders were placed in a hydrogen storage tank, which was heated to 300°C under a vacuum of 0.1 Pa and kept at that temperature for 4 hours to activate the alloy powders, thereby obtaining hydrogen storage alloys 1 to 13 and C1 to C4.

[0266] 1 kg of hydrogen storage alloy was placed in a hydrogen storage tank, and organic matter-containing hydrogen gas (methane content 0.01% by volume) at 20°C was introduced into the hydrogen storage tank as a model compound. Hydrogen gas was reacted with the hydrogen storage alloy to form a hydrogen-containing alloy. When the hydrogen storage capacity of the hydrogen storage alloy reached 75% of the theoretical capacity, the introduction of the organic matter-containing hydrogen gas was stopped, and purging was performed for 20 minutes using hydrogen gas with a purity of 95%. The hydrogen storage tank was then heated, and the hydrogen storage alloy was maintained under 50 MPa, and continuous hydrogen release was performed. The purity of the hydrogen gas was analyzed by gas chromatography. The purity of the hydrogen gas, the cumulative hydrogen storage capacity, and the decay rate of the hydrogen storage capacity are shown in Table 3. The cumulative hydrogen storage capacity refers to the total hydrogen absorption capacity for 30 times. After the above-mentioned hydrogen absorption and hydrogen release were repeated 30 times, the decay rate of the hydrogen storage capacity was measured. Decay rate = (amount of hydrogen absorbed in the first hydrogen absorption / release - amount of hydrogen absorbed in the 30th hydrogen absorption / release) / amount of hydrogen absorbed in the first hydrogen absorption / release × 100%

[0267] (Hydrogen Storage Alloy Examples 14 to 26 and C5 to C10) According to the alloy composition, a total of about 1000 g of metal was weighed out, placed in a water-cooled crucible of an induction heating vacuum melting furnace, and melted under vacuum to obtain an alloy. The preparation conditions included the following: 1×10 -4 Melting was carried out at the melting temperatures and times shown in Table 3 under a background vacuum of 1×10 Pa; -4 The temperature was lowered to the annealing temperature at a rate of 10° C. / min under a background vacuum of 1×10 Pa, and annealing was performed at the annealing temperature and time shown in Table 3. -4 The alloys were naturally cooled to room temperature under a background vacuum of 0.1 Pa; the obtained alloys were crushed and sieved to obtain metal powders of 70 to 200 mesh; the powders were placed in a hydrogen storage tank, which was heated to 300°C under a vacuum of 0.1 Pa and kept at 300°C for 4 hours to activate the alloy powders, thereby obtaining hydrogen storage alloys 14 to 26 and C5 to C10.

[0268] 1 kg of hydrogen storage alloy was placed in a hydrogen storage tank, and organic matter-containing hydrogen gas (methane content 0.05% by volume) at 10°C was introduced into the hydrogen storage tank as a model compound. Hydrogen gas was reacted with the hydrogen storage alloy to form a hydrogen-containing alloy. When the hydrogen storage capacity of the hydrogen storage alloy reached 75% of the theoretical capacity, the introduction of the organic matter-containing hydrogen gas was stopped, and hydrogen gas with a purity of 98% or more was used for 20 minutes to purge. The hydrogen storage tank was then heated, the hydrogen storage alloy was maintained under 35 MPa, and continuous hydrogen release was performed. The purity of the hydrogen gas was analyzed by gas chromatography. The purity of the hydrogen gas, the cumulative hydrogen storage capacity, and the decay rate of the hydrogen storage capacity are shown in Table 3. The cumulative hydrogen storage capacity refers to the total hydrogen absorption capacity for 10 times. After the above-mentioned hydrogen absorption and hydrogen release were repeated 10 times, the decay rate of the hydrogen storage capacity was measured. Decay rate = (amount of hydrogen absorbed in the first hydrogen absorption / release - amount of hydrogen absorbed in the 10th hydrogen absorption / release) / amount of hydrogen absorbed in the first hydrogen absorption / release × 100%

[0269] (Hydrogen Storage Alloy Examples 27 to 40 and C11 to C14) According to the alloy composition, a total of about 1000 g of metal was weighed out, placed in a water-cooled crucible of an induction heating vacuum melting furnace, and melted under vacuum to obtain an alloy. The preparation conditions included the following: 1×10 -4 Melting was carried out at the melting temperatures and times shown in Table 3 under a background vacuum of 1×10 Pa; -4 The temperature was lowered to the annealing temperature at a rate of 10° C. / min under a background vacuum of 1×10 Pa, and annealing was performed at the annealing temperature and time shown in Table 3. -4 The alloys were naturally cooled to room temperature under a background vacuum of 0.1 Pa; the obtained alloys were crushed and sieved to obtain metal powders of 70 to 200 mesh; the powders were placed in a hydrogen storage tank, which was heated to 300°C under a vacuum of 0.1 Pa and kept at 300°C for 4 hours to activate the alloy powders, thereby obtaining hydrogen storage alloys 27 to 40 and C11 to C14.

[0270] 1 kg of hydrogen storage alloy was placed in a hydrogen storage tank, and organic matter-containing hydrogen gas (methane content 0.1% by volume) at 20°C was introduced into the hydrogen storage tank at a pressure of 5 MPa as a model compound. Hydrogen gas was reacted with the hydrogen storage alloy to form a hydrogen-containing alloy. When the hydrogen storage capacity of the hydrogen storage alloy reached 75% of the theoretical capacity, the introduction of the organic matter-containing hydrogen gas was stopped, and purging was performed for 20 minutes using hydrogen gas with a purity of 95%. The hydrogen storage tank was then heated to maintain the hydrogen storage alloy under 20 MPa, and continuous hydrogen release was performed. The purity of the hydrogen gas was analyzed by gas chromatography. The purity of the hydrogen gas, the cumulative hydrogen storage capacity, and the decay rate of the hydrogen storage capacity are shown in Table 3. The cumulative hydrogen storage capacity refers to the total hydrogen absorption capacity for 10 times. After the above-mentioned hydrogen absorption and hydrogen release were repeated 10 times, the decay rate of the hydrogen storage capacity was measured. Decay rate = (amount of hydrogen absorbed in the first hydrogen absorption / release - amount of hydrogen absorbed in the 10th hydrogen absorption / release) / amount of hydrogen absorbed in the first hydrogen absorption / release × 100%

[0271] (Hydrogen Storage Alloy Examples 41 to 56 and C15 to C19) According to the alloy composition, a total of about 1000 g of metal was weighed out, placed in a water-cooled crucible of an arc melting furnace, and melted under an argon atmosphere to obtain an alloy. The specific preparation includes the following: Melting was performed under a high-purity Ar atmosphere (purity 99.999%) at the melting temperature, pressure, and time shown in Table 3; 1×10 -4 The temperature was lowered to an annealing temperature of 650°C at a rate of 10°C / min under a background vacuum of 0.1 Pa, and annealed at the annealing temperature for 48 hours; the alloy was naturally cooled to room temperature under vacuum; the obtained alloy was crushed and sieved to obtain metal powder of 70 to 200 mesh; the powder was placed in a hydrogen storage tank, and the hydrogen storage tank was heated to 300°C under a vacuum of 0.1 Pa and kept at that temperature for 4 hours to activate the alloy powder, and hydrogen storage alloys 41 to 56 and C15 to C19 were obtained.

[0272] 1 kg of hydrogen storage alloy was placed in a hydrogen storage tank, and organic matter-containing hydrogen gas (methane content 0.1% by volume) at 20°C was introduced into the hydrogen storage tank as a model compound at a pressure of 2 MPa. To form a hydrogen-containing alloy, hydrogen gas was reacted with the hydrogen storage alloy, and when the hydrogen storage capacity of the hydrogen storage alloy reached 75% of the theoretical capacity, the introduction of the organic matter-containing hydrogen gas was stopped, and the pressure was reduced for 5 minutes at 80°C using a vacuum pump. The hydrogen storage tank was then heated, and the hydrogen storage alloy was maintained under 0.1 MPa, and continuous hydrogen release was performed. The purity of the hydrogen gas was analyzed by gas chromatography. The purity of the hydrogen gas, the cumulative hydrogen storage capacity, and the decay rate of the hydrogen storage capacity are shown in Table 3. The cumulative hydrogen storage capacity refers to the total hydrogen absorption capacity for 10 times. After the above-mentioned hydrogen absorption and hydrogen release were repeated 10 times, the decay rate of the hydrogen storage capacity was measured. Decay rate = (amount of hydrogen absorbed in the first hydrogen absorption / release - amount of hydrogen absorbed in the 10th hydrogen absorption / release) / amount of hydrogen absorbed in the first hydrogen absorption / release × 100%

[0273] (Hydrogen Storage Alloy Examples 57 to 67 and C20 to C24) According to the alloy composition, a total of about 1000 g of metal was weighed out, placed in a water-cooled crucible of an arc melting furnace, and melted under an argon atmosphere to obtain an alloy. The specific preparation includes the following: melting was performed under a high-purity Ar atmosphere (purity 99.999%) at the melting temperature, pressure, and time shown in Table 3; the alloy was naturally cooled to room temperature under an Ar atmosphere, then transferred to a vacuum annealing furnace and melted at 1 × 10 -4 The alloys were subjected to vacuum annealing at a background pressure of 1.0 Pa at the annealing temperatures and times shown in Table 3, and then naturally cooled to room temperature; the obtained alloys were crushed and sieved to obtain metal powders of 70 to 200 mesh; the powders were placed in a hydrogen storage tank, which was heated to 50 to 300°C under a vacuum of 0.1 Pa and kept at that temperature for 1 to 10 hours to activate the alloy powders (the specific temperature and time for activation are shown in Table 3), and hydrogen storage alloys 57 to 67 and C20 to C24 were obtained.

[0274] 1 kg of hydrogen storage alloy was placed in a hydrogen storage tank, and organic matter-containing hydrogen gas (methane content 0.1% by volume) at 20°C was introduced into the hydrogen storage tank as a model compound at a pressure of 2 MPa. In order to form a hydrogen-containing alloy, hydrogen gas was reacted with the hydrogen storage alloy, and when the hydrogen storage capacity of the hydrogen storage alloy reached 75% of the theoretical capacity, the introduction of the organic matter-containing hydrogen gas was stopped and purged for 20 minutes using hydrogen gas with a purity of 95%. The hydrogen storage tank was then heated to maintain the hydrogen storage alloy under 10 MPa, and continuous hydrogen release was performed. The purity of the hydrogen gas was analyzed by gas chromatography. The hydrogen gas purity is shown in Table 3. After the above-mentioned hydrogen absorption and hydrogen release were repeated 10 times, the cumulative hydrogen storage capacity and the decay rate of the hydrogen storage capacity were measured. The measurement results are shown in Table 3. Decay rate = (amount of hydrogen absorbed in the first hydrogen absorption / release - amount of hydrogen absorbed in the 10th hydrogen absorption / release) / amount of hydrogen absorbed in the first hydrogen absorption / release × 100% The cumulative amount of hydrogen storage refers to the total amount of hydrogen adsorption for 10 times.

[0275] The hydrogen storage alloy provided by the present invention has good resistance to contamination by organic matter, and even when the hydrogen gas contains organic matter, it exhibits favorable hydrogen adsorption efficiency and has a higher hydrogen storage capacity, making it possible to obtain high-pressure, high-purity hydrogen gas.

[0276] AB5 type hydrogen storage alloy Example 68: MmNi 3.55 Co 0.75 Mn 0.4 Al 0.3 , where Mm=La 0.61 Ce 0.16 Pr 0.04 Nd 0.19 According to the alloy formulation, a total of about 100 g of metal was weighed, placed in a water-cooled crucible of an arc melting furnace, and melted under an argon atmosphere to obtain an alloy. The preparation conditions included the following: melting under a high-purity Ar atmosphere (purity 99.999%) at a pressure of 0.9-1.0 atm, a current of 80-200 A, a voltage of 40 V, and a melting time of 10-60 min, followed by natural cooling to room temperature under an Ar atmosphere; the alloy was transferred to a high-vacuum annealing furnace and melted at 1 × 10 -4 The alloys were subjected to vacuum annealing at a background pressure of 0.1 Pa, an annealing temperature of 800-950°C, and an annealing time of 24-168 h, followed by natural cooling to room temperature; the alloys obtained were crushed and sieved to obtain metal powders of 70-200 mesh; the powders were placed in a hydrogen storage tank, which was heated to 200-400°C under a vacuum of 0.1 Pa, and kept at that temperature for 1-4 hours to activate the alloy powders.

[0277] The following test methods are used to demonstrate the effect of the dehydrogenation reaction of the liquid organic hydrogen storage raw material, and the separation effect by purification and pressurization, for the catalyst of Example 1 and the AB5 type hydrogen storage alloy of Example 68.

[0278] Using methylcyclohexane as the feedstock, the dehydrogenation reaction of methylcyclohexane was evaluated in a fixed-bed microreactor. The conditions for evaluation were reaction temperature of 350°C, pressure of 1MPa, flow rate of additional hydrogen gas of 150mL / min H2 (standard conditions), methylcyclohexane supply amount of 2mL / min, and catalyst loading amount of 20g. Specific parameters and results are shown below.

[0279] After cooling the dehydrogenation reaction product, separation was carried out in a separation tank placed in 20°C salt water while controlling the cooling temperature at 20°C. The liquid product was collected, and the gaseous product was introduced into a hydrogen storage alloy storage tank for hydrogen gas absorption. When the adsorption amount of the hydrogen storage alloy reached a set value, the hydrogen storage alloy storage tank was purged with 99% purity hydrogen gas for 30 minutes at the hydrogen adsorption temperature. The hydrogen storage alloy was then heated to release the hydrogen gas.

[0280] Here, conversion rate = reacted methylcyclohexane / total methylcyclohexane feed amount. The reaction products were analyzed by chromatography 10 minutes after the start of the reaction, and the conversion rate was calculated from the composition data.

[0281] Dehydrogenation reaction temperature: 350℃; Dehydrogenation reaction pressure: 1MPa; Dehydrogenation conversion of organic liquid: 98.50%; Hydrogen adsorption temperature: 20℃; Hydrogen partial pressure in hydrogen adsorption: 0.2MPa; Hydrogen release temperature: 200℃; Hydrogen partial pressure at hydrogen release: 35MPa; Hydrogen gas purity: 99.99%; Hydrogen storage capacity (200ml): 14.1g.

[0282] [Table 1]

[0283] [Table 2] TIFF0007625538000003.tif231169 TIFF0007625538000004.tif232169

[0284] [Table 3] JPEG0007625538000006.jpg255161 JPEG0007625538000007.jpg255161 JPEG0007625538000008.jpg255161 [Brief description of the drawings]

[0285] [Figure 1] Figure 1 shows an X-ray diffraction (XRD) spectrum of a support composition containing alumina and titanium oxide. In the figure, "1" shows the XRD spectrum of the support composition (alumina supporting titanium oxide) provided by the present invention, "2" shows the XRD spectrum of a support composition prepared by an impregnation method in which alumina supports Ti oxide, and "3" shows the XRD spectrum of a mixture obtained by mechanically mixing alumina and titanium dioxide. In the XRD curve, the peaks at 2θ=25.37°, 48.12°, 53.97°, and 55.1° are the diffraction peaks of TiO2 (anatase). [Diagram 2]FIG. 2 is an X-ray photoelectron spectroscopy (XPS) spectrum. In the figure, 1 shows the XPS spectrum of pure TiO2, and the other curves show the XPS spectrum of the support composition (alumina carrying titanium oxide) with different TiO2 contents prepared by the method of the present invention. M-2, M-4, M-7, and M-8 show the supports of Examples 2, 4, 7, and 8, respectively. In FIG. 2, the support composition provided by the present invention has a peak at 458.8 eV of the Ti 2P3 / 2 orbital electron binding energy (abbreviated as binding energy) shifted 0.6 to 0.7 eV to the high binding energy side, and a peak at 464.5 eV of the Ti 2P1 / 2 orbital electron binding energy shifted 0.8 to 0.9 eV to the high binding energy side, indicating the existence of an interaction between Ti and the alumina support. [Diagram 3] 3 is a schematic diagram of the high-purity high-pressure hydrogen gas provided by the present invention, in which 1 indicates an organic liquid storage tank, 2 indicates a raw material pump, 3 indicates a heat exchanger, 4 indicates a dehydrogenation reactor, 5 indicates a heat exchanger, 6 indicates a hydrogen storage tank, 7 indicates a one-way valve, 8 indicates an energy transmission system, 9 indicates a purge system, and 10 indicates a hydrogen storage control system.

Claims

1. A step (1) of contacting a liquid organic hydrogen storage raw material with a dehydrogenation catalyst to react with the raw material and obtaining a dehydrogenation reaction product containing hydrogen gas; (2) cooling the dehydrogenation reaction product to obtain a liquid product and a hydrogen-rich gaseous product, and recovering the liquid product; (3) contacting the hydrogen-rich gas with a hydrogen storage alloy to obtain a hydrogen-containing alloy and recovering unabsorbed gas; Optionally, a step (3a) of removing organic matter within the containment vessel of the hydrogen-containing alloy; (4) heating the hydrogen-containing alloy to release hydrogen gas, The hydrogen storage alloy is La 0.5 Ce 0.32 Nd 0.15 Pr 0.02 Y 0.01 Ni 4.4 Fe 0.55 Al 0.05 , La 0.5 Ce 0.32 Nd 0.15 Pr 0.02 Y 0.01 Ni 4.4 Fe 0.6 , La 0.8 Ce 0.15 Y 0.05 Ni 4 Mn 0.5 Al 0.5 , La 0.8 Ce 0.15 Y 0.05 Ni 4.5 Mn 0.5 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4 Co 0.8 Al 0.2 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4.2 Co 0.8 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.7 Al 0.1 Fe 0.2 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.8 Fe 0.2 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.3 Mn 0.1 Al 0.1 , La 0.8 Ce 0.15 N.D. 0.03 Y 0.02 Ni 4.5 Co 0.4 Mn 0.1 , La 0.97 Y 0.03 Ni 4 Co 1 A method for supplying high-purity hydrogen gas selected from the above.

2. In step (1), the reaction temperature in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 150 to 450° C.; The weight space velocity per hour in the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is 0.5 to 50 h -1 and the pressure during the contact reaction between the liquid organic hydrogen storage raw material and the dehydrogenation catalyst is a gauge pressure of 0.03 to 5 MPa; Optionally, when the mixture of the liquid organic hydrogen storage feedstock and hydrogen gas is contacted with the dehydrogenation catalyst, the hydrogen to hydrocarbon ratio, i.e., the molar ratio of hydrogen gas to the liquid organic hydrogen storage feedstock, is 0 to 10; In step (2), The cooling temperature for cooling the dehydrogenation reaction product is lower than the boiling point of the organic substance having the lowest boiling point that becomes liquid at room temperature and normal pressure; In step (3), the hydrogen-rich gas is a hydrogen-rich gas product or a hydrogen-containing gas obtained by further separation of the hydrogen-rich gas product, the method of further separation comprising temperature swing separation, membrane separation, pressure swing adsorption separation, or a combination thereof; The mass fraction of hydrogen gas in the hydrogen-rich gas is ≧80%; contacting the hydrogen-rich gas with the hydrogen storage alloy in a containment vessel or vessels of the hydrogen storage alloy; The number of the hydrogen storage alloys may be one or more, and the multiple hydrogen storage alloys may be used in a mixed form, and may be used in a series form, a parallel form, or a combination of series and parallel; the pressure at which the hydrogen-rich gas contacts the hydrogen storage alloy is 0.001 to 5 MPa, and when there are a plurality of hydrogen storage alloy storage containers connected in series, the hydrogen-rich gas contacts the hydrogen storage alloy at the most downstream side in the flow direction, and the contact pressure, also called the hydrogen adsorption pressure, is 0.05 to 5 MPa, the temperature at which the hydrogen-rich gas contacts the hydrogen-absorbing alloy, also referred to as the hydrogen adsorption temperature, is −70 to 100° C.; When contacting the hydrogen storage alloy, the temperature of the hydrogen-rich gas is lower than the boiling point of the liquid organic hydrogen storage raw material at normal pressure; In step (4), the temperature at which hydrogen gas is released from the hydrogen storage alloy, i.e., the temperature at which the hydrogen storage alloy is heated, which is abbreviated as hydrogen release temperature, is 150-450°C, the pressure of the released hydrogen gas is ≧35 MPa in order to obtain high-purity high-pressure hydrogen gas, or the partial pressure of the released hydrogen gas is 0.1-5 MPa in order to obtain high-purity hydrogen gas, and the hydrogen release temperature is higher than the hydrogen adsorption temperature; The liquid organic hydrogen storage raw material is an organic compound having a ring in a molecule and optionally containing a heteroatom, the heteroatom may be present on the ring. The method for supplying high purity hydrogen gas according to claim 1.

3. In step (3), the number of storage vessels for the hydrogen storage alloy is one or more, the hydrogen storage alloy in the storage vessel that comes into contact with hydrogen gas last in the order of contact with hydrogen gas is a hydrogen storage alloy having a high equilibrium pressure, and the hydrogen storage alloy having high equilibrium pressure has at least one temperature point within a temperature range of 150 to 450°C at which the equilibrium pressure in adsorption of hydrogen gas is 35 MPa or more; The method for supplying high purity hydrogen gas according to claim 1.

4. 2. The method for supplying high purity hydrogen gas according to claim 1, further comprising the step of: (3a) removing organic matter from within the hydrogen-containing alloy containment vessel by a purging method.

5. The method further includes a step of releasing hydrogen gas from the hydrogen-containing alloy and contacting the released hydrogen gas with another hydrogen storage alloy to form a hydrogen-containing alloy; The process is carried out one or more times, and the hydrogen storage alloy used in at least the last one of the processes is a hydrogen storage alloy having a high equilibrium pressure. The method for supplying high purity hydrogen gas according to claim 1.

6. the hydrogen storage alloy is a combination of a first hydrogen storage alloy and a second hydrogen storage alloy, The first hydrogen storage alloy is a magnesium-based A alloy used for contact with the hydrogen-rich gas. 2 B type hydrogen storage alloy, the second hydrogen storage alloy is used for pressurizing the first hydrogen storage hydrogen gas and has a high equilibrium pressure; The second hydrogen storage alloy is a rare earth alloy. 5 Type, Zirconium Titanium AB 2 and one or more of titanium-based AB type hydrogen storage alloys; First, the hydrogen-rich gas is passed through the first hydrogen storage alloy to separate impurities, then the high-purity hydrogen gas released from the first hydrogen storage alloy is brought into contact with the second hydrogen storage alloy, and then the hydrogen gas is released into the second hydrogen storage alloy under high pressure; The hydrogen release temperature of the first hydrogen storage alloy is higher than the hydrogen adsorption temperature of the second hydrogen storage alloy, and the temperature difference therebetween is ≧100° C.; the first hydrogen storage alloy and the second hydrogen storage alloy are present in storage tanks of different hydrogen storage alloys, and a heat exchange system is present between the storage tank of the first hydrogen storage alloy and the storage tank of the second hydrogen storage alloy; the hydrogen adsorption temperature during contact between the hydrogen-rich gas and the first hydrogen storage alloy is 20 to 150° C., and the hydrogen gas partial pressure is 0.001 to 0.1 MPa; the temperature at which hydrogen gas is released from the first hydrogen storage alloy, i.e., the hydrogen release temperature, is 150 to 450° C., and the hydrogen gas partial pressure during hydrogen release is 0.1 to 5 MPa; The second hydrogen storage alloy adsorbs hydrogen gas at a hydrogen adsorption temperature of −70 to 100° C. and at a hydrogen gas partial pressure of 0.1 to 5 MPa; The hydrogen release temperature of the second hydrogen storage alloy is 150 to 450°C, and the hydrogen gas partial pressure during hydrogen release is ≧35 MPa. The method for supplying high purity hydrogen gas according to claim 1.

7. The method further includes a step of introducing the released hydrogen gas into a hydrogen gas storage tank to store the hydrogen gas, or a step of directly using the resulting high purity high pressure hydrogen gas for refueling a hydrogen fuel cell vehicle. The method for supplying high purity hydrogen gas according to claim 1.

8. performing a dehydrogenation reaction of the liquid organic hydrogen storage raw material in a dehydrogenation reactor in the presence of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas; cooling and separating the dehydrogenation reaction product in a cooling separation unit to obtain a hydrogen-rich stream and an organic liquid; contacting a hydrogen-rich stream or a purified hydrogen-rich stream with a hydrogen-absorbing alloy in a hydrogen-absorbing alloy containment vessel to obtain a hydrogen-containing alloy; removing organic matter from within a storage vessel for the hydrogen absorbing alloy by a purging method using hydrogen gas having a purity of more than 90% by weight; and heating the hydrogen-containing alloy to release hydrogen gas to obtain high-pressure hydrogen gas, and supplying the obtained high-pressure hydrogen gas to a hydrogen consumption device or a high-pressure hydrogen gas storage tank for storage. The hydrogen storage alloy is La 0.5 Ce 0.32 Nd 0.15 Pr 0.02 Y 0.01 Ni 4.4 Fe 0.55 Al 0.05 , La 0.5 Ce 0.32 Nd 0.15 Pr 0.02 Y 0.01 Ni 4.4 Fe 0.6 , La 0.8 Ce 0.15 Y 0.05 Ni 4 Mn 0.5 Al 0.5 , La 0.8 Ce 0.15 Y 0.05 Ni 4.5 Mn 0.5 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4 Co 0.8 Al 0.2 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4.2 Co 0.8 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.7 Al 0.1 Fe 0.2 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.8 Fe 0.2 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.3 Mn 0.1 Al 0.1 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.4 Mn 0.1 , La 0.97 Y 0.03 Ni 4 Co 1 Selected from A highly efficient, distributed production method for high-purity, high-pressure hydrogen gas.

9. A high-purity high-pressure hydrogen gas supply system, a liquid organic hydrogen storage raw material storage-supply device for storing a liquid organic hydrogen storage raw material and supplying the liquid organic hydrogen storage raw material to a dehydrogenation reactor; a dehydrogenation liquid storage device for storing a liquid product obtained by dehydrogenating the liquid organic hydrogen storage raw material; a dehydrogenation reactor device for performing a dehydrogenation reaction of the liquid organic hydrogen storage raw material under the action of a dehydrogenation catalyst to obtain a dehydrogenation reaction product containing hydrogen gas; a cooling and separating unit for separating the dehydrogenation reaction product to obtain a hydrogen-rich gas product and a liquid product; a hydrogen storage / hydrogen supply device comprising a hydrogen storage alloy storage vessel and a hydrogen storage alloy heating system, the hydrogen-rich gas being brought into contact with the hydrogen storage alloy at low temperature and pressure to adsorb hydrogen, and after saturated adsorption, dehydrogenating the gas by heating; Optionally, a purge device used to remove organic matter from within the hydrogen storage container; A hydrogen gas supply device that supplies high-pressure hydrogen gas to a hydrogen consumption device or a hydrogen gas storage tank, The hydrogen storage alloy is La 0.5 Ce 0.32 Nd 0.15 Pr 0.02 Y 0.01 Ni 4.4 Fe 0.55 Al 0.05 , La 0.5 Ce 0.32 Nd 0.15 Pr 0.02 Y 0.01 Ni 4.4 Fe 0.6 , La 0.8 Ce 0.15 Y 0.05 Ni 4 Mn 0.5 Al 0.5 , La 0.8 Ce 0.15 Y 0.05 Ni 4.5 Mn 0.5 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4 Co 0.8 Al 0.2 , La 0.45 Ce 0.4 Nd 0.1 Pr 0.03 Y 0.02 Ni 4.2 Co 0.8 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.7 Al 0.1 Fe 0.2 , La 0.75 Ce 0.15 Nd 0.05 Pr 0.02 Y 0.03 Ni 4.8 Fe 0.2 , La 0.8 Ce 0.15 Nd 0.03 Y 0.02 Ni 4.5 Co 0.3 Mn 0.1 Al 0.1 , La 0.8 Ce 0.15 N.D. 0.03 Y 0.02 Ni 4.5 Co 0.4 Mn 0.1 , La 0.97 Y 0.03 Ni 4 Co 1 Selected from A high-purity, high-pressure hydrogen gas supply system.

10. A mobile hydrogen supply system comprising: a transportation vehicle; and the high-purity high-pressure hydrogen gas supply system according to claim 9, installed on the transportation vehicle.

11. A distributed hydrogen supply device comprising the high-purity high-pressure hydrogen gas supply system according to claim 9, and optionally comprising a high-pressure hydrogen gas storage tank.

12. The dehydrogenation catalyst is a catalyst for producing hydrogen gas by dehydrogenating an organic substance, The catalyst comprises a support composition for an organic dehydrogenation catalyst and an active component, The support composition comprises alumina and a modifying metal oxide providing a modifying property, the modifying metal oxide is titanium oxide or a combination of titanium oxide and zirconium oxide; η<0.3, θ≧5 (η=wt% content of the crystalline phase of the modified metal oxide in the support composition / wt% content of the chemical composition of the modified metal oxide in the support composition; θ=wt% content of the modified metal oxide at the surface of the support composition / wt% content of the modified metal oxide chemical composition in the support composition; Titanium oxide is TiO 2 and zirconium oxide is ZrO 2 (calculated as) The method according to claim 1 or 8.

13. The method of claim 12, wherein η=0.

14. The method of claim 13, wherein θ is 5 to 40.

15. The method of claim 14, wherein θ is between 5.4 and 34.

3.

16. TiO 2 Compared to the pure phase of In the XPS spectrum of the carrier composition, Ti 2P 3/2 The peak of the orbital electron binding energy at 458.8 eV shifts to the high binding energy side by 0.6 to 0.7 eV, and / or the 2P of Ti 1/2 The peak of the orbital electron binding energy at 464.5 eV is shifted by 0.8 to 0.9 eV to the higher binding energy side. The method of claim 12.

17. In the support composition, the mass fraction of alumina is 80-97.5% and the mass fraction of the modifying metal oxide is 2.5-20%; The modified metal oxide comprises titanium oxide, and in the carrier composition, the mass fraction of titanium dioxide is 2.5-20% and the mass fraction of zirconium dioxide is 0-8%; The support composition has at least one of the phase structures of γ-alumina, η-alumina, ρ-alumina, or χ-alumina; The specific surface area of ​​the carrier composition is 100 to 350 m 2 / g, and the pore volume of the carrier composition is 0.3 to 1.3 mL / g; The method of claim 12.

18. The active ingredient is any one of the following (1), (2) and (3): (1) at least one element from the group of precious metals; (2) Pt and at least one element of the first metal group; (3) Ni, at least one element of the second metal group, and optionally phosphorus; the precious metal group is a group consisting of elements selected from Pt, Pd, Ru, Re, Rh, Ir and Os; The first metal group is a group consisting of elements selected from Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca; The second metal group is a group consisting of elements selected from Zn, Sn, Cu, Fe, Ag, In, Re, Mo, Co, Ca, and W; In the catalyst, the content of the carrier composition is 70 to 99.9 wt %, and the content of the active component is 0.1 to 30 wt %. The method of claim 12.

19. The active component is (1) at least one element of the precious metal group, and in the catalyst, the content of the carrier composition is 90 to 99.9 wt %, and the content of the active component is 0.1 to 10 wt %; Or, the active component is (2) Pt and at least one element of the first metal group, the content of the carrier composition in the catalyst is 75 to 99.4 wt %, and the content of the active component is 0.6 to 25 wt %, Among the active components, the content of Pt calculated as a simple substance is 0.01 to 10 wt %, and the content of at least one element of the first metal group calculated as an oxide is 0.5 to 20 wt %, Or, The active components are (3) Ni, at least one element of the second metal group, and optionally phosphorus, and in the catalyst, the content of the support composition is 70 to 95 wt %, the content of the active components calculated as oxides is 5 to 30 wt %, the content of nickel calculated as NiO is 0.5 to 25 wt %, the content of at least one element of the second metal group calculated as oxides is 0 to 15 wt %, and the content of phosphorus calculated as P is 0.5 to 25 wt %. 2 O 5 The content calculated as is 0 to 15% by weight; 20. The method of claim 18.

20. The dehydrogenation catalyst is a catalyst for producing hydrogen gas by dehydrogenating an organic substance, The catalyst comprises a support composition for an organic dehydrogenation catalyst and an active component, The support composition comprises alumina and a modifying metal oxide providing a modifying property, the modifying metal oxide is titanium oxide or a combination of titanium oxide and zirconium oxide; η<0.3, θ≧5 (η=wt% content of the crystalline phase of the modified metal oxide in the support composition / wt% content of the chemical composition of the modified metal oxide in the support composition; θ=wt% content of the modified metal oxide at the surface of the support composition / wt% content of the modified metal oxide chemical composition in the support composition; Titanium oxide is TiO 2 and zirconium oxide is ZrO 2 (calculated as) The system of claim 9.

21. 21. The system of claim 20, wherein η=0.

22. The system of claim 21, wherein θ is between 5 and 40.

23. 23. The system of claim 22, wherein θ is between 5.4 and 34.

3.

24. TiO 2 Compared to the pure phase of In the XPS spectrum of the carrier composition, Ti 2P 3/2 The peak of the orbital electron binding energy at 458.8 eV shifts to the high binding energy side by 0.6 to 0.7 eV, and / or the 2P of Ti 1/2 The peak of the orbital electron binding energy at 464.5 eV is shifted by 0.8 to 0.9 eV to the higher binding energy side.

21. The system of claim 20.

25. In the support composition, the mass fraction of alumina is 80-97.5% and the mass fraction of the modifying metal oxide is 2.5-20%; The modified metal oxide comprises titanium oxide, and in the carrier composition, the mass fraction of titanium dioxide is 2.5-20% and the mass fraction of zirconium dioxide is 0-8%; The support composition has at least one of the phase structures of γ-alumina, η-alumina, ρ-alumina, or χ-alumina; The specific surface area of ​​the carrier composition is 100 to 350 m 2 / g, and the pore volume of the carrier composition is 0.3 to 1.3 mL / g; 21. The system of claim 20.

26. The active ingredient is any one of the following (1), (2) and (3): (1) at least one element from the group of precious metals; (2) Pt and at least one element of the first metal group; (3) Ni, at least one element of the second metal group, and optionally phosphorus; the precious metal group is a group consisting of elements selected from Pt, Pd, Ru, Re, Rh, Ir and Os; The first metal group is a group consisting of elements selected from Sn, V, Mo, Cr, Mn, Fe, Co, Ni, Cu, Ag, Ce, W, Cu, and Ca; The second metal group is a group consisting of elements selected from Zn, Sn, Cu, Fe, Ag, In, Re, Mo, Co, Ca, and W; In the catalyst, the content of the carrier composition is 70 to 99.9 wt %, and the content of the active component is 0.1 to 30 wt %.

21. The system of claim 20.

27. The active component is (1) at least one element of the precious metal group, and in the catalyst, the content of the carrier composition is 90 to 99.9 wt %, and the content of the active component is 0.1 to 10 wt %; Or, the active component is (2) Pt and at least one element of the first metal group, the content of the carrier composition in the catalyst is 75 to 99.4 wt %, and the content of the active component is 0.6 to 25 wt %, Among the active components, the content of Pt calculated as a simple substance is 0.01 to 10 wt %, and the content of at least one element of the first metal group calculated as an oxide is 0.5 to 20 wt %, Or, The active components are (3) Ni, at least one element of the second metal group, and optionally phosphorus, and in the catalyst, the content of the support composition is 70 to 95 wt %, the content of the active components calculated as oxides is 5 to 30 wt %, the content of nickel calculated as NiO is 0.5 to 25 wt %, the content of at least one element of the second metal group calculated as oxides is 0 to 15 wt %, and the content of phosphorus calculated as P is 0.5 to 25 wt %. 2 O 5 The content calculated as is 0 to 15% by weight.

27. The system of claim 26.

Citation Information

Patent Citations

  • Hydrogen-storing alloy, alloy powder for nickel hydrogen secondary battery negative electrode and negative electrode for the same

    JP2001266864A

  • Hydrogen storage alloy, electrode, nickel-hydrogen storage battery and method for producing hydrogen storage alloy

    JP2013199703A

  • Hydrogen feeding method and hydrogen feeding device

    JP2016196382A

  • Dehydrogenation catalyst and method for producing the same, and dehydrogenation treatment method using the same

    JP2018144016A